Electrolyte Composition for Lithium-Ion Battery Cells Having Negative Electrodes Comprising a Blend of Silicon-Carbon Composite Particles and Graphite Particles - Patent application
By using electrolytes of fluorine-containing vinyl charcoal, linear esters and branched esters in lithium-ion batteries, the problems of capacity degradation and gas generation in lithium-ion batteries are solved under high temperature or high voltage conditions, and better cycle stability and thermal stability are achieved.
Patent Information
- Application Number
- JP2024554212
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-16
- Filing Date
- 2023-03-17
- Publication Date
- 2025-04-11
AI Technical Summary
Existing lithium-ion batteries exhibit excessive capacity degradation, volume expansion and gas generation under high temperature or high voltage conditions, limiting their application range and life.
The electrolyte consisting of solvents containing vinyl fluoride carbonide (FEC), linear esters and branched esters is used to adjust the FEC content and ester content in the electrolyte to optimize the performance of the battery.
It improves the cycle stability, thermal stability and suppresses gas generation at high temperatures of lithium-ion batteries, extends the service life of the battery and increases its energy density.
Smart Images

Figure 2025509492000001_ABST
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This patent application claims the benefit of U.S. Non-provisional Application No. 18 / 185,207, filed March 16, 2023, entitled "ELECTROLYTE COMPOSITIONS FOR LITHIUM-ION BATTERY CELLS WITH ANODES COMPRISING A BLEND OF SILICON-CARBON COMPOSITE PARTICLES AND GRAPHITE PARTICLES," and U.S. Provisional Application No. 63 / 269,571, filed March 18, 2022, entitled "ELECTROLYTE COMPOSITIONS FOR LITHIUM-ION BATTERY CELLS WITH ANODES COMPRISING A BLEND OF SILICON-CARBON COMPOSITE PARTICLES AND GRAPHITE PARTICLES," both of which are assigned to the applicant and are expressly incorporated by reference in their entireties herein.
[0002] Field
[0003] Aspects of the present disclosure relate generally to energy storage devices, particularly battery technology. [Background technology]
[0004] background
[0005] Due in part to their relatively high energy density, relatively high specific energy, light weight, and potential for long life, high performance rechargeable batteries are desirable for a wide range of consumer electronics, electric vehicles, grid storage, and other important applications.
[0006] However, despite the increasing commercial popularity of batteries, further development of batteries is needed, particularly for applications in low or zero emission hybrid electric or all-electric vehicles, home appliances, wearable devices, energy efficient cargo ships and locomotives, drones, aerospace applications, and power grids. In particular, further improvements are desired for various rechargeable batteries, such as rechargeable Li and Li-ion batteries, rechargeable Na and Na-ion batteries, and rechargeable K and K-ion batteries, to name a few.
[0007] A wide range of electrolyte compositions can be utilized in the construction of Li and Li-ion batteries as well as other metal and metal-ion batteries. However, for improved cell performance (e.g., low and stable resistance, high cycling stability, high rate capability, good thermal stability, long calendar life, etc.), the optimal selection of electrolyte needs to be developed for the specific type and specific size of active particles in both the negative electrode (anode) and the positive electrode (cathode), the specific total battery cell capacity, and the specific operating conditions (e.g., temperature, charge rate, discharge rate, voltage range, capacity utilization, etc.). In many cases, the selection of electrolyte components and their ratios can be non-trivial and counter-intuitive.
[0008] In certain types of Li metal and Li ion rechargeable batteries, the charge-storing anode may comprise silicon-containing (Si) anode particles having a gravimetric capacity in the range of about 800 mAh / g to about 3000 mAh / g (per mass of the Si-containing anode particles without Li). A subset of such anodes includes anodes having electrode layers exhibiting a capacity in the range of about 400 mAh / g to about 2800 mAh / g (per mass of the electrode layer, not counting the mass of the current collector, without Li). Such types of charge-storing anodes offer great potential for increasing the gravimetric and volumetric energy of rechargeable batteries. Unfortunately, Li and Li ion battery cells with such anodes and conventional electrolytes have limited calendar life or such cells cannot be charged to high voltages (e.g., above about 4.1 to 4.3 V) and often require the use of such large amounts of conventional solid electrolyte interphase (SEI)-building additives to maintain acceptable cycling stability. The performance of such battery cells may be particularly poor when the cells are charged above about 4.3-4.4 V, and even more so when the cells are charged above about 4.5 V. However, the higher cell voltage, wider operating temperature window, and longer cycle life are advantageous for most applications. Such cells may suffer from excessive capacity degradation (e.g., greater than about 5%), large volume expansion (e.g., greater than about 10%), and significant gassing (e.g., greater than about 10% thickness change) when exposed to high temperatures (e.g., greater than about 50-90° C.) for extended periods of time (e.g., about 12-168 hours) at a fully charged state (e.g., about 90-100% state of charge, SOC). Passing such high temperature charging tests is necessary for most applications. The performance of such cells may also be poor when the negative electrode capacity loading (areal capacity) is moderate (e.g., about 2-4 mAh / cm 2 ), it is particularly insufficient when the areal capacity is high (e.g., about 4 to 12 mAh / cm 2 ), however, higher capacity loading is advantageous for increasing cell energy density and reducing cell fabrication costs.
[0009] In certain types of rechargeable batteries, charge-storing negative electrode materials may be produced as high-capacity (nano)composite powders (e.g., composed at least in part of active material nanomaterials or nanostructures) that exhibit moderately high volume change (e.g., about 8-180% by volume) during the first charge-discharge cycle, and moderate volume change (e.g., about 5-50% by volume) during subsequent charge-discharge cycles. A subset of such charge-storing negative electrode particles may include negative electrode particles having an average size (e.g., diameter or thickness) in the range of about 0.2 to about 40 microns (micrometers). Such types of charge-storing particles offer great prospects for scalable fabrication and the achievement of high cell-level energy density and other performance characteristics. Unfortunately, such particles are relatively new, and their use in cells employing conventional electrolytes may lead to relatively poor cell performance characteristics and limited cycle stability. The performance of such battery cells may be particularly poor when the cells are charged above about 4.1-4.3 V, even more so when the cells are charged above about 4.3-4.4 V, and even more so when the cells are charged above about 4.5 V. However, the higher cell voltage, wider operating temperature window, and longer cycle life are advantageous for most applications. Such cells may suffer from excessive capacity degradation (e.g., greater than about 5%), large volume expansion (e.g., greater than about 10%), and significant gassing when exposed to high temperatures ("hot gassing") (e.g., about 50-90°C, or higher) for extended periods of time (e.g., about 12-168 hours) at a fully charged state (e.g., about 90-100% state of charge, SOC). Passing such high temperature charging tests is necessary for most applications. High capacity (nano)composite anode capacity loading (areal capacity) is moderate (e.g., about 2-4 mAh / cm 2 ) and the areal capacity is higher (e.g., about 4 to 12 mAh / cm 2), cell performance may be particularly poor. However, higher capacity loading is advantageous for increasing cell energy density and reducing cell fabrication costs. Similarly, cell performance may be degraded if the porosity of such negative electrodes (e.g., the volume occupied by the space between the (nano)composite active negative electrode particles in the electrode and filled with electrolyte, excluding closed pores, if any, within the particles themselves that are inaccessible to electrolyte) becomes moderately small (e.g., about 25-35% by volume after the first charge-discharge cycle), and more so if the porosity of the negative electrodes becomes small (e.g., about 5-25% by volume after the first charge-discharge cycle), or if the amount of binder and conductive additive in the electrode becomes moderately small (e.g., about 5-15% by weight), and more so if the amount of binder and conductive additive in the electrode becomes small (e.g., about 0.5-5% by weight). However, higher electrode density and lower binder and conductive additive content are advantageous for increasing cell energy density and reducing costs. Lower binder content can also be advantageous for improving cell rate performance.
[0010] Examples of materials that exhibit moderately high volume changes (e.g., about 8-180% by volume) during the first charge-discharge cycle, and moderate volume changes (e.g., about 5-50% by volume) during subsequent charge-discharge cycles include (nano)composites, including so-called conversion-type (including both so-called chemical conversion and so-called "true conversion" subclasses), as well as so-called alloy-type active electrode materials. For metal-ion batteries (e.g., Li-ion batteries), examples of such conversion-type active electrode materials include, but are not limited to, metal fluorides (e.g., lithium fluoride, iron fluoride, copper fluoride, bismuth fluoride, mixtures and alloys thereof, etc.), metal chlorides, metal iodides, metal bromides, metal chalcogenides (e.g., sulfides, including lithium sulfide and other metal sulfides), sulfur, selenium, metal oxides (including but not limited to lithium oxide and silicon oxide), metal nitrides, metal phosphides (including lithium phosphide), metal hydrides, etc. For metal-ion batteries (e.g., Li-ion batteries), examples of such alloy-type electrode materials include, but are not limited to, silicon, germanium, antimony, aluminum, magnesium, zinc, gallium, arsenic, phosphorus, silver, cadmium, indium, tin, lead, bismuth, their alloys, and the like. These materials typically exhibit higher gravimetric and volumetric capacity than the so-called intercalation-type electrodes commonly used in commercial metal-ion (e.g., Li-ion) batteries. Alloy-type electrode materials are particularly advantageous for use in certain high-capacity negative electrodes for Li-ion batteries. Silicon-based alloy-type negative electrodes may be particularly attractive for such applications.
[0011] An example of a low swelling particle may include a mixture of graphite, a converted silicon anode containing a so-called silicon-graphite blend. In such a blend anode, the Si-containing anode particles (e.g., in the form of nanocomposite or core-shell particles) may contribute about 5% to about 98% (e.g., in some designs, about 20% to about 80% capacity), while the remainder of the capacity may be attributed to graphite or graphitic carbon materials. Such materials offer much higher volumetric and gravimetric energy densities than the pure intercalation graphite or graphitic carbon electrodes commonly used in commercial Li-ion batteries. Furthermore, in such a blend anode, the graphite or graphitic carbon materials may be composed of natural, artificial, or a mixture of natural and artificial graphite (or artificial soft or hard artificial graphitic carbon materials). In some designs, it may be more advantageous to use natural graphite or a mixture of natural and synthetic graphite to reduce the overall anode swelling of the blend, since such graphite particles may be able to accommodate the stress caused by the more swellable silicon-containing particles. Such properties of silicon-containing particle-graphite carbon blends (which may be referred to as silicon-graphite blends) may present an overall moderate volume change during the first cycle and a low volume change during subsequent charging cycles. Such properties may be advantageous for high capacity loading anodes. The development of improved electrolytes and additives for such silicon-graphite blends may improve overall cell performance due to, among other desirable properties, (i) slower capacity fading due to reduced swelling, (ii) reduced gassing at high temperatures (e.g., about 50-90°C or higher) at full charge (e.g., about 90-100% state of charge, SOC) for extended periods (e.g., about 12-168 hours), and / or (iii) reduced cell impedance due to reduced additive use.
[0012] Thus, there remains a need for improved electrolytes, additives, batteries, components and other related materials and fabrication processes. Summary of the Invention [Problem to be solved by the invention]
[0013] The following provides a simplified summary relevant to one or more aspects disclosed herein. As such, the following summary should not be considered an extensive overview relevant to all contemplated aspects, nor should the following summary be considered to identify key or critical elements relevant to all contemplated aspects or to delineate the scope of any particular aspect in combination. As such, the following summary has the sole purpose of presenting certain concepts relevant to one or more aspects related to the mechanisms disclosed herein in a simplified form prior to the detailed description presented below. [Means for solving the problem]
[0014] SUMMARY OF THE DISCLOSURE The embodiments disclosed herein address the above stated needs through the provision of improved electrolytes, batteries, components, and other related materials and fabrication processes.
[0015] One embodiment is directed to an electrolyte for a lithium ion battery comprising a primary lithium salt and a solvent composition. The solvent composition comprises fluoroethylene carbonate (FEC), at least one linear ester, and at least one branched ester. The mole fraction of FEC in the electrolyte ranges from about 2 mol % to about 30 mol % by volume (e.g., in some designs, from about 4 mol % to about 30 mol %). The combined mole fraction of the at least one linear ester and the at least one branched ester in the electrolyte is at least about 45 mol %. In some designs, the molar ratio of the at least one linear ester to the at least one branched ester ranges from about 1:10 to about 20:1 by volume (e.g., in some designs, from about 1:1 to about 10:1 by volume). The electrolyte is substantially free of tetracarbon cyclic carbonates.
[0016] Another embodiment is directed to an electrolyte for a lithium ion battery, comprising a primary lithium salt and a solvent composition. The solvent composition comprises fluoroethylene carbonate (FEC), at least one ester, and at least one non-FEC cyclic carbonate. The mole fraction of the FEC in the electrolyte is in the range of about 2 mol % to about 30 mol % (e.g., in some designs, in the range of about 4 mol % to about 30 mol %). The total mole fraction of the at least one ester in the electrolyte is at least 40 mol %. The total mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte is in the range of about 0.5 mol % to about 30 mol %. The electrolyte may advantageously be substantially free of tetracarbon cyclic carbonates.
[0017] Yet another embodiment is directed to an electrolyte for a lithium ion battery comprising a primary lithium salt and a solvent composition. The solvent composition comprises fluoroethylene carbonate (FEC) and at least one linear carbonate. The mole fraction of FEC in the electrolyte is in the range of about 2 mol% to about 20 mol% (e.g., in some designs, in the range of about 4 mol% to about 20 mol%). The total mole fraction of the at least one linear carbonate in the electrolyte is at least 40 mol%. The electrolyte may advantageously be substantially free of tetracarbon cyclic carbonates. The electrolyte may advantageously be substantially free of any linear carbonates with a molecular weight greater than 117.
[0018] Yet another embodiment is directed to an electrolyte for a lithium ion battery comprising a primary lithium salt and a solvent composition. The solvent composition comprises at least one tri-carbon cyclic carbonate and ethyl trimethylacetate (ET). The at least one tri-carbon cyclic carbonate comprises ethylene carbonate (EC). The mole fraction of ET in the electrolyte is at least about 50 mole %. The electrolyte may advantageously be substantially free of tetra-carbon cyclic carbonates.
[0019] Yet another embodiment is directed to a lithium ion battery including a negative electrode, a positive electrode, a separator interposed between the negative electrode and the positive electrode, and any of the aforementioned electrolytes ionically connecting the negative electrode and the positive electrode.
[0020] Yet another embodiment is directed to a lithium ion battery including a negative electrode current collector, a positive electrode current collector, a negative electrode disposed on and / or in the negative electrode current collector, a positive electrode disposed on and / or in the positive electrode current collector, and any of the aforementioned electrolytes ionically connecting the negative electrode and the positive electrode.
[0021] Another embodiment is directed to a battery pack or device utilizing at least one such lithium-ion battery cell containing any of the aforementioned electrolytes.
[0022] In one embodiment, an electrolyte for a lithium ion battery comprises a primary lithium salt; a solvent composition including fluoroethylene carbonate (FEC), at least one linear ester, and at least one branched ester; where the mole fraction of FEC in the electrolyte is in the range of about 2 mole % to about 30 mole %; the combined mole fraction of the at least one linear ester and the at least one branched ester in the electrolyte is at least about 45 mole %; the mole ratio of the at least one linear ester to the at least one branched ester is in the range of about 1:10 to about 20:1; and the electrolyte is substantially free of tetracarbon cyclic carbonates.
[0023] In some embodiments, the combined mole fraction of the at least one linear ester and the at least one branched ester in the electrolyte ranges from about 60 mol % to about 75 mol %.
[0024] In some embodiments, the molar ratio of the at least one linear ester to the at least one branched ester ranges from about 1:1 to about 2:1.
[0025] In some embodiments, the at least one linear ester is selected from methyl acetate (MA), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), ethyl propionate (EP), ethyl butyrate (EB), propyl acetate (PA), propyl propionate (PP), propyl butyrate (PB), butyl acetate (BA), butyl propionate (BP) and butyl butyrate (BB).
[0026] In some embodiments, the at least one branched ester is selected from the group consisting of methyl isobutyrate (MI), methyl trimethylacetate (MT), methyl isovalerate (MIV), methyl 2-methylbutyrate (MMB), ethyl isobutyrate (EI), ethyl trimethylacetate (ET), ethyl isovalerate (EIV), ethyl 2-methylbutyrate (EMB), propyl isobutyrate (PI), propyl trimethylacetate (PT), propyl isovalerate (PIV), propyl 2-methylbutyrate (PMB), butyl isobutyrate (BI), butyl trimethylacetate (BT), butyl isovalerate (BIV), butyl 2-methylbutyrate (BMB), isopropyl acetate (IPA), isopropyl propionate (IPP), isopropyl butyrate (IPB), isopropyl isobutyrate (I tert-butyl isovalerate (IPIV), isopropyl trimethylacetate (IPMB), tert-butyl acetate (TBA), tert-butyl propionate (TBP), tert-butyl butyrate (TBB), tert-butyl isobutyrate (TBI), tert-butyl trimethylacetate (TBT), tert-butyl isovalerate (TBIV), tert-butyl 2-methylbutyrate (TBMB), isobutyl acetate (IBA), isobutyl propionate (IBP), isobutyl butyrate (IBB), isobutyl isobutyrate (IBI), isobutyl trimethylacetate (IBT), isobutyl isovalerate (IBIV), and isobutyl 2-methylbutyrate (IBMB).
[0027] In some embodiments, at least one linear ester is ethyl propionate (EP) and at least one branched ester is ethyl isobutyrate (EI) and / or ethyl isovalerate (EIV).
[0028] In some embodiments, the electrolyte is substantially free of diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate.
[0029] In some embodiments, the primary lithium salt is LiPF6.
[0030] In some embodiments, the mole fraction of the predominant lithium salt in the electrolyte ranges from about 6 mol % to about 20 mol %.
[0031] In some embodiments, the one or more charge transfer additives are selected from lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium fluorosulfate (LiSOF), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
[0032] In some embodiments, the one or more charge transfer additives include lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluoro(oxalato)borate (LiDFOB).
[0033] In some embodiments, the mole fraction of the one or more charge transfer additives in the electrolyte ranges from about 0.1 mol % to about 6 mol %.
[0034] In some embodiments, the mole fraction of the one or more charge transfer additives ranges from about 0.5 mole % to about 1.5 mole %.
[0035] In some embodiments, the one or more high temperature storage additives are adiponitrile, 3-(2-cyanoethoxy)propanenitrile, 1,5-dicyanopentane, 1-(cyanomethyl)cyclopropane-1-carbonitrile, 4,4-dimethylheptanedinitrile, trans-1,4-dicyano-2-butene, 1,3,6-hexanetricarbonitrile, 3-{[1,3-bis(2-cyanoethoxy)propan-2-yl]oxy}propanenitrile, 1-(propan-2-yl)-1H-imidazole-4,5-dicarbonitrile, pyridine-2,6-dicarbonitrile, ethylene glycol bis(propionitrile) ether, 3-(triethoxysilyl)propionitrile, The alkyl group is selected from succinonitrile, benzonitrile, 4-(trifluoromethyl)benzonitrile, 1,2,2,3-propanetetracarbonitrile, triisopropyl borate, 1-propene 1,3-sultone, 1,3-propane sultone, phenyl disulfide, sulfolane, N,N,N,N-tetraethylsulfamide, succinic anhydride, maleic anhydride, tris(trimethylsilyl) phosphite, tris(trimethylsilyl) phosphate, dimethoxydiphenylsilane, tris(trimethylsilyl) borate, 3-(triethoxysilyl)propyl isocyanate, 1,3,2-dioxathiolane 2,2-dioxide (DTD), and methylene methanedisulfonate (MMDS).
[0036] In some embodiments, the molar fraction of the one or more high temperature storage additives in the electrolyte ranges from about 0.1 mol % to about 3 mol %.
[0037] In some embodiments, the at least one non-FEC cyclic carbonate is selected from ethylene carbonate and vinylene carbonate.
[0038] In some embodiments, the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte ranges from about 0.5 mol % to about 30 mol %.
[0039] In some embodiments, the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte ranges from about 1 mol % to about 6 mol %.
[0040] In one embodiment, a lithium ion battery includes a negative electrode current collector; a positive electrode current collector; a negative electrode disposed on and / or in the negative electrode current collector; a positive electrode disposed on and / or in the positive electrode current collector; and an electrolyte ionically connecting the negative electrode and the positive electrode.
[0041] In some embodiments, the negative electrode comprises a mixture of (A) silicon-containing particles comprising silicon and carbon, and (B) graphitic carbon particles comprising carbon and substantially free of silicon; the mass of silicon is in the range of about 1.5 wt.% to about 60 wt.% of the total mass of the negative electrode.
[0042] In one embodiment, an electrolyte for a lithium ion battery comprises a primary lithium salt; and a solvent composition including fluoroethylene carbonate (FEC), at least one ester, and at least one non-FEC cyclic carbonate; the mole fraction of FEC in the electrolyte is in the range of about 2 mol % to about 30 mol %; the total mole fraction of the at least one ester in the electrolyte is at least about 40 mol %; the total mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte is in the range of about 0.5 mol % to about 30 mol %; and the electrolyte is substantially free of tetracarbon cyclic carbonates.
[0043] In some embodiments, the total mole fraction of the at least one ester in the electrolyte ranges from about 45 mol % to about 70 mol %.
[0044] In some embodiments, the molar ratio of the at least one ester to the at least one non-FEC cyclic carbonate ranges from about 1.5:1 to about 20:1.
[0045] In some embodiments, the at least one ester is selected from the group consisting of methyl acetate (MA), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), ethyl propionate (EP), ethyl butyrate (EB), propyl acetate (PA), propyl propionate (PP), propyl butyrate (PB), butyl acetate (BA), butyl propionate (BP), butyl butyrate (BB), methyl isobutyrate (MI), methyl trimethylacetate (MT), methyl isovalerate (MIV), methyl 2-methylbutyrate (MMB), ethyl isobutyrate (EI), ethyl trimethylacetate (ET), ethyl isovalerate (EIV), ethyl 2-methylbutyrate (EMB), propyl isobutyrate (PI), propyl trimethylacetate (PT), propyl isovalerate (PIV), 2-propyl methylbutyrate (PMB), butyl isobutyrate (BI), butyl trimethylacetate (BT), butyl isovalerate (BIV), 2-methyl Selected from butyl butyrate (BMB), isopropyl acetate (IPA), isopropyl propionate (IPP), isopropyl butyrate (IPB), isopropyl isobutyrate (IPI), isopropyl trimethylacetate (IPT), isopropyl isovalerate (IPIV), isopropyl 2-methylbutyrate (IPMB), tert-butyl acetate (TBA), tert-butyl propionate (TBP), tert-butyl butyrate (TBB), tert-butyl isobutyrate (TBI), tert-butyl trimethylacetate (TBT), tert-butyl isovalerate (TBIV), tert-butyl 2-methylbutyrate (TBMB), isobutyl acetate (IBA), isobutyl propionate (IBP), isobutyl butyrate (IBB), isobutyl isobutyrate (IBI), isobutyl trimethylacetate (IBT), isobutyl isovalerate (IBIV), and isobutyl 2-methylbutyrate (IBMB).
[0046] In some embodiments, the at least one ester comprises ethyl acetate (EA), ethyl propionate (EP), ethyl isobutyrate (EI), and / or ethyl isovalerate (EIV).
[0047] In some embodiments, the at least one ester comprises a mixture of ethyl acetate (EA) and ethyl propionate (EP).
[0048] In some embodiments, the at least one non-FEC cyclic carbonate is selected from ethylene carbonate and vinylene carbonate.
[0049] In some embodiments, the electrolyte is substantially free of diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate.
[0050] In some embodiments, the primary lithium salt is LiPF6.
[0051] In some embodiments, the mole fraction of the predominant lithium salt in the electrolyte ranges from about 6 mol % to about 20 mol %.
[0052] In some embodiments, the electrolyte further comprises one or more charge transfer additives selected from lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium fluorosulfate (LiSOF), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
[0053] In some embodiments, the one or more charge transfer additives include lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluoro(oxalato)borate (LiDFOB).
[0054] In some embodiments, the mole fraction of the one or more charge transfer additives in the electrolyte ranges from about 0.1 mol % to about 6 mol %.
[0055] In some embodiments, the mole fraction of the one or more charge transfer additives ranges from about 0.5 mole % to about 1.5 mole %.
[0056] In some embodiments, the electrolyte is adiponitrile, 3-(2-cyanoethoxy)propanenitrile, 1,5-dicyanopentane, 1-(cyanomethyl)cyclopropane-1-carbonitrile, 4,4-dimethylheptanedinitrile, trans-1,4-dicyano-2-butene, 1,3,6-hexanetricarbonitrile, 3-{[1,3-bis(2-cyanoethoxy)propan-2-yl]oxy}propanenitrile, 1-(propan-2-yl)-1H-imidazole-4,5-dicarbonitrile, pyridine-2,6-dicarbonitrile, ethylene glycol bis(propionitrile) ether, 3-(triethoxysilyl)propionitrile, succinonitrile, benzonitrile, The composition further comprises one or more high temperature storage additives selected from 4-(trifluoromethyl)benzonitrile, 1,2,2,3-propanetetracarbonitrile, triisopropyl borate, 1-propene 1,3-sultone, 1,3-propane sultone, phenyl disulfide, sulfolane, N,N,N,N-tetraethylsulfamide, succinic anhydride, maleic anhydride, tris(trimethylsilyl)phosphite, tris(trimethylsilyl)phosphate, dimethoxydiphenylsilane, tris(trimethylsilyl)borate, 3-(triethoxysilyl)propyl isocyanate, 1,3,2-dioxathiolane 2,2-dioxide (DTD), and methylene methanedisulfonate (MMDS).
[0057] In some embodiments, the molar fraction of the one or more high temperature storage additives in the electrolyte ranges from about 0.1 mol % to about 3 mol %.
[0058] In one embodiment, a lithium ion battery includes a negative electrode current collector; a positive electrode current collector; a negative electrode disposed on and / or in the negative electrode current collector; a positive electrode disposed on and / or in the positive electrode current collector; and an electrolyte ionically connecting the negative electrode and the positive electrode.
[0059] In some embodiments, the negative electrode comprises a mixture of (A) silicon-containing particles comprising silicon and carbon, and (B) graphitic carbon particles comprising carbon and substantially free of silicon; the mass of silicon is in the range of about 1.5 wt.% to about 60 wt.% of the total mass of the negative electrode.
[0060] In some embodiments, the negative electrode comprises graphitic carbon particles that comprise carbon and are substantially free of silicon.
[0061] In some embodiments, the primary lithium salt is LiPF6.
[0062] In one embodiment, an electrolyte for a lithium ion battery comprises a primary lithium salt; and a solvent composition comprising fluoroethylene carbonate (FEC) and at least one linear carbonate; the mole fraction of the FEC in the electrolyte is in the range of about 2 mol % to about 20 mol %; the total mole fraction of the at least one linear carbonate in the electrolyte is at least 40 mol %; the electrolyte is substantially free of tetracarbon cyclic carbonates; and the electrolyte is substantially free of any linear carbonates having a molecular weight greater than 117.
[0063] In some embodiments, the at least one linear carbonate is selected from ethyl methyl carbonate and dimethyl carbonate; the total mole fraction of the at least one linear carbonate in the electrolyte is in the range of about 60 mol % to about 75 mol %.
[0064] In some embodiments, the mole fraction of the predominant lithium salt in the electrolyte ranges from about 6 mol % to about 20 mol %.
[0065] In some embodiments, the one or more charge transfer additives are selected from lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium fluorosulfate (LiSOF), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
[0066] In some embodiments, the one or more charge transfer additives include lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), and / or lithium difluoro(oxalato)borate (LiDFOB).
[0067] In some embodiments, the mole fraction of the one or more charge transfer additives in the electrolyte ranges from about 0.1 mol % to about 6 mol %.
[0068] In some embodiments, the mole fraction of the one or more charge transfer additives ranges from about 0.5 mole % to about 1.5 mole %.
[0069] In some embodiments, the one or more high temperature storage additives are adiponitrile, 3-(2-cyanoethoxy)propanenitrile, 1,5-dicyanopentane, 1-(cyanomethyl)cyclopropane-1-carbonitrile, 4,4-dimethylheptanedinitrile, trans-1,4-dicyano-2-butene, 1,3,6-hexanetricarbonitrile, 3-{[1,3-bis(2-cyanoethoxy)propan-2-yl]oxy}propanenitrile, 1-(propan-2-yl)-1H-imidazole-4,5-dicarbonitrile, pyridine-2,6-dicarbonitrile, ethylene glycol bis(propionitrile) ether, 3-(triethoxysilyl)propionitrile, The alkyl group is selected from succinonitrile, benzonitrile, 4-(trifluoromethyl)benzonitrile, 1,2,2,3-propanetetracarbonitrile, triisopropyl borate, 1-propene 1,3-sultone, 1,3-propane sultone, phenyl disulfide, sulfolane, N,N,N,N-tetraethylsulfamide, succinic anhydride, maleic anhydride, tris(trimethylsilyl) phosphite, tris(trimethylsilyl) phosphate, dimethoxydiphenylsilane, tris(trimethylsilyl) borate, 3-(triethoxysilyl)propyl isocyanate, 1,3,2-dioxathiolane 2,2-dioxide (DTD), and methylene methanedisulfonate (MMDS).
[0070] In some embodiments, the molar fraction of the one or more high temperature storage additives in the electrolyte ranges from about 0.1 mol % to about 3 mol %.
[0071] In some embodiments, the electrolyte further comprises at least one non-FEC cyclic carbonate selected from ethylene carbonate and vinylene carbonate.
[0072] In some embodiments, the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte ranges from about 1 mol % to about 30 mol %.
[0073] In some embodiments, the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte ranges from about 15 mol % to about 30 mol %.
[0074] In one embodiment, a lithium ion battery includes a negative electrode current collector; a positive electrode current collector; a negative electrode disposed on and / or in the negative electrode current collector; a positive electrode disposed on and / or in the positive electrode current collector; and an electrolyte ionically connecting the negative electrode and the positive electrode.
[0075] In some embodiments, the negative electrode comprises a mixture of (A) silicon-containing particles comprising silicon and carbon, and (B) graphitic carbon particles comprising carbon and substantially free of silicon; the mass of silicon is in the range of about 1.5 wt.% to about 60 wt.% of the total mass of the negative electrode.
[0076] In one embodiment, an electrolyte for a lithium ion battery comprises a primary lithium salt; and a solvent composition comprising at least one tri-carbon cyclic carbonate and ethyl trimethylacetate (ET); where the at least one tri-carbon cyclic carbonate comprises ethylene carbonate (EC); the mole fraction of ET in the electrolyte is at least about 50 mole %; and the electrolyte is substantially free of tetra-carbon cyclic carbonates.
[0077] In some embodiments, the molar fraction of ET in the electrolyte ranges from about 50 mol % to about 80 mol %.
[0078] In some embodiments, the primary lithium salt is LiPF6.
[0079] In some embodiments, the mole fraction of the predominant lithium salt in the electrolyte ranges from about 6 mol % to about 20 mol %.
[0080] In some embodiments, the mole fraction of the at least one tricarbon cyclic carbonate in the electrolyte ranges from about 20 mol % to about 40 mol %.
[0081] In some embodiments, the at least one tricarboncyclic carbonate comprises fluoroethylene carbonate (FEC) and / or vinylene carbonate.
[0082] In some embodiments, the electrolyte is substantially free of linear carbonates.
[0083] In one embodiment, a lithium ion battery includes a negative electrode current collector; a positive electrode current collector; a negative electrode disposed on and / or in the negative electrode current collector; a positive electrode disposed on and / or in the positive electrode current collector; and an electrolyte ionically connecting the negative electrode and the positive electrode.
[0084] In some embodiments, the negative electrode comprises graphitic carbon particles that comprise carbon and are substantially free of silicon.
[0085] Other objects and advantages associated with the embodiments disclosed herein will become apparent to one of ordinary skill in the art based on the accompanying drawings and detailed description.
[0086] The accompanying drawings are presented to aid in the description of embodiments of the present disclosure and are provided only to illustrate, not limit, the embodiments. Unless otherwise stated or implied by context, different shading, shading and / or fill patterns in the drawings are intended only to depict distinctions between different components, elements, features, etc., and are not intended to suggest the use of particular materials, colors or other characteristics that may be defined outside of this disclosure for the specific patterns used. [Brief description of the drawings]
[0087] [Figure 1] FIG. 1 illustrates an example of a Li-ion battery in which the electrolytes, components, materials, methods, and other techniques described herein may be implemented. [Diagram 2] 1A-1D show selected examples of cyclic carbonates that may be used in certain electrolytes. [Diagram 3]FIG. 1 shows selected examples of linear carbonates that may be used in certain electrolytes. [Figure 4] FIG. 1 shows selected examples of linear esters suitable for use in the electrolyte. [Diagram 5] FIG. 1 shows selected examples of linear esters suitable for use in the electrolyte. [Figure 6] FIG. 1 shows selected examples of branched esters suitable for use in the electrolyte. [Figure 7] FIG. 1 shows selected examples of branched esters suitable for use in the electrolyte. [Figure 8] FIG. 1 shows selected examples of branched esters suitable for use in the electrolyte. [Figure 9] FIG. 1 shows selected examples of branched esters suitable for use in the electrolyte. [Figure 10] FIG. 1 shows selected examples of branched esters suitable for use in the electrolyte. [Figure 11] FIG. 1 shows selected examples of high temperature storage additives suitable for use in the electrolyte. [Figure 12] FIG. 1 shows selected examples of high temperature storage additives suitable for use in the electrolyte. [Figure 13] FIG. 1 shows selected examples of high temperature storage additives suitable for use in the electrolyte. [Figure 14] FIG. 1 shows selected examples of high temperature storage additives suitable for use in the electrolyte. [Figure 15] FIG. 1 shows selected examples of high temperature storage additives suitable for use in the electrolyte. [Figure 16] 1 is a table (Table 1) showing electrolyte composition data for electrolytes (ELY) #1, #2, #3, #4, #5, #6, #7, #8, #9, #10, #11, #12, #13, and #14. [Figure 17-1]17A, 17B, and 17C are graphical plots of capacity retention (in % of initial capacity) as a function of cycle number for Li-ion battery cells containing ELY #1, #2, and #3, respectively. FIGs. 17F, 17G, and 17H are graphical plots of the estimated number of cycles to 80% of initial capacity as a function of cycle number for Li-ion battery cells containing ELY #1, #2, and #3, respectively. ELY #1, #2, and #3 are examples of electrolytes containing esters. [Figure 17-2] Figures 17D and 17E are graphical plots of capacity retention (in % of initial capacity) as a function of cycle number for Li-ion battery cells containing ELY #4 and #5, respectively. Figures 17I and 17J are graphical plots of the estimated number of cycles to 80% of initial capacity as a function of cycle number for Li-ion battery cells containing ELY #4 and #5, respectively. ELY #4 and #5 are examples of electrolytes containing esters. [Figure 18] Figures 18A and 18B are graphical plots of capacity retention (in % of initial capacity) as a function of cycle number for Li-ion battery cells containing ELY #6 and #7, respectively. Figures 18C and 18D are graphical plots of the estimated number of cycles to 80% of initial capacity as a function of cycle number for Li-ion battery cells containing ELY #6 and #7, respectively. ELY #6 and #7 are examples of electrolytes containing esters. [Figure 19] Figures 19A and 19B are graphical plots of capacity retention (in % of initial capacity) as a function of cycle number for Li-ion battery cells containing ELY #8 and #9, respectively. Figures 19C and 19D are graphical plots of the estimated number of cycles to 80% of initial capacity as a function of cycle number for Li-ion battery cells containing ELY #8 and #9, respectively. ELY #8 and #9 are examples of electrolytes containing linear carbonates. [Figure 20-1]20A, 20B, 20C show cycle life test results for Li-ion battery test cells containing electrolytes ELY #10, 11, and 12. Figures 20A, 20B, and 20C are graphical plots of capacity retention (in % of initial capacity) as a function of cycle number for Li-ion battery cells containing ELY #10, #11, and #12, respectively. ELY #10, #11, and #12 are examples of electrolytes containing at least one cyclic carbonate and branched ester. [Figure 20-2] 20D, 20E, and 20F show cycle life test results for Li-ion battery test cells containing electrolytes ELY #10, 11, and 12. FIGs. 20D, 20E, and 20F are graphical plots of the estimated number of cycles to 80% of the initial capacity as a function of cycle number for Li-ion battery cells containing ELY #10, #11, and #12, respectively. ELY #10, #11, and #12 are examples of electrolytes containing at least one cyclic carbonate and branched ester. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0088] Aspects of the invention are disclosed in the following description and associated drawings directed to specific embodiments of the invention. The term "embodiments of the invention" does not necessarily require that all embodiments of the invention include the discussed features, advantages, processes or modes of operation, and alternative embodiments may be devised without departing from the scope of the invention. Additionally, well-known elements of the invention may not be described in detail or may be omitted so as not to obscure other more relevant details.
[0089] Any numerical range described herein with respect to any embodiment of the invention is intended not only to define the upper and lower limits of the relevant numerical range, but also to implicitly disclose each individual value within that range in units or increments consistent with the level of precision by which the upper and lower limits are characterized. For example, a numerical distance range of 7 nm to 20 nm (i.e., a precision level of 1 unit or increment) encompasses the set [7, 8, 9, 10, ..., 19, 20] (in nm), as if the intervening numerical values from 8 to 19 in units or increments of 1 were explicitly disclosed. In another example, a temperature range of about -120°C to about -60°C encompasses the set of temperature ranges (in °C) of about -120°C to about -119°C, about -119°C to about -118°C, ... about -61°C to about -60°C, as if the intervening numerical values (in °C) between -120°C and -60°C in the incremental range were explicitly disclosed. In yet another example, a numerical percentage range of 30.92% to 47.44% (i.e., at the level of precision of hundredths or increments) encompasses the set (units %) of [30.92, 30.93, 30.94, ..., 47.43, 47.44], as if the intervening numerical values between 30.92 and 47.44 in hundredths or increments were expressly disclosed. Thus, any intervening numerical values encompassed within any disclosed numerical range are intended to be construed as if those intervening numerical values were expressly disclosed, whereby any such intervening numerical values may constitute their own upper and / or lower limits of subranges falling within the broader range. Each subrange (e.g., each range that includes at least one intervening numerical value from the broader range as an upper and / or lower limit) is intended to be construed thereby as implicitly disclosed by the express disclosure of the broader range. In yet another example, a numerical range having upper and lower limits defined at different levels of precision shall be interpreted in increments corresponding to the boundary having the higher level of precision.For example, a numerical percentage range of 30.92% to 47.4% (i.e., precision levels of hundredths and tenths, respectively) encompasses the set (units %) of [30.92, 30.93, 30.94, …, 47.39, 47.40] as if 47.4% (tenths) were stated as 47.40% (hundredths), and as if the intervening numerical values between 30.92 and 47.40 were in hundredths or increments and explicitly disclosed.
[0090] It will be appreciated that the level of precision of any particular measurement, threshold, or other imprecise parameter may vary based on a variety of factors, such as, for example, the measurement equipment, environmental conditions, etc. Hereinafter, reference to such a measurement or threshold may be interpreted as the respective value thereby assuming a pseudo-precise level of precision (e.g., a threshold of 80% includes 80.0000...%). Alternatively, reference to such a measurement or threshold may be described via a modifier that captures the pseudo-precise value, plus an extending range higher and / or lower than the pseudo-precise value(s). For example, the above threshold of 80% may be interpreted as "about," "approximately," "nearly," or "to" 80%, which encompasses "exactly" 80% (e.g., 80.0000...%), plus a range of approximately 80%. In some designs, the range encompassed for a measurement or threshold via the modifier "about," "approximately," "nearly," or "to" may encompass the level of precision that the respective measurement or threshold can be measured by the most accurate commercially available equipment as of the priority date of this application.
[0091] In some embodiments described below, certain parameters (e.g., temperature, state of charge (SOC), etc.) are defined in terms of relative terms, such as, for example, low, decreased, high, increased, elevated, etc. With respect to temperature, unless otherwise indicated, the relative terms may be characterized with respect to a battery cell storage temperature or a battery cell operating temperature depending on the context of the relevant example. With respect to SOC, unless otherwise indicated, a high SOC may be defined as greater than about 70% SOC (e.g., about 70-80% SOC in some designs; about 80-90% SOC in some designs; about 90-100% SOC in some designs).
[0092] In some instances, Li or Li-ion batteries are described due to the dominance of Li-ion batteries in the market and their high energy characteristics, but it will be recognized that other metal or metal ion batteries (e.g., Na and Na-ion, K or K-ion, Mg or Mg-ion, Ca or Ca-ion, various mixed metal ion, etc. batteries) may be used instead with the electrolyte or electrolyte solvent composition of the present disclosure. In this case, one or more salts of Na, K or other metals may be used in place of or in addition to the appropriate salt(s) of Li. In this case, Na, K, Mg, Ca or other corresponding metals, or mixtures thereof, may be used in place of or in addition to Li in the positive electrode composition. In this case, the blended negative electrode may also be designed to include different compositions (e.g., hard or soft carbon may be used in place of or in addition to graphite, Sn or Sb may be used in place of or in addition to Si, etc.).
[0093] In one or more embodiments of the present disclosure, preferred Li or Li-ion battery cells may include active positive electrode materials that include nickel (Ni), cobalt (Co), manganese (Mn), titanium (Ti) and / or iron (Fe) - including, but not limited to, lithium cobalt oxide (LCO), various lithium nickel cobalt manganese oxides (NCM), various lithium nickel cobalt aluminum oxides (NCA), various lithium nickel cobalt manganese aluminum oxides (NCMA), various lithium nickel oxides (NCO), various lithium manganese oxides (LMO), various lithium manganese nickel oxides (LNMO), to name a few. Other examples of preferred or suitable Li-ion positive electrodes include, but are not limited to, various olivine compounds (e.g., lithium iron phosphate, LFP, lithium manganese phosphate, LNP, lithium iron manganese phosphate, LMFP, lithium vanadium fluorophosphate, LVFP, lithium iron fluorosulfate, LFSFP, etc.), various high voltage spinels (e.g., LNMO), various excess Li materials such as disordered rock salts (e.g., transition metal oxides and oxyfluorides, e.g., those containing Mn, Mo, Cr, Ti, and / or Nb, e.g., lithium molybdenum chromium oxide and oxyfluoride, lithium manganese niobium oxide and oxyfluoride, lithium manganese titanium oxide and oxyfluoride, lithium nickel titanium molybdenum oxide and oxyfluoride, and many others), to name a few.
[0094] In some preferred examples, the positive electrode active material (e.g., LCO, NCM, NCA, NCMA, NCO, LMO, LNMO, LMFP, etc.) may be doped with one or more metals or metalloids (e.g., Mg, Ca, Sr, Ba, Sc, Y, La or the lanthanides, Ti, V, Cr, Ce, Zn, Zr, Nb, Mo, Tc, In, Sn, Sb, Si, Hf, Ta, W, Tl, etc.).
[0095] In some preferred examples, the surface of the positive electrode active material (e.g., LCO, NCM, NCA, NCMA, NCO, LMO, LNMO, LMFP, etc.) may be coated with one or more layers of ceramic materials having distinct compositions or microstructures. Illustrative examples of preferred coating materials for the preferred active positive electrode materials may include, but are not limited to, metal oxides containing one or more of the following metals: Ti, Al, Mg, Sr, Li, Si, Sn, Sb, Nb, W, Cr, Mo, Hf, Ta, B, Y, La, Ce, Zn, and Zr. Examples of such oxides may include, but are not limited to, titanium oxide (e.g., TiO), aluminum oxide (e.g., AlO), magnesium oxide (e.g., MgO), silicon oxide (e.g., SiO), boron oxide (e.g., BO), lanthanum oxide (LaO), zirconium oxide (e.g., ZrO), as well as other suitable metal or mixed metal oxides, and various mixtures and alloys thereof.
[0096] In some designs, the preferred positive current collector may comprise aluminum or an aluminum alloy, and in some designs, the preferred negative current collector may comprise copper or a copper alloy.
[0097] In some designs, the preferred battery cells may include a polymer separator, a polymer ceramic composite separator, or a ceramic separator. In some designs, such separators may be free-standing or integrated into the negative or positive electrodes, or both. In some designs, the polymer separator may include or be made from polyethylene, polypropylene, or mixtures thereof. In some preferred examples, the surface of the polymer separator may be coated with a layer of ceramic material. Examples of preferred coating materials for the polymer separator may include, but are not limited to, titanium oxide (TiO2), silicon oxide (SiO2), aluminum oxide (Al2O3), aluminum hydroxide, zirconium oxide (ZrO2), magnesium oxide (MgO), magnesium hydroxide, magnesium oxyhydroxide, or various alloys or mixtures thereof.
[0098] In some designs, a preferred battery cell may include one or more of the following materials in its negative electrode composition: (i) silicon (Si), including doped or heavily doped Si; (ii) silicon oxide (SiO x(iii) silicon nitride or silicon oxynitride; (iv) silicon phosphide; (v) silicon binary or ternary alloys or other silicon alloys (e.g., Si-Mg, Si-Al, Si-Al-Mg, Si-Fe, Si-Ge, etc.), (vi) silicon-containing or silicon alloy or silicon oxide or silicon nitride or silicon oxynitride composites or nanocomposites; (vii) silicon carbide or silicon oxycarbide; (viii) composites or nanocomposites containing both silicon and carbon atoms, such as silicon-carbon (Si-C) nanocomposites (e.g., as used herein, nanocomposites). A nanocomposite or (nano)composite is at least partially composed of an active material nanomaterial or nanostructure or nanoparticle, whether or not the body or (nano)composite is itself a nanomaterial; as used herein, it is also noted that a silicon-carbon (or Si-C) composite or nanocomposite may contain elements other than Si and C, so long as Si and C comprise the majority of the elements that contribute to about 75-100% by weight of the total weight fraction of the combined Si and C of the composite or nanocomposite; (ix) or natural or synthetic graphite; (x) soft or hard carbon; and (xi) various mixtures and combinations thereof.
[0099] In some preferred examples, the negative electrode material comprises a mixture of silicon-carbon nanocomposite (sometimes abbreviated herein as Si-C nanocomposite) and one or more graphites (or hard or soft synthetic carbons, etc.) (e.g., the C-portion of the Si-C nanocomposite and another graphite or synthetic carbon). In some embodiments, the Si-C nanocomposite comprises a composite particle that may include Si nanoparticles embedded in the pores of the porous carbon skeleton particle. Such porous carbon skeleton particles may include graphene material and / or graphite material. In some embodiments, the Si-C nanocomposite may contain micropores (pores less than 2 nm), mesopores (pores between 2 and 50 nm), and / or macropores (pores greater than 50 nm) in various ratios (e.g., about 20-70-10 volume % ratio, or, for example, about 60-35-5 volume % ratio, or, for example, about 80-10-10 volume % ratio, or, for example, about 10-40-50 volume % ratio) as determined by known (e.g., nitrogen) sorption experiments or other suitable measurements (e.g., electron microscopy, neutron scattering, x-ray scattering, x-ray imaging, etc.). In some preferred designs, at least some of such pores may be closed (e.g., inaccessible to nitrogen during nitrogen sorption experiments). In some preferred designs, at least some of such pores may be open (e.g., accessible to nitrogen during nitrogen sorption experiments).
[0100] In one or more embodiments of the present disclosure, a preferred battery cell has relatively high areal capacity loadings on its electrodes (negative and positive electrodes), e.g., approximately 2.0 mAh / cm 2 ~Approximately 12mAh / cm 2 (In some embodiments, about 2 to about 3.5 mAh / cm 2 in other embodiments, from about 3.5 to about 4.5 mAh / cm 2 in other embodiments, from about 4.5 to about 6.5 mAh / cm 2 in other embodiments, from about 6.5 to about 8 mAh / cm 2 in other embodiments, from about 8 to about 12 mAh / cm 2 ) may also be included.
[0101] While the following description may also describe certain examples of Li-free material formulations (such as in silicon-containing nanocomposite anodes or metal fluoride cathodes), it will be appreciated that various embodiments may be applicable to Li-containing electrodes and active materials (e.g., partially or fully lithiated Si-containing anodes or partially or fully lithiated Si-containing anode particles, partially or fully lithiated metal-containing fluoride cathodes (e.g., mixtures of LiF with metals such as Cu, Fe, Ni, Bi, and various other metals, metal alloys and mixtures of such metals with other metals, etc.) or partially or fully lithiated metal halide cathode particles, partially or fully lithiated chalcogenides (e.g., LiS, LiS / metal mixtures, LiSe, LiSe / metal mixtures, LiS-LiSe mixtures, various other compositions including lithiated chalcogenides, etc.), partially or fully lithiated metal oxides (e.g., LiO, LiO / metal mixtures, etc.), partially or fully lithiated carbon, among others). In some designs, various material properties (e.g., at the particle level, interparticle level, electrode level, etc.) may vary based on whether the active material particle(s) are in a Li-free state, a partially lithiated state, or a fully lithiated state. Such Li-dependent material properties may include particle pore volume, electrode pore volume, etc. Unless otherwise stated or implied, hereinafter, references to such Li-dependent material properties (e.g., at the particle level, interparticle level, electrode level, etc.) may be deemed to be provided as if the active material particles were in a Li-free state.
[0102] During battery (e.g., Li-ion) operation, the conversion material changes (transforms) from one crystal structure to another (hence the term "conversion" type, e.g., electrochemical reaction). This process involves breaking chemical bonds and forming new bonds. During (e.g., Li-ion) battery operation, Li ions are inserted into the alloy-type material and a lithium alloy is formed (hence the term "alloy" type). Sometimes "alloy" type electrode materials are considered a subclass of "conversion" type electrode materials.
[0103] In one or more embodiments of the present disclosure, a preferred negative electrode for a battery cell may include a mixture of Si-containing material (e.g., Si-C nanocomposite or other) (particles) and graphite (or soft or hard carbon) (particles) as the negative electrode active material, so-called blended negative electrode. In some designs, the Si-containing material (e.g., Si-C nanocomposite or other) (particles) contributes about 5% to about 98% of the total negative electrode capacity (in some designs, about 5 to about 20%; in other designs, about 20 to about 50%; in other designs, about 50 to about 80%; in still other designs, about 80 to about 98%), with the remainder of the negative electrode capacity being contributed by the graphite (or soft or hard carbon) (particles).
[0104] In addition to the negative electrode active material, the negative electrode may include inactive materials such as binder(s) (e.g., polymeric binder) and other functional additives (e.g., surfactants, conductive additives). In some embodiments, the negative electrode active material may be in the range of about 88% to about 98% by weight of the negative electrode (not including the weight of the negative electrode current collector); in other designs, it may be in the range of about 90% to about 98% by weight of the negative electrode (not including the weight of the negative electrode current collector). For example, the negative electrode active material may be about 95.5% by weight of the negative electrode. In some embodiments, the blended negative electrode may include Si-C nanocomposite (e.g., particles) in the range of about 7% to about 50% by weight of the negative electrode, with graphite (or soft or hard carbon) making up the remainder of the mass (weight) of the negative electrode active material. In some embodiments where the negative electrode active material is about 95.5% by weight of the blended negative electrode, the blended negative electrode (including active and inactive materials) may, for example, comprise about 7% by weight of Si-C nanocomposite and about 88.5% by weight of graphite. In some embodiments where the negative electrode active material is about 95.5% by weight of the blended negative electrode, the blended negative electrode (including active and inactive materials) may, for example, comprise about 19% by weight of Si-C nanocomposite and about 76.5% by weight of graphite. In some embodiments where the negative electrode active material is about 95.5% by weight of the blended negative electrode, the blended negative electrode (including active and inactive materials) may, for example, comprise about 35% by weight of Si-C nanocomposite and about 60.5% by weight of graphite. In some embodiments in which the negative electrode active material is about 95.5% by weight of the blended negative electrode, the blended negative electrode (including active and inactive materials) may include, for example, about 50% by weight Si-C nanocomposite and about 45.5% by weight graphite.
[0105] The following description may also describe certain examples of blended anode formulations expressed as mass (wt%) of Si-C nanocomposite, but it will be appreciated that various aspects of the present disclosure may be applicable to blended anode formulations expressed as wt% of Si (as element) in the anode. In some embodiments, a blended anode composition of about 7 wt% Si-C nanocomposite may correspond to about 3 wt% Si in the blended anode. In some embodiments, a blended anode composition of about 19 wt% Si-C nanocomposite may correspond to about 8 wt% Si in the blended anode. In some embodiments, a blended anode composition of about 35 wt% Si-C nanocomposite may correspond to about 15 wt% Si in the blended anode. In some embodiments, a blended anode composition of about 50 wt% Si-C nanocomposite may correspond to about 21 wt% Si in the blended anode. In such and other embodiments, the mass (weight) of silicon (element) ranges from about 1.5% to about 60% by weight of the total mass of the negative electrode; in other designs, a blended negative electrode can be obtained that ranges from about 3% to about 30% by weight of the total mass of the negative electrode. As used herein, the "total mass of the negative electrode" refers to the total mass of the negative electrode excluding the mass of the negative electrode current collector, even if the negative electrode is disposed on and / or within the negative electrode current collector.
[0106] Although the following description may also describe certain examples of blended anode formulations expressed as the mass (wt%) of Si-C nanocomposite, it will be appreciated that various aspects of the present disclosure may be applicable to blended anode formulations in which a fraction (e.g., %) of the blended anode's total capacity is attributed to the capacity of Si. In some embodiments, about 25% of the blended anode's total capacity is derived from the Si-C nanocomposite in a blended anode composition of about 7 wt% Si-C nanocomposite. In some other embodiments, about 50% of the blended anode's total capacity is derived from the Si-C nanocomposite in a blended anode composition of about 19 wt% Si-C nanocomposite. In some other embodiments, about 70% of the blended anode's total capacity is derived from the Si-C nanocomposite in a blended anode composition of about 35 wt% Si-C nanocomposite. In some other embodiments, about 80% of the blended anode's total capacity is derived from the Si-C nanocomposite in a blended anode composition of about 50 wt% Si-C nanocomposite. In such and some other embodiments, the Si-C nanocomposite or another Si-containing material, or various mixtures thereof, can contribute from about 5% to about 98% of the total negative electrode capacity (from about 5 to about 20% in some designs; from about 20 to about 50% in other designs; from about 50 to about 80% in other designs; from about 80 to about 98% in still other designs).
[0107] While the following description may set forth certain specific examples of suitable intercalation-type graphites for use in combination with Si-C nanocomposites in blends, various embodiments of the present disclosure may be applicable to soft-type synthetic graphite, hard-type synthetic graphite, and pitch-coated natural graphite; including, but not limited to, those exhibiting a discharge capacity of about 300 to about 380 (e.g., 300 to 340, or 340 to 350, or 350 to 362, or 362 to 372, or 372 to 380) mAh / g; including, but not limited to, those exhibiting low, moderate, and high swelling; including, but not limited to, those exhibiting good and poor compaction, including, but not limited to, those exhibiting a discharge capacity of about 1 to about 4 m. 2including, but not limited to, those exhibiting a Brunauer-Emmett-Teller (BET) surface area of about 1.5 g / cm; including, but not limited to, those exhibiting a lithiation efficiency of about 90% or greater; including, but not limited to, those exhibiting a particle size of about 8 μm to about 18 μm; 3 ~Approx. 2.3g / cm 3 (Approximately 1.5g / cm for other designs) 3 ~Approx. 1.8g / cm 3 ) true density in the range of 0.1 to 1.0 mm; including, but not limited to, those that exhibit poor, fair, or good cycle life; and including, but not limited to, those that are coated with a coating having a coating thickness to provide robust improvement in compression and rebound during cycling.
[0108] The following description is in the context of cathodes based on intercalation of lithium (Li) and changes in TM oxidation state of lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt manganese aluminum oxide (NCMA), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese cobalt oxide (NCM), lithium cobalt oxide (LCO), lithium cobalt aluminum oxide (LCAO), lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), LNP (lithium nickel phosphate), lithium cobalt phosphate (LCP), and other lithium transition metal (TM) oxides or phosphates or sulfates (or mixtures), including, but not limited to, those which may be doped or heavily doped; including, but not limited to, those which may have gradients in composition or core-shell morphology. % Mn, Fe, Ni, Co, Nb, Mg, Cr, Mo, Zr, W, Ta, Ti, Hf, Y, La, Sb, Sn, Si, or Ge), it will be appreciated that the various embodiments may be applicable to a variety of (including high voltage) lithium transition metal oxide (or phosphate or sulfate or oxyfluoride, or mixture or other) cathodes in which the TM and oxygen (O) are covalently bonded and both the TM and O participate in electrochemical reduction-oxidation (redox) reactions during charge and discharge (including, but not limited to, oxide or phosphate or sulfate or mixture cathodes that may contain at least about 0.25 atomic % Mn, Fe, Ni, Co, Nb, Mg, Cr, Mo, Zr, W, Ta, Ti, Hf, Y, La, Sb, Sn, Si, or Ge).
[0109] FIG. 1 shows an example of a metal-ion (e.g., Li-ion) battery to which the components, materials, methods, and other techniques described herein, or combinations thereof, may be applied according to various embodiments. A cylindrical battery is shown here for illustrative purposes, but other types of arrangements, including prismatic or pouch-type (laminated) batteries, may also be used as needed. The example battery 100 includes a negative electrode 102, a positive electrode 103, a separator 104 interposed between the negative electrode 102 and the positive electrode 103, an electrolyte (not explicitly shown) impregnating the separator 104, a battery case 105, and a sealing member 106 that seals the battery case 105. The electrolyte ionically connects the negative electrode (anode, negative electrode) and the positive electrode (cathode, positive electrode). In some embodiments, the battery 100 also includes a negative electrode current collector and a positive electrode current collector. The negative electrode is disposed on and / or in the negative electrode current collector, and the positive electrode is disposed on and / or in the positive electrode current collector.
[0110] The conventional salt used in the most common Li-ion battery electrolytes is LiPF6. Examples of less common salts (e.g., primarily explored in research publications, or in some cases, not even described in Li-ion battery electrolyte applications, but which may still be applicable and useful) include lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroantimonate (LiSbF6), lithium hexafluorosilicate (Li2SiF6), lithium hexafluoroaluminate (Li3AlF6), lithium bis(oxalato)borate (LiB(C2O4)2) (LiBOB), lithium difluoro(oxalato)borate (LiBF2(C2O4)) (LiDFOB), various lithium imides (e.g. SO2FN), ...silicate (Li2SiF6), lithium hexafluoroaluminate (Li3AlF6), lithium bis(oxalato)borate (LiB(C2O4)) (LiBOB), lithium difluoro(oxalato)borate (LiBF2(C2O4)) (LiDFOB), various lithium imides (e.g. SO2FN), lithium hexafluorosilicate (Li2SiF6), lithium hexafluorosilicate (Li2SiF6), lithium hexafluorosilicate (Li2SiF6), lithium hexafluorosilicate (Li2SiF6), - (Li + )SO2F, CF3SO2N - (Li + )SO2CF3, CF3CF2SO2N - (Li + )SO2CF3, CF3CF2SO2N - (Li + )SO2CF2CF3, CF3SO2N- (Li + )SO2CF2OCF3, CF3OCF2SO2N - (Li + )SO2CF2OCF3, C6F5SO2N - (Li + )SO2CF3, C6F5SO2N - (Li + )SO2C6F5 or CF3SO2N - (Li + )SO2PhCF3, and others), lithium difluorophosphate (LFO), and others.
[0111] Electrodes utilized in Li-ion batteries are typically produced by (i) forming a slurry containing the active materials, conductive additives, a binder solution, and in some cases surfactants or other functional additives, (ii) casting the slurry onto a metal current collector foil (e.g., Cu foil for most negative electrodes and Al foil for most positive electrodes), and (iii) drying the cast electrode to completely evaporate the solvent.
[0112] Conventional negative electrode materials utilized in Li-ion batteries are of the intercalation type, where metal ions are intercalated and occupy interstitial sites of such materials during charging or discharging of the battery. Such negative electrodes undergo small or very small volume changes when used in electrodes. Polyvinylidene fluoride, also known as polyvinylidene difluoride (PVDF), and carboxymethyl cellulose (CMC) are the two most common binders used in these electrodes. In some designs, other binders (e.g., acrylic binders, various polysaccharide binders, polytetrafluoroethylene (PTFE) and PTFE-based binders, etc.) may also be used. Carbon black is the most common conductive additive used in these electrodes. In some designs, other conductive additives (e.g., carbon fibers, single-walled carbon nanotubes, multi-walled carbon nanotubes, dendritic carbon, single-walled graphene or graphene oxide, multi-layered graphene or graphene oxide, metal nanowires, conductive carbides or carbonitriles, various mixtures and combinations thereof, etc.) may also be used. However, such anodes have relatively low gravimetric and volumetric capacities (typically less than about 370 mAh / g rechargeable specific capacity for graphite or hard carbon based anodes, and about 600 mAh / cm at the electrode level not considering the volume of the current collector foil). 3 Rechargeable volume capacity (less than 1000mAh).
[0113] The alloy-type (or more broadly, conversion-type) anode materials used in Li-ion batteries offer high gravimetric and volumetric capacities compared to intercalation-type anodes. For example, terrestrially abundant silicon (Si) offers roughly 10 times higher gravimetric capacity and roughly 3 times higher volumetric capacity compared to intercalation-type graphite (or graphitic) anodes. However, Si undergoes significant volume expansion (approximately up to 300% by volume) during Li insertion, which can therefore induce thickness changes and mechanical failure of Si-containing anodes. Furthermore, Si (and some Li-Si alloy compounds that can form during Si lithiation) exhibit relatively low electrical and ionic (Li-ion) conductivity. The electronic and ionic conductivity of Si is lower than that of graphite. The formation of (nano)composite-containing Si particles (including but not limited to Si-carbon composites, Si-metal composites, Si-polymer composites, Si-ceramic composites, nanostructured Si, composites containing various combinations of carbon, polymer, ceramic and metal, or other types of porous composites containing nanostructured Si, or nanostructured or nano-sized Si particles of various shapes and morphologies) can reduce the volume change during Li-ion insertion and extraction, leading to better cycle stability in rechargeable Li-ion cells. In some designs, Si may be doped or heavily doped with nitrogen (N), phosphorus (P), aluminum (Al), magnesium (Mg), boron (B) or other elements, or alloyed with metals (Al, Mg, Fe, Cu, Zn, Zr, etc.). In addition to Si-based composites, silicon oxide (SiO x ) or silicon oxynitride (SiO x N y ) or silicon nitride (SiN y) or silicon phosphide or other silicon-containing element particles (including those partially reduced by, for example, Li or Mg or Al) can lower the volume change and improve cycling stability, but at the expense of higher irreversible first cycle losses or faster degradation or both. In some designs, the Si-containing anode particles can exhibit high gravimetric capacity in the range of about 800 mAh / g to about 3000 mAh / g (per mass of the Si-containing anode particles without Li). Such high specific capacity is advantageous for obtaining a lighter battery. However, Li-ion battery cells having anodes containing high-capacity anode particles can undesirably exhibit fast degradation in conventional electrolytes, especially when charged at high temperatures (e.g., above battery operating temperatures, e.g., above about 50-80° C.) or at high voltages (e.g., above about 4-4.3 V). In some designs, the subset of anodes having Si-containing anode particles may include anodes having electrode layers exhibiting capacities ranging from about 400 mAh / g to about 2800 mAh / g (not counting the mass of the current collector per mass of the electrode layer in a Li-free state). Such types of charge-storing anodes may offer great potential for increasing the gravimetric and volumetric energy of rechargeable batteries. However, Li-ion battery cells having anodes with high-capacity anode particles may undesirably exhibit fast degradation in conventional electrolytes, especially when charged at high temperatures (e.g., above battery operating temperatures, e.g., above about 50-80° C.) or at high voltages (e.g., above about 4-4.3 V). In addition to Si-containing anodes, other examples of such high capacity (e.g., nanocomposite) anodes that contain alloy-type (or, more broadly, conversion-type) active materials include, but are not limited to, those that contain germanium, antimony, aluminum, magnesium, zinc, gallium, arsenic, phosphorus, silver, cadmium, indium, tin, bismuth, lead, alloys thereof, and others.In addition to negative electrodes that include active materials in metallic form, other types of high capacity (including nanocomposite) negative electrodes of interest may include metal oxides (including silicon oxide, lithium oxide, etc.), metal nitrides (including silicon nitride, etc.), metal oxynitrides (including silicon oxynitride, etc.), metal phosphides (including lithium phosphide), metal hydrides, and others.
[0114] Li-ion cells having alloy-type (or, more broadly, conversion-type) active negative electrode materials can exhibit undesirable fast degradation in conventional electrolytes, especially when charged to high temperatures (e.g., above battery operating temperatures, e.g., above about 50-80° C.) or high voltages (e.g., above about 4-4.3 V) and stored at such voltages at high temperatures (e.g., above about 50-80° C.). In some designs, degradation of Li-ion cells having alloy-type (or, more broadly, conversion-type) active negative electrode materials is particularly undesirable because it can be fast for large cells (e.g., cells having cell capacities in the range of about 10 Ah to about 40 Ah) or very large cells (e.g., cells having cell capacities in the range of about 40 Ah to about 400 Ah) or jumbo cells (e.g., cells having cell capacities in the range of about 400 Ah to about 4,000 Ah, or much larger). It should be noted that small cells (e.g., cells having capacities ranging from about 0.001 Ah to about 1 Ah) and medium cells (e.g., cells having capacities ranging from about 1 Ah to about 10 Ah) may also suffer from the same problems in some designs. However, large, or very large, or giant cells may be particularly attractive for use in some electrical transport or grid storage applications. In some designs, degradation of Li-ion cells having alloy-type (or, more broadly, conversion-type) active negative electrode materials, when normalized by total cell capacity, may be faster for cells containing medium (e.g., about 3-4 g / Ah) or low (e.g., about 2-3 g / Ah) amounts of electrolyte, which is particularly undesirable. However, in some designs, the use of medium or low amounts of electrolyte may be particularly attractive for reducing cell assembly costs or certain side reactions, and maximizing the energy density of the cell. One or more embodiments of the present disclosure allow for mitigating or overcoming some or all of such constraints, and for substantially enhancing the performance of such Li-ion cells through the use of certain disclosed electrolyte compositions.
[0115] High capacity (nano)composite anode powders (including, but not limited to, those containing Si) that exhibit moderately high volume change (e.g., about 8 to about 180 vol.%) during the first charge / discharge cycle, moderate volume change (e.g., about 4 to about 50 vol.%) during subsequent charge / discharge cycles, and average sizes in the range of about 0.2 to about 40 microns (more preferably, for some applications, about 0.4 to about 20 microns) may be particularly attractive for battery applications in terms of manufacturability and performance characteristics. In particular, average sizes in the range of about 0.5 microns 2 / g~about 50m 2 / g (approximately 0.5m in some designs) 2 / g ~ approx. 2m 2 / g; approx. 2m in other designs 2 / g ~ approx. 12m 2 / g; and about 12m in other designs. 2 / g~about 50m 2 A subclass of such anode powders having specific surface areas in the range of about 100 mAh / cm2 / g have performed particularly well in some embodiments. In some designs, 2 ) to altitude (e.g., about 4 to about 12 mAh / cm 2 ) and extremely high (e.g., about 12 mAh / cm 2 Electrodes with electrode area capacity loadings of up to 10 ...
[0116] However, despite some improvements that may be achieved through the formation and utilization of (e.g., nanocomposite) anode materials and electrode formulations that include such alloy-type (or conversion-type) active materials, substantial further improvements in cell performance characteristics may be achieved through improved compositions and preparations of electrolytes (e.g., liquid electrolytes) beyond those known or indicated by the prior art. Unfortunately, high capacity (nano)composite anode and cathode powders are relatively new, exhibiting moderately high volume changes (e.g., about 8 to about 180% by volume) during the first charge / discharge cycle, moderate volume changes (e.g., about 4 to about 50% by volume) during subsequent charge / discharge cycles, average sizes in the range of about 0.2 to about 40 microns, and relatively low densities (e.g., about 0.5 to 3.8 g / cc), and their performance characteristics and limited cycling stability are typically limited, particularly at moderate electrode area capacity loadings (e.g., about 2 to about 4 mAh / cm). 2 ), and also when the electrode area capacity loading is high (e.g., about 4 to about 12 mAh / cm 2 ) or extremely high. However, higher capacity loadings are advantageous in some designs to increase cell energy density and reduce cell fabrication costs. Similarly, cell performance may be worse when such electrode (e.g., negative electrode) porosity (e.g., the volume occupied by the space between the (nano)composite active negative electrode particles in the electrode and filled with electrolyte, excluding closed pores, if any, within the particles themselves that are inaccessible to electrolyte) is moderately small (e.g., about 25 to about 35% by volume), and more when the electrode (e.g., negative electrode) porosity is small (e.g., about 5 to about 25% by volume), or when the amount of binder and conductive additive in the electrode (e.g., negative electrode) is moderately small (e.g., about 6 to about 15% by weight in total), and more when the amount of binder and conductive additive in the electrode (e.g., negative electrode) is small (e.g., about 0.5 to about 5% by weight in total).
[0117] However, higher electrode density and lower binder content are advantageous for increasing cell energy density and reducing costs in certain applications. In some designs, lower binder content may also be advantageous for improving cell rate performance. In some designs, larger volume changes result in poorer performance in some designs, which may be related to damage to the solid electrolyte interphase (SEI) layer formed in the negative electrode, non-uniform lithiation and delithiation of electrode particles in the electrode, and / or other factors. Unfortunately, Li and Li-ion battery cells with such negative electrodes and conventional electrolytes avoid or are undesirable for their use at high or low temperatures, limiting their calendar life, or such cells cannot be charged to high voltages (e.g., above about 4.1-4.3 V), and often require the use of such large amounts of conventional SEI building additives to maintain acceptable cycle stability. In some designs, the performance of such battery cells may be particularly poor when the cells are charged above about 4.3-4.4 V, and even more so when the cells are charged above about 4.5 V.
[0118] However, higher cell voltages, wider operating temperature windows, and longer cycle life are advantageous for most applications. In some designs, such cells (e.g., cells containing large amounts of conventional SEI building additives) may suffer from excessive capacity degradation (e.g., greater than about 5%), large volume expansion (e.g., greater than about 10%), and significant gassing when exposed to high temperatures (e.g., greater than about 50-90°C) at a fully charged state (e.g., about 90-100% state of charge, SOC) for extended periods of time (e.g., about 12-168 hours). Passing such high temperature charging tests is often necessary for most applications. In some designs, degradation of Li-ion cells containing high capacity (nano)composite anode powders exhibits moderately high volume change during the first charge / discharge cycle, moderate volume change during subsequent charge / discharge cycles, and average size in the range of about 0.2 to about 40 microns, which is particularly undesirable since it can be fast for large cells (e.g., cells having a cell capacity in the range of about 10 Ah to about 40 Ah) or very large cells (e.g., cells having a cell capacity in the range of about 40 Ah to about 400 Ah) or giant cells (e.g., cells having a cell capacity in the range of about 400 Ah to about 4,000 Ah, or much larger). It should be noted that small cells (e.g., cells having a capacity in the range of about 0.001 Ah to about 1 Ah) and medium cells (e.g., cells having a capacity in the range of about 1 Ah to about 10 Ah) can also have the same problem in some designs. In some designs, Li-ion cells containing such volume-changing negative electrode particles are particularly undesirable because, when normalized by total cell capacity, they can become fast for cells containing moderate (e.g., about 3-4 g / Ah) or low (e.g., about 2-3 g / Ah) amounts of electrolyte. One or more embodiments of the present disclosure alleviate or overcome some or all of such limitations and enable the performance of such Li-ion cells to be substantially enhanced through the use of certain disclosed electrolyte compositions.
[0119] One or more embodiments of the present disclosure overcome some of the challenges discussed above for various types of metal ion (e.g., Li ion) cells that include nanocomposite anode materials (e.g., materials including conversion-type or alloy-type active materials) that may include Si in their composition, may experience some volume change during cycling (e.g., moderately high volume change (e.g., about 8 to about 160 or about 180 vol.%) during the first charge / discharge cycle and moderate volume change (e.g., about 4 to about 50 vol.%) during subsequent charge / discharge cycles), have an average particle size in the range of about 0.2 to about 40 microns, and a particle size of about 0.5 to about 50 microns. 2 / g (approximately 0.5 to 2 m in some designs) 2 / g; about 2 to about 12 m in other designs 2 / g; and in other designs, about 12 to about 50 m 2 / g), and may exhibit a medium specific surface area (e.g., from about 2 to about 4 mAh / cm 2 ) such electrodes and high areal capacity loadings (e.g., from about 4 to about 12 mAh / cm 2 ), with high packing density (electrode porosity filled with electrolyte in the range of about 5 to about 35 volume % after the first charge / discharge cycle), may be formulated with a relatively low binder content (e.g., about 0.5 to about 14 wt %), may contain a moderate or low amount of electrolyte per cell capacity (e.g., less than about 4 g / mAh), may be charged to a moderately high (e.g., greater than about 4.1 to 4.3 V), high (e.g., greater than about 4.3 to 4.4 V), or very high (e.g., greater than about 4.5 to 4.8 V) voltage, and may be charged to a high state of charge (e.g., greater than about 4.1 to 4.3 V) or high (e.g., greater than about 4.3 to 4.4 V) voltage during testing or operation. The cells may be exposed to temperatures in excess of about 40° C. at about 70-100% SOC) and may be produced as small cells (e.g., cells having a capacity in the range of about 0.001 Ah to about 1 Ah); as medium cells (e.g., cells having a capacity in the range of about 1 Ah to about 10 Ah); as large cells (e.g., cells having a capacity in the range of about 10 Ah to about 40 Ah) or as very large cells (e.g., cells having a capacity in the range of about 40 Ah to about 400 Ah) or jumbo cells (e.g., cells having a capacity in the range of about 400 Ah to about 4,000 Ah or much larger).
[0120] Conventional cathode materials utilized in Li-ion batteries are of the intercalation type and are generally crystalline and polycrystalline. Such cathodes typically have a maximum potential of about 4.3 V vs. Li / Li + a maximum charge potential of less than about 190 mAh / g, a gravimetric capacity (based on the mass of active material) of less than about 800 mAh / cm 3 For a given positive electrode, the higher energy density in Li-ion batteries is achieved by using a high voltage positive electrode (approximately 4.3 V vs. Li / Li + ~Approx. 5.1V vs.Li / Li +This can be achieved either by using a high-voltage intercalation type positive electrode (a positive electrode having a maximum charging potential of 10 ... Some high-voltage intercalation type positive electrodes may include phosphorus (P) as a dopant. Some high-voltage intercalation type positive electrodes may include sulfur (S) as a dopant. Some high-voltage intercalation type positive electrodes may include selenium (Se) as a dopant. Some high-voltage intercalation type positive electrodes may include tellurium (Te) as a dopant. Some high-voltage intercalation type positive electrodes may include iron (Fe). Some high-voltage intercalation type positive electrodes may include magnesium (Mg). Some high-voltage intercalation type positive electrodes may include zirconium (Zr). The combination of such (or similar) types of higher energy density positive electrodes with high capacity (e.g., Si-based) negative electrodes can lead to high cell-level energy densities. Unfortunately, the cycling stability and other performance characteristics of such cells may not be sufficient for some applications, at least when used in combination with conventional electrolytes.
[0121] Thereby, one or more embodiments of the present disclosure provide a high voltage intercalation positive electrode (about 4.0 to 4.2 V to about 4.5 V vs. Li / Li +, in some cases about 4.5V vs. Li / Li + ~Approx. 5.1V vs.Li / Li + The present invention is directed to electrolyte compositions that work well for combinations of a subclass of high capacity moderate volume change negative electrodes (e.g., negative electrodes that include (nano)composite negative electrode powders that exhibit a moderately high volume change (e.g., about 8 to about 160 or about 180 vol.%) during a first charge / discharge cycle and a moderate volume change (e.g., about 4 to about 50 vol.%) during subsequent charge / discharge cycles), with an average particle size (e.g., average diameter) in the range of about 0.2 to about 40 microns and an average particle size (e.g., average diameter) of about 0.5 to about 50 microns. 2 / g (when normalized by the mass of the composite electrode particles), and in the case of a Si-containing anode, a specific capacity in the range of about 400 to about 2800 mAh / g (when normalized by the total mass of all anode particles, not including the weight of conductive or other additives and binders, but the current collector) or in the range of about 650 to 800 to about 3000 mAh / g (when normalized by the mass of only the Si-containing anode particles). In at least one embodiment, a particular electrolyte composition may be selected based on the value of the maximum positive electrode charging potential, or the maximum operating temperature, or the longest calendar life requirement.
[0122] One or more embodiments of the present disclosure also provide: (i) moderate capacity (e.g., about 160-260 mAh / g mass of active material in some designs), with a cell capacity of about 4.1 V vs. Li / Li during full cell battery cycling; + (In some designs, it is about 4.2V vs. Li / Li + More than 4.3V vs. Li / Li in other designs + and about 4.4V vs. Li / Li in other designs. + and about 4.5V vs. Li / Li in other designs. + and about 4.6V vs. Li / Li in other designs. +A high voltage intercalation type cathode (which in some designs may be a layered cathode; in some designs may be Ni or Co or Mn, or some combination of such metals, such as LCO (lithium cobalt oxide), NCA (lithium nickel cobalt aluminum oxide), NCMA (lithium nickel cobalt manganese aluminum oxide), LNO (lithium nickel oxide), LMO (lithium manganese oxide), NCM (lithium nickel cobalt manganese oxide, also known as NMC), LCAO (lithium cobalt aluminum oxide), LCP (lithium cobalt phosphate), LNP (lithium phosphate), LN ... (ii) a subclass of high capacity moderate volume change anodes: anodes comprising about 5 to about 100 wt. % of a (nano)composite anode powder, which may include a moderately high volume change (e.g., about 8 to about 160 or about 180 vol. %) during a first charge-discharge cycle, a moderate volume change (e.g., about 4 to about 50 vol. %) during a subsequent charge-discharge cycle, an average size (e.g., average diameter) in the range of about 0.2 to about 40 microns, and a mass (e.g., average diameter) of about 0.5 to about 50 m normalized by the mass of the (nano)composite anode particles. 2 The present invention is directed to electrolyte compositions that work well in combination with anodes that exhibit specific surface areas in the range of about 400 to about 2800 mAh / g (when normalized by the combined mass of the active electrode particles, conductive additive, and binder) or about 800 to about 3000 mAh / g (when normalized by the mass of the composite anode particles alone) for Si-containing anodes.
[0123] The inventors have found that in some designs, cells including negative electrodes based on high capacity nanocomposite anode particles or powders (including conversion or alloy type active anode materials) that undergo volumetric change during cycling (moderately high volumetric change (e.g., about 8 to about 180 vol. % increase or about 8 to about 70 vol. % decrease) during the first charge / discharge cycle and moderate volumetric change (e.g., about 4 to about 50 vol. %) during subsequent charge / discharge cycles) and average sizes in the range of about 0.2 to about 40 microns (such as Si-based nanocomposite anode powders, among others) can benefit from certain compositions of electrolytes that provide significantly improved performance (especially for high capacity loadings or small electrolyte fractions, or large cells).
[0124] For example, the combination of (i) the continuous volume change of high-capacity nanocomposite particles during cycling and (ii) the decomposition of electrolyte at the conductive electrode surface at the electrode working potential (e.g., mainly electrochemical electrolyte reduction in the case of Si-based anodes) can result in the continuous (albeit relatively slow) growth of a solid electrolyte interphase (SEI) layer at the surface of the nanocomposite anode particles, resulting in irreversible loss of cell capacity. In some designs, the addition of some known SEI-forming additives can improve SEI stability during cycling, but can induce undesirable electrolyte oxidation at the cathode (especially at higher voltages or temperatures), resulting in gassing, cell swelling, and shortened cycle and calendar life. In some designs, the addition of some known cathode solid electrolyte interphase (CEI)-forming additives can induce protective film formation at the cathode, further reducing electrolyte oxidation and gassing, but often at the expense of reduced SEI stability or other undesirable effects at the anode.
[0125] The inventors have found that in some designs, the performance of cells containing Si-nanocomposites and graphite particle or powder-based negative electrodes can benefit from using electrolytes exhibiting a medium to low fluoroethylene carbonate (FEC) mole fraction and a low to lowest vinylene carbonate (VC) mole fraction, where "medium to low" (for FEC) is about 18 mol% to about 6 mol% and "low to lowest" (VC) is about 5 mol% to 0.1 mol%. FEC and VC are examples of tri-carbon cyclic carbonates, shown in FIG. 2 as structures 202 and 204, respectively. Ethylene carbonate (EC) is another tri-carbon cyclic carbonate, shown in FIG. 2 as structure 206. Although the blending electrolyte formulation may be entirely free of EC, the inventors have found that in some designs, it may be advantageous to use a "low to lowest" mole fraction of EC in the electrolyte (e.g., about 0.1 mol% to about 5.0 mol%).
[0126] For example, unlike electrolytes with high mole fractions of FEC and VC, where "high" is greater than about 18 mol% for FEC and greater than about 5 mol% for VC, electrolytes with medium to low FEC mole fractions and low to lowest VC mole fractions can improve SEI stability during cycling, improve cycle life, reduce high temperature (HT) outgassing at the positive electrode, improve ionic conductivity of the respective electrolytes, improve discharge voltage (V), reduce direct current (DC) resistance, lower voltage hysteresis, and reduce negative electrode charge transfer resistance.
[0127] The inventors have found that in some designs, it may be advantageous to maintain the necessary low mole fraction of VC (VC remaining in the electrolyte after formation) in the electrolyte to ensure that there is no electrolyte outgassing under HT storage conditions due to excessive decomposition of residual VC in the cell after formation at the positive electrode. In some designs, it may be advantageous to use an appropriate amount of branched ester co-solvent in the electrolyte (ELY) formulation to reduce HT outgassing that may be caused by VC. In some preferential designs, it may be advantageous to use a small fraction of branched ester to form a protective film on the positive electrode. In some other designs, it may be advantageous to use additives, such as 1,3,2-dioxathiolane 2,2-dioxide (DTD), methylene methane disulfonate (MMDS), dinitrile, trinitrile, difluorophosphate (LFO), sulfolane, or other compounds, to suppress HT outgassing caused by VC. Some nitrile additives, including dinitrile and trinitrile, are shown in Figures 11, 12, and 13 and are described in more detail below.
[0128] The inventors have also found that in some designs, it is advantageous to maintain the required low mole fractions of FEC and VC (FEC and VC remaining in the electrolyte after formation) in the electrolyte to ensure that there is no electrolyte outgassing at approximately 80% state of health (SOH), also known as end of life (EoL). In some designs, it may be advantageous to use a larger amount of branched ester co-solvent in the electrolyte formulation to suppress outgassing during cycling as the battery cell approaches its EoL. In some designs, it may be advantageous to use a high temperature storage additive (e.g., a nitrile additive) or a charge transfer additive (e.g., a Li salt additive) to suppress outgassing during cycling. In some designs, it is advantageous to keep to the minimum required % of FEC to reduce outgassing at EoL. The optimal FEC and VC mole fractions may depend on the particular cell design and electrolyte composition.
[0129] In some designs, it may be advantageous to use linear esters as the primary co-solvent. Herein, a compound used in a solvent composition may be referred to as a "primary co-solvent" (alternatively referred to as a "major solvent") when the mole fraction of that compound is greater than any of the other compounds in the solvent composition. The inventors have found that linear esters may be more advantageous than linear carbonates in reducing outgassing as the cell approaches its EoL. The poor stability of linear carbonates compared to esters may be due to the excess formation of carbon monoxide (CO), which may be the primary cause of outgassing at EoL.
[0130] In some designs, the swelling of the binder(s) in the electrolyte(s) may not only depend on the binder composition(s), but also on the electrolyte composition(s). Furthermore, in some designs, such swelling (and the resulting performance degradation) often correlates with a decrease in modulus when the binder is exposed to the electrolyte. In this sense, the smaller the decrease in modulus in a given electrolyte, the more stable the (nano)composite active particle / conductive additive interface that the binder connects. In some designs, a decrease in binder modulus of more than about 15-20% may result in significant performance degradation. As an example, a decrease in binder modulus of about two times (2x) may result in a significant performance degradation. In a further example, a decrease in modulus of about five times or more (e.g., about 5x-500x) may result in very significant performance degradation. Therefore, selecting an electrolyte composition that does not induce significant binder swelling may be highly preferential for certain applications. In some instances, it may be preferable to select an electrolyte composition such that the binder modulus decreases by less than about 30% (more preferably, less than about 10%) when exposed to the electrolyte. In negative electrodes that include multiple binder compositions, it may be preferable in some designs to select an electrolyte composition such that the modulus of at least one binder does not decrease by more than about 30% (more preferably, the modulus does not decrease by more than about 10%) when exposed to the electrolyte.
[0131] In some designs, it is advantageous to use a binder with functional groups that do not chemically or electrochemically interact with electrolyte components such as Li salts, FEC, VC, other co-solvents, and additives (e.g., Li salt additives, HT storage additives). We have found that in some designs, the presence of carboxylic acid groups in the binder can cause undesirable excessive gassing during HT storage testing. In some designs, it may be advantageous to use a higher amount of branched esters, DTD, MMDS, dinitriles, trinitriles, LFO, sulfolane, or other compounds in the ELY formulation to reduce HT gassing.
[0132] In one or more embodiments of the present disclosure, it may be advantageous to have a total salt mole fraction in the electrolyte ranging from about 6 mol % to about 20 mol % (about 8 mol % to about 20 mol % in other designs) while utilizing one salt or a mixture of two, three or more salts. In one or more embodiments of the present disclosure, it may be advantageous to have a total salt concentration in the electrolyte ranging from about 0.8 M to about 1.8 M while utilizing one salt or a mixture of two, three or more salts. A salt concentration in the electrolyte that is too low (e.g., less than about 0.8 M) may be inappropriate in some designs (e.g., when high capacity anode materials are used), particularly for high areal capacity electrodes (e.g., about 4 mAh / cm2). 2 If too much salt is used (more than 100%), it can result in excessive HT outgassing, reduced ELY conductivity, and increased charge transfer resistance. On the other hand, too high a salt mole fraction (concentration) in the electrolyte can result in reduced cycle life stability. In some designs, such excess salt-induced degradation of cycle life stability properties can be attributed to the Li + Decreased mobility of cations, which in some designs may be associated with the formation of an SEI that exhibits poor mechanical and / or chemical stability. In some designs, higher salt mole fractions (concentrations) may also lead to increased electrolyte density and reduced electrolyte conductivity and cost, which may be undesirable for some applications, such as low temperature applications. However, some applications, especially high electrode capacity loadings (> approx. 4 mAh / cm 2), an increase in salt molarity, for example about 1.3-1.7M (e.g., about 1.5M), may be advantageously used to lower the charge transfer resistance, which may be advantageous for low temperature applications. In some designs, higher salt mole fractions (concentrations) may also lead to faster charge and discharge rates (especially in cells with low or moderate electrode capacity loadings - for example, about 1-4 mAh / cm 2 ), which may be beneficial for some applications. Such improved rate performance may be associated with reduced anode and cathode charge transfer resistance despite lower electrolyte conductivity. Such improved rate performance may be beneficial for fast charging applications. Higher salt mole fractions (concentrations) may also lead to reduced HT gassing during HT storage tests. Such improved performance of HT storage tests may be associated with higher concentrations of lithium hexafluorophosphate and the formation of a LiF protective layer on the surface of the cathode, thereby shielding other chemicals from oxidative decomposition. The optimal salt concentration may depend on the particular cell design and electrolyte composition.
[0133] One aspect of the present disclosure is directed to an electrolyte for a lithium-ion battery. The electrolyte includes a primary lithium salt and a solvent composition. In some embodiments, the primary lithium salt may preferably be LiPF6. In some embodiments, the molar fraction of the primary lithium salt in the electrolyte may preferably range from about 6 mol% to about 20 mol%. In some embodiments, the concentration of the primary lithium salt in the electrolyte may preferably range from about 0.65M to about 2.1M. In some embodiments, the primary lithium salt is LiPF6 and the molar fraction (concentration) of the primary lithium salt in the electrolyte ranges from about 6 mol% to about 16 mol% or from about 0.65M to about 1.7M. In some designs, it may be advantageous to increase the molar concentration of LiPF6 to improve the operation of the electrolyte under high-rate charging conditions, for example, from 3C to 6C. In some designs, it may be advantageous to use an increased molar concentration of LiPF6 to improve the operation of the electrolyte at low temperatures, for example, from about -30°C to about +10°C. In some designs, it may be advantageous to increase the molar concentration of LiPF6 to reduce HT gas release. In some designs, a higher LiPF6 molar concentration may lead to poor cycle life at room temperature. The optimal LiPF6 molar concentration may depend on the particular cell design and electrolyte composition.
[0134] High temperature gassing in a battery cell is an undesirable phenomenon observed to result from heat treatment (also called high temperature storage treatment) of a battery cell after it is charged to a high state of charge (SOC). The temperature of the heat treatment can vary depending on the specific heat treatment embodiment, for example, about 80°C, about 72°C, about 60°C, and other temperatures ranging from about 50°C to about 90°C. The duration of the heat treatment can also vary depending on the specific heat treatment embodiment, for example, about 10 days, about 7 days, about 3 days, about 2.5 days, about 2 days, and other durations. In some Li-ion battery tests conducted by the inventors, the heat treatment was conducted at a temperature of 72°C for a duration of 60 hours (2.5 days).
[0135] The volume measurement of gas formed in the cell constitutes a metric as a high-temperature gas release test. In a specific example, the volume of gas in the cell at atmospheric pressure ("gas volume"), measured after the cell is cooled to 25°C for 1 hour after high-temperature storage treatment under high state of charge (SOC), is compared with the initial volume of the cell before high-temperature storage treatment under high state of charge (SOC). In some embodiments, the gas volume is preferably not more than 10% by volume of the initial volume of the cell. In some embodiments, the gas volume is preferably not more than 3% by volume of the initial volume of the cell. In some embodiments, the gas volume is preferably not more than about 1% by volume of the initial volume of the cell.
[0136] In some embodiments, the electrolyte may further include one or more charge transfer additives. Certain Li salt additives, as well as some other compounds, may function as charge transfer additives. In some embodiments, the one or more charge transfer additives are selected from lithium difluorophosphate (LiPO2F2 or LFO), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium fluorosulfate (LiSO3F), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(oxalato)borate (LiBOB). In some embodiments, the mole fraction of the charge transfer additive (e.g., lithium salt additive) may range from about 0.1 mole % to about 6 mole %. In some embodiments, the mole fraction of the charge transfer additive may range from about 0.5 mole % to about 1.5 mole %. In some embodiments, the concentration of the additive lithium salt(s) in the electrolyte may preferably range from about 0.05M to about 0.15M.
[0137] The inventors have found that in some designs, it may be advantageous to use an LFO additive to reduce HT gassing, improve discharge voltage (V), and improve charge and discharge rates. In some designs, the presence of LFO may reduce HT gassing by up to 100% compared to electrolyte formulations that do not contain LFO, which may be related to the formation of a cathode surface film that blocks oxidative decomposition of other electrolyte components. The inventors have found that the presence of LFO enhances the performance of electrolytes using LCO and / or NMC811 (approximate composition LiNi 0.8 Co 0.1 Mn 0.1 It has been found that LFOs can result in reduced formation of carbon dioxide and carbon monoxide in battery cells containing O2 NMCs. In some designs, the presence of LFOs can improve discharge V, which can be related to the formation of highly ionically conductive cathode CEI and anode SEI. In some designs, the presence of LFOs can reduce cycle life, which can be related to poor mechanical properties of the cathode CEI. In some other designs, LFOs can reduce charging performance due to chemical passivation of the binder surface.
[0138] The inventors have found that in some designs, it may be advantageous to use LiBF4 additives to reduce HT gas release, improve discharge voltage (V), and improve charge and discharge rates. In some designs, electrolyte formulations containing LiBF4 may be advantageously used to reduce HT gas release, which may be related to the formation of LiF on the positive electrode surface. The latter may originate from LiBF4 due to the low oxidation potential of LiBF4. However, it may also originate from LiPF6 due to the changes in the Li-ion solvation shell and the higher concentration of LiPF6 contact ion pairs in the presence of LiBF4. In some designs, LiBF4 may be advantageously used to increase the recoverable capacity after HT storage testing due to improved SEI stability. In some designs, it may be advantageous to use LiBF4 to improve charge and discharge rates, which may be related to the formation of highly ionically conductive positive CEI and negative SEI. In some designs, it may be advantageous to use LiBF4 to reduce DC resistance, which may be related to the formation of highly conductive positive CEI. In some designs, the use of LiBF4 may result in shortened cycle life due to the formation of a resistive anode SEI. However, in some designs, the more resistive anode SEI caused by LiBF4 may be advantageous for stability at high temperatures, including HT storage and HT cycling. In some designs, the use of LiBF4 reduces the amount of BF4 to Li-ions. - This may result in a decrease in ELY conductivity and an increase in ELY viscosity, which may be related to stronger coordination of LiBF. In some designs, LiBF may be advantageously used for cycling at high temperatures, e.g., above about 45° C., for improved SEI stability.
[0139] The inventors have found that in some designs, it may be advantageous to use LiDFOB additives to improve the discharge voltage (V) and improve the charge and discharge rates. In some designs, it may be advantageous to use LiDFOB to improve the discharge voltage (V) and improve the charge and discharge rates, which may be related to the formation of highly ionically conductive cathode CEI and anode SEI, respectively. In some other designs, electrolyte formulations containing LiDFOB may increase HT gas evolution at the cathode, which may be related to the conductive cathode CEI formed by LiDFOB. In some other designs, electrolyte formulations containing LiDFOB may increase DC resistance. In some designs, LiDFOB may be advantageously used to maintain a stable SEI during cycling and slow down resistance growth.
[0140] The inventors have found that it may be advantageous to use LiFSI additive in some designs to improve the discharge voltage (V) and improve the charge and discharge rate. In some designs, it may be advantageous to use LiFSI to improve the discharge voltage (V) and improve the charge and discharge rate, which may be related to the formation of high ion-conductivity cathode CEI and anode SEI, respectively. In some designs, LiFSI may be used as the main Li salt to replace LiPF6 in cells including NMC811 cathodes operating at about 4.2V. In some designs, LiFSI may be advantageously used to achieve high recoverable capacity after HT storage testing. In some designs, LiFSI may be advantageously used to improve HT cycle operation.
[0141] Therefore, in some embodiments, it may be advantageous to use LFO, LiBF4, LiFSI and LiDFOB as charge transfer additives in the electrolyte. In some cases, the total molar fraction of LFO, LiBF4, LiFSI and LiDFOB combined may be in the range of about 0.1 mol% to about 6 mol%, or in the range of 0.5 mol% to about 1.5 mol%. In some other designs, LiFSI may be used as the main Li salt to replace LiPF6, with a molar fraction of about 8 to about 20 mol%. In some other designs, LiFSI and LiPF6 may be used as a mixture in the electrolyte.
[0142] In one or more embodiments of the present disclosure, a lithium ion battery electrolyte includes a primary lithium salt and a solvent composition. The solvent composition may include (1) fluoroethylene carbonate (FEC), (2) at least one linear ester, and (3) at least one branched ester. The mole fraction of FEC in the electrolyte may range from about 2 mol % or 4 mol % to about 30 mol % (e.g., about 2-4 mol %, or about 4-8 mol %, or about 8-15 mol %, or about 15-30 mol %). The combined mole fraction of the at least one linear ester and the at least one branched ester in the electrolyte may be at least about 45 mol % (e.g., about 45-60 mol %, or about 60-75 mol %, or about 75-92 mol %, or about 60-80 mol %, or about 80-92 vol %) in some designs. The molar ratio of the at least one linear ester to the at least one branched ester may range from about 1:10 to about 20:1 (about 1:10 to about 1:2 in some designs; about 1:2 to about 1:1 in other designs; about 1:1 to about 2:1 in other designs; about 1.1:1 to about 1.4:1 in other designs; about 2:1 to about 5:1 in other designs; about 5:1 to about 10:1 in other designs; about 10:1 to about 20:1 in other designs). In other designs, the molar ratio of the at least one linear ester to the at least one branched ester may range from about 1:1 to about 10:1. The electrolyte may be substantially free of tetracarbonyl cyclic carbonate. As used herein, an electrolyte that is "substantially free" of a component (in this case, tetracarbonyl cyclic carbonate) may refer to an electrolyte that contains 0% by weight of the component or about 0% by weight of the component (e.g., trace amounts of the component may be present). As used herein, an electrolyte may be considered to be "substantially free" of a component when the mole fraction of that component in the electrolyte is about 0.01 mol% or less. Furthermore, in some embodiments, the electrolyte may also include at least one non-FEC cyclic carbonate. In some embodiments, the at least one non-FEC cyclic carbonate may be ethylene carbonate, vinylene carbonate, or a combination thereof.In some embodiments, the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte may be in the range of about 0.5 mol % to about 30 mol %, or in the range of about 1 mol % to about 6 mol %.
[0143] In one or more embodiments of the present disclosure, an electrolyte for a lithium ion battery includes a primary lithium salt and a solvent composition. The solvent composition may include (1) fluoroethylene carbonate (FEC), (2) at least one ester (e.g., at least one ester, at least one branched ester, or at least one linear ester and at least one branched ester), and (3) at least one non-FEC cyclic carbonate. The mole fraction of FEC in the electrolyte may range from about 2 mol % or 4 mol % to about 30 mol % (e.g., about 2-4 mol % or about 4-8 mol % or about 8-12 mol % or about 12-20 mol % or about 20-30 mol %). The total mole fraction of the at least one ester may be at least about 40 mol % in some designs. The total mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte may range from about 0.5 mol % to about 30 mol % in some designs. The electrolyte is substantially free of tetracarbon cyclic carbonate in some designs. Further, in some embodiments, the total mole fraction of all cyclic carbonates (FEC and non-FEC cyclic carbonates) does not exceed about 40 mole percent. In some embodiments, the total mole fraction of the at least one ester in the electrolyte may range from about 45 mole percent to about 70 mole percent. In some embodiments, the molar ratio of the at least one ester to the at least one non-FEC cyclic carbonate may range from about 1.5:1 to about 20:1.
[0144] In one or more embodiments of the present disclosure, the electrolyte for the lithium ion battery includes a primary lithium salt and a solvent composition. The solvent composition may include (1) fluoroethylene carbonate (FEC), (2) at least one ester (e.g., at least one ester, at least one branched ester, or at least one linear ester and at least one branched ester), and (3) at least one linear carbonate. The mole fraction of FEC in the electrolyte may range from about 2 mol % to about 30 mol % (e.g., about 2-4 mol %, or about 4-8 mol %, or about 8-15 mol %, or about 15-30 mol %). In some designs, the mole fraction of the at least one ester and one linear carbonate in the electrolyte may be at least about 45 mol %. In some designs, the molar ratio of the at least one ester to the at least one linear carbonate may range from about 1:1 to about 10:1. In some designs, the electrolyte may be substantially free of tetracarbon cyclic carbonates. Further, in some embodiments, the electrolyte may also include at least one non-FEC cyclic carbonate. In some embodiments, the at least one non-FEC cyclic carbonate may be ethylene carbonate, vinylene carbonate, or a combination thereof. In some embodiments, the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte may be in the range of about 0.5 mol% to about 30 mol%, or in the range of about 1 mol% to about 6 mol%.
[0145] In one or more embodiments of the present disclosure, a lithium ion battery may include a negative current collector, a positive current collector, a negative electrode disposed on and / or in the negative current collector, a positive electrode disposed on and / or in the positive current collector, and any one of the aforementioned electrolytes in ionically association with the negative and positive electrodes. For example, a separator may be interposed in the space between the negative and positive electrodes, and the separator may be impregnated with the electrolyte. In some embodiments, the negative electrode may comprise a mixture of (A) Si-containing particles (e.g., Si-C composite or nanocomposite particles containing both Si and C atoms (e.g., silicon portions are arranged as active material particles, carbon forms an inert, or substantially inert, or substantially less active, part of a scaffold matrix having pores, silicon active material (e.g., nanoparticles) are disposed around the composite particles, and / or a carbon coating or shell part is disposed around it)), in which the total weight of Si and C is in the range of about 75-100% of the total weight of the composite, and (B) graphitic carbon particles containing carbon (e.g., carbon-containing graphite as the active material) and substantially free of silicon. Such negative electrodes containing a mixture are sometimes referred to herein as blended negative electrodes. In some embodiments, the mass of silicon is in the range of about 1.5% to about 60% by weight of the total mass of the negative electrode (in other designs, in the range of about 3% to about 30% by weight of the total mass of the negative electrode).
[0146] In some embodiments, the negative electrode may include graphitic carbon particles that include carbon and are substantially free of silicon. The inventors have found that certain electrolytes may be particularly suitable for use with graphite negative electrodes in lithium ion batteries. Such suitable lithium ion battery electrolytes may include a primary lithium salt and a solvent composition. The solvent composition may include (1) fluoroethylene carbonate (FEC), (2) at least one ester (e.g., at least one ester, at least one branched ester, or at least one linear ester and at least one branched ester), and (3) at least one non-FEC cyclic carbonate. The mole fraction of FEC in the electrolyte may range from about 1 mol % or 4 mol % to about 30 mol % (e.g., about 1-2 mol % or about 2-4 mol % or about 4-8 mol % or about 8-15 mol % or about 15-30 mol %). The total mole fraction of the at least one ester may be at least about 40 mol % in some designs. The total mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte may range from about 0.5 mol % to about 30 mol %, or from about 1 mol % to about 6 mol % in some designs. The electrolyte may be substantially free of tetracarbon cyclic carbonates in some designs.
[0147] In one or more embodiments of the present disclosure, preferred lithium-ion battery electrolytes may include cyclic carbonates (CCs) that promote the formation of a negative electrode solid electrolyte interphase (SEI). Figure 2 shows three examples of such preferred SEI "builders": fluoroethylene carbonate (FEC) (202), vinylene carbonate (VC) (204), and ethylene carbonate (EC) (206). In some embodiments, FEC, VC, and EC may be preferably present in the electrolyte. FEC, VC, and EC are examples of tricarbon cyclic carbonates.
[0148] In some embodiments, the solvent composition of the electrolyte comprises FEC. In some embodiments, the molar fraction of FEC in the electrolyte may preferably range from about 1 mol% or 4 mol% to about 30 mol% (about 1 mol% to about 4 mol% in some embodiments; about 4 mol% to about 10 mol% in other embodiments; about 10 mol% to about 18 mol% in other embodiments; about 18 mol% to about 30 mol%). In some embodiments, the molar fraction of FEC in the electrolyte may range from about 1 mol% to about 30 mol%. In some preferred embodiments, the molar fraction of FEC is in the range of about 4 mol% to about 26 mol%. In some embodiments, the molar fraction of at least one ester in the electrolyte is in the range of about 45 mol% to about 70 mol% or about 80 mol%, while the molar fraction of FEC in the electrolyte may preferably range from about 4 mol% to about 26 mol%. In some designs, if the mole fraction of FEC in the electrolyte is too low (e.g., in some embodiments, less than about 1-8 mol% or 1-4 mol%, especially with a high fraction of Si in the anode), the cycle life may deteriorate rapidly due to an insufficient amount of suitable SEI builder, which is undesirable. In some designs, if the FEC mole fraction is more than about 8 mol%, the formation of SEI is more likely. If certain branched esters are present in the electrolyte, the formation of a more robust SEI may occur. However, in some designs, increasing the FEC mole fraction may be accompanied by an increase in hot gas emission and / or a decrease in discharge voltage (due to the formation of an excessively resistant SEI) and / or an increase in the viscosity of the electrolyte (due to the high viscosity of FEC), which is undesirable. A lower discharge voltage usually results in a lower volumetric energy density (VED), and a higher viscosity reduces ionic conductivity. For these reasons, the FEC mole fraction should preferably be set below a certain threshold (e.g., a mole % threshold) in some designs. In some embodiments, the FEC mole fraction should preferably not exceed about 30 mol%. In some embodiments, the FEC mole fraction preferably does not exceed about 20 mole percent.For FEC mole fractions in the preferred mole fraction ranges (e.g., in the range of about 1 mol % to about 30 mol %, or in the range of about 4 mol % to about 26 mol %, or in the range of about 8 mol % to about 18 mol %), high temperature outgassing may be effectively mitigated by the addition of certain high temperature storage additive(s) (e.g., nitrile additive(s)) or high temperature storage additive(s) in combination with branched ester(s) as discussed below. In some designs, the presence of FEC in the electrolyte, within the preferred mole fraction ranges, may contribute to a favorable balance of sufficiently good cycle life, good ionic conductivity, high discharge voltage, mitigation of high temperature outgassing, and / or good low temperature performance.
[0149] In some embodiments, the molar fraction of VC in the electrolyte may preferably be in the range of about 0.1 mol% or 0.5 mol% to about 5 mol% (e.g., about 0.1 to 2.5 mol% or about 0.5 to 2.5 mol% or about 2.5 to 5 mol%). In some embodiments, the molar fraction of VC in the electrolyte may preferably be in the range of about 1 mol% to about 3 mol%. In some designs, within the preferred molar fraction range (e.g., in the range of about 1 mol% to about 2 mol%), the presence of VC in the electrolyte may contribute to a favorable balance of good cycle life, good ionic conductivity, and high discharge voltage.
[0150] In some embodiments, if the mole fraction of VC in the electrolyte is too low (e.g., less than about 0.5 mol%; especially for negative electrodes with high Si fractions), the cycle life may deteriorate at a high rate due to insufficient formation of SEI or insufficient robustness of SEI. In some embodiments, the cycle life may be good in an electrolyte with a VC mole fraction of more than about 0.5 mol% or more than about 2.5 mol%. In some embodiments, a higher mole fraction of VC in the electrolyte results in a higher mole fraction of VC in the Li-ion solvation shell and a higher mole fraction of VC (or its decomposition products) in the SEI. Thus, if the VC mole fraction is more than about 1.0 mol%, more than about 1.5 mol%, more than about 2.0 mol%, more than about 2.5 mol%, more than about 3.0 mol%, more than about 3.5 mol%, or more than about 4.0 mol%, a more robust SEI may be formed during the initial 1 to 100 charge-discharge cycles. In some designs, due to its high dielectric constant (ε=126 at 25° C.), the presence of VC in the electrolyte may also enable the formation of an electrolyte with higher Li-ion conductivity. Thus, in some embodiments, ionic conductivity may be higher in electrolytes with VC mole fractions greater than about 0.5 mol%, greater than about 1.0 mol%, greater than about 1.5 mol%, greater than about 2.0 mol%, greater than about 2.5 mol%, or greater than about 3.0 mol%. Nevertheless, in some embodiments, there is a greater tendency to high-temperature outgassing in electrolytes with higher VC mole fractions. In some embodiments, when the VC mole fraction in the electrolyte is in the range of about 0.1 mol% or 0.5 mol% to about 5 mol% (e.g., in some designs, in the range of about 0.1 mol% or 0.5 mol% to about 1 mol%; in some other designs, in the range of about 1 mol% to about 2 mol%; in still other designs, in the range of about 2 mol% to about 3 mol%; and in still other designs, in the range of about 3 mol% to about 5 mol%), a good balance between cycle life, ionic conductivity, high discharge voltage, and mitigation of high temperature outgassing can be achieved.
[0151] In one or more embodiments of the present disclosure, a lithium-ion battery electrolyte includes a primary lithium salt and a solvent composition. In some designs, the solvent composition may include at least one tri-carbon cyclic carbonate, and ethyl trimethylacetate (ET) (a branched ester, shown as structure 612 in FIG. 6). In some designs, the at least one tri-carbon cyclic carbonate may include ethylene carbonate (EC). In some designs, the mole fraction of ET in the electrolyte may range from about 30 mol % to about 80 mol % (e.g., about 30-40 mol %; about 40-50 mol %; about 50-60 mol %; about 60-70 mol %; about 70-80 mol %). In some designs, the mole fraction of ET in the electrolyte may be at least about 50 mol %. In some designs, the electrolyte may be substantially free of tetra-carbon cyclic carbonates. In some embodiments, the total mole fraction of ET in the electrolyte may range from about 50 mol % to about 80 mol %. In some embodiments, the mole fraction of the at least one tri-carbocyclic carbonate in the electrolyte may range from about 5 mol% to about 40 mol% (e.g., about 5-10 mol%; about 10-20 mol%; about 20-30 mol%; about 30-40 mol%). In some embodiments, the mole fraction of the at least one tri-carbocyclic carbonate in the electrolyte may range from about 20 mol% to about 40 mol%. In some embodiments, the at least one tri-carbocyclic carbonate may include FEC and / or VC. In some embodiments, the electrolyte may be substantially free of linear carbonates. In some designs, the branched ester used in this example electrolyte is ET. Alternatively, in other designs, any one or more of the branched esters illustrated in Figures 6, 7, 8, 9 and 10 may be suitable for use in similar example electrolytes. These branched esters are discussed below.
[0152] In one or more embodiments of the present disclosure, a lithium-ion battery may include a negative current collector, a positive current collector, a negative electrode disposed on and / or in the negative current collector, a positive electrode disposed on and / or in the positive current collector, and any one of the aforementioned electrolytes ionically connecting the negative and positive electrodes. For example, a separator may be interposed in the space between the negative and positive electrodes, and the electrolyte may be impregnated into the separator.
[0153] In some embodiments, the negative electrode may include graphitic carbon particles that include carbon and are substantially free of silicon. The inventors have found that certain electrolytes may be particularly suitable for use with graphite (or hard or soft carbon) negative electrodes in lithium ion batteries. Such suitable lithium ion battery electrolytes may include a primary lithium salt and a solvent composition. In some designs, the solvent composition may include at least one tri-carbon cyclic carbonate and ethyl trimethylacetate (ET) (a branched ester shown as structure 612 in FIG. 6). In some designs, the at least one tri-carbon cyclic carbonate may include ethylene carbonate (EC). In some designs, the mole fraction of ET in the electrolyte may be at least about 50 mole %. The electrolyte may be substantially free of tetra-carbon cyclic carbonates in some designs.
[0154] In some embodiments, it may be advantageous to use ethylene carbonate (EC) as an SEI "builder" for blended anodes. In some embodiments, EC may be used as an SEI "builder" to build the SEI in graphite materials, helping to improve cycle life. Thus, the use of EC in the electrolyte may be beneficial in Li-ion battery cells in which the anode contains graphite, such as blended anodes (e.g., a mixture of silicon-carbon composite particles and graphitic carbon particles) and "pure" graphite anodes (e.g., the anode active material contains graphitic carbon particles, but does not contain silicon-carbon composite particles). The use of EC in the electrolyte may be particularly beneficial in anodes in which the anode active material contains a large fraction (e.g., about 90% to about 100% by weight) of graphitic carbon particles. In some embodiments, it may be advantageous to use about 1 mol% to about 32 mol%, or 20 mol% to about 40 mol%, or about 20 mol% to about 32 mol% of EC in the electrolyte. In some embodiments, when the mole fraction of EC in the electrolyte is from about 1 mol% to about 32 mol%, or from about 20 mol% to about 40 mol%, or from about 20 mol% to about 32 mol%, a good balance between cycle life, ionic conductivity, cell resistance, discharge voltage, high temperature cycling, and low temperature performance can be achieved.
[0155] Propylene carbonate (PC) is known as a co-solvent in electrolyte formulations for Li-ion battery cells. In some embodiments of the Li-ion batteries contemplated herein, such as blended anodes (e.g., a mixture of silicon-carbon composite particles and graphitic carbon particles) and "pure" graphite anodes (e.g., the anode active material includes graphitic carbon particles but does not include silicon-carbon composite particles), the inventors have found that PC can reduce the ionic conductivity of the electrolyte and can be a poor SEI "builder". Thus, in some embodiments, electrolytes that include PC can exhibit one or more of the following characteristics: increased high temperature gas release, reduced discharge voltage, and poor cycle life compared to some other electrolytes that do not include PC. In some embodiments, it may be preferable to avoid (e.g., partially or in total) the use of PC in the electrolyte. PC is an example of a tetracarbon cyclic carbonate. In some embodiments, it may be preferable to avoid the use of tetracarbon cyclic carbonates in the electrolyte. In some embodiments, the electrolyte for the lithium ion battery may be substantially free of tetracarbon cyclic carbonates. In some embodiments, the lithium ion battery electrolyte may be substantially free of propylene carbonate.
[0156] The mechanism of decomposition of cyclic carbonates (CC) at high temperatures may be different at the positive and negative electrodes. For example, oxidation of CC with the formation of CO and CO2 at the positive electrode may be the result of various electrolyte-cathode chemical or electrochemical interactions and may result in gas evolution. Several mechanisms of decomposition of CC at the positive electrode may occur. For example, oxygen, which may occur at the positive electrode at high state of charge (SOC), may oxidize CC, leading to the formation of a CO / CO2 mixture. Also, hydrogen (H) abstraction from CC may result in the disproportionation of the five-membered ring of CC with the formation of CO and CO2 as a result of oxidation. Also, electron abstraction from VC may accelerate the formation of gas products. Also, the change in the size of ion pairing of Li salts, which can be adjusted by changing the CC concentration, may result in an increase in gas evolution at high temperatures. For example, Li + and PF6- The increase in ion pairing of LiPF6 can result in a decrease in high temperature (HT) gas evolution due to the decomposition of LiPF6 and the formation of a LiF protective layer.
[0157] The mechanism of gassing at the negative electrode may be very different from that at the positive electrode. At high SOC, electrons originating from the negative electrode may act as nucleophiles attacking the positively charged carbonyls of CC. The resulting decomposition product may be CO2. In addition to CO2, the formation of H2, CO, CH4, C2H4, C2H6, C3H6 and / or C3H8 may also occur as a result of chemical or electrochemical interactions of the electrolyte with the negative electrode surface, inducing significant high temperature (HT) gassing.
[0158] In one or more embodiments of the present disclosure, preferred lithium-ion battery electrolytes may include at least one linear ester (ES) as a primary (e.g., about 20 to about 70 mole % of the electrolyte) co-solvent. Figures 4 and 5 show examples of some suitable linear esters: methyl acetate (sometimes abbreviated herein as MA, structure 402), methyl propionate (MP, 404), methyl butyrate (MB, 406), ethyl acetate (EA, 408), ethyl propionate (EP, 410), ethyl butyrate (EB, 412), propyl acetate (PA, 502), propyl propionate (PP, 504), propyl butyrate (PB, 506), butyl acetate (BA, 508), butyl propionate (BP, 510), and butyl butyrate (BB, 512).
[0159] In one or more embodiments of the present disclosure, preferred lithium ion battery electrolytes may include at least one branched ester (ES) as one of the primary (e.g., about 20 to about 70 mol%) co-solvents or major co-solvents. In some designs, two or more branched esters may be advantageously used. Figures 6, 7, 8, 9, and 10 show examples of some suitable branched esters: methyl isobutyrate (MI, 602), methyl trimethylacetate (MT, 604), methyl isovalerate (MIV, 606), methyl 2-methylbutyrate (MMB, 608), ethyl isobutyrate (EI, 610), ethyl trimethylacetate (ET, 612), ethyl isovalerate (EIV, 614), ethyl 2-methylbutyrate (EMB, 616), propyl isobutyrate (PI, 702). , Propyl trimethylacetate (PT, 704), Propyl isovalerate (PIV, 706), Propyl 2-methylbutyrate (PMB, 708), Butyl isobutyrate (BI, 710), Butyl trimethylacetate (BT, 712), Butyl isovalerate (BIV, 714), Butyl 2-methylbutyrate (BMB, 716), Isopropyl acetate (IPA, 802), Isopropyl propionate (IPP, 804), Isopropyl butyrate (IPB, 806), Isopropyl isobutyrate isopropyl (IPI, 808), isopropyl trimethylacetate (IPT, 810), isopropyl isovalerate (IPIV, 812), isopropyl 2-methylbutyrate (IPMB, 814), tert-butyl acetate (TBA, 902), tert-butyl propionate (TBP, 904), tert-butyl butyrate (TBB, 906), tert-butyl isobutyrate (TBI, 908), tert-butyl trimethylacetate (TBT, 910), isopropyl tert-Butyl valerate (TBIV, 912), tert-butyl 2-methylbutyrate (TBMB, 914), isobutyl acetate (IBA, 1002), isobutyl propionate (IBP, 1004), isobutyl butyrate (IBB, 1006), isobutyl isobutyrate (IBI, 1008), isobutyl trimethylacetate (IBT, 1010), isobutyl isovalerate (IBIV, 1012), and isobutyl 2-methylbutyrate (IBMB, 1014).
[0160] In some designs, the appropriate mixture of ester compounds may contribute to better ionic conductivity in the electrolyte, better discharge performance (also referred to as "C-rate performance"), better high-rate charge performance, reduced HT gassing, reduced end-of-life gassing, better calendar life, and / or better low-temperature performance. In one or more embodiments of the present disclosure, a preferred lithium-ion battery electrolyte may include a mixture of at least one linear ester and at least one branched ester. In some embodiments, the total mole fraction of the mixture (at least one linear ester and at least one branched ester) may be at least about 45 mol%. In some embodiments, the total mole fraction of the mixture (at least one linear ester and at least one branched ester) may range from about 60 mol% to about 75 mol%. In some embodiments, the molar ratio of the at least one linear ester to the at least one branched ester may range from about 1:10 to about 20:1 (in some designs, from about 1:10 to about 1:5; in other designs, from about 1:5 to about 1:2; in other designs, from about 1:2 to about 1:1; in other designs, from about 1:1 to about 2:1; in other designs, from about 2:1 to about 5:1; in other designs, from about 5:1 to about 10:1; in still other designs, from about 10:1 to about 20:1; in still other designs, from about 1:1 to about 10:1). In some embodiments, the molar ratio of the at least one linear ester to the at least one branched ester may range from about 1:1 to about 2:1. In some embodiments, the molar ratio of the at least one linear ester to the at least one branched ester may range from about 1.1:1 to about 1.4:1.
[0161] In some designs, the appropriate ester(s) may contribute to improved ionic conductivity in the electrolyte, improved discharge performance (also referred to as "C-rate performance"), and / or improved lower temperature performance. In some designs, the presence of branched esters in electrolytes containing FEC, VC, and / or EC may lead to the formation of a more robust SEI. Thus, in some designs, electrolytes containing branched esters may exhibit better (and in some designs improved) cycle life. In one or more embodiments of the present disclosure, the mole fraction of the ester(s) (linear esters, branched esters, or a mixture of linear and branched esters) in the electrolyte may preferably range from about 20 mol% to about 70 mol%, or about 80 mol%. In other embodiments, the mole fraction of the ester in the electrolyte may preferably range from about 45 mol% to about 70 mol%, or about 80 mol%. In other embodiments, the mole fraction of the ester in the electrolyte may preferably range from about 30 mol% to about 50 mol%. In other embodiments, the mole fraction of the ester in the electrolyte may preferably range from about 50 mol% to about 70 mol%, or about 80 mol%. In other embodiments, the mole fraction of the ester in the electrolyte may preferably be at least about 30 mol%. In other embodiments, the mole fraction of the ester in the electrolyte may preferably be at least about 40 mol%. In other embodiments, the mole fraction of the ester in the electrolyte may preferably be at least about 50 mol%. In other embodiments, the mole fraction of the ester in the electrolyte may preferably be at least about 60 mol%.
[0162] In some embodiments, the linear ester EP (410) may contribute to lower viscosity, higher discharge voltage, lower cell resistance, better C-rate performance, and / or better low temperature performance. However, in some designs, the presence of EP in the electrolyte is undesirable because it may also lead to high temperature outgassing, end-of-life outgassing, shorter cycle life, and / or generation of gas by-products such as hydrogen at the anode. Thus, in some designs, the mole fraction of EP in the electrolyte may preferably be in the range of about 20 mol% to about 70 mol% or about 80 mol% (about 30 mol% to about 60 vol% in some designs). In some designs, within this preferred mole fraction range, the presence of EP in the electrolyte may contribute to a favorable balance of good cycle life, high discharge voltage, and / or mitigation of high temperature outgassing, and / or end-of-life outgassing in the appropriate electrolyte (which in some designs may also include an SEI "builder", or a combination of an SEI "builder" and a branched ester).
[0163] In some embodiments, the linear ester EA (408) may contribute to lower viscosity, higher discharge voltage, lower cell resistance, better C-rate performance, and / or better low temperature performance. However, in some designs, the presence of EA in the electrolyte is undesirable because it may also lead to high temperature outgassing, end-of-life outgassing, shorter cycle life, and / or generation of gas by-products such as methane at the anode. Thus, in some designs, the mole fraction of EP in the electrolyte may preferably range from about 20 mol% to about 80 mol% (about 30 mol% to about 60 vol% in some designs). In some designs, within this preferred mole fraction range, the presence of EA in the electrolyte may contribute to a favorable balance of good cycle life, high discharge voltage, and / or mitigation of high temperature outgassing, and / or end-of-life outgassing in the appropriate electrolyte (which in some designs may also include an SEI "builder", or a combination of an SEI "builder" and a branched ester). In some designs, a mixture of EA and EP may contribute to a favorable balance of good cycle life, high discharge voltage, low cell resistance, and high electrolyte conductivity. In some embodiments, a mixture of EA (linear ester) and EP (linear ester) may be used in a suitable electrolyte (e.g., an electrolyte using a tricarbon cyclic carbonate such as FEC), where the molar ratio of EA (linear ester) to EP (linear ester) may range from about 1:10 to about 20:1 (in some designs, from about 1:10 to about 1:5; in other designs, from about 1:5 to about 1:2; in other designs, from about 1:2 to about 1:1; in other designs, from about 1:1 to about 2:1; in other designs, from about 2:1 to about 5:1; in other designs, from about 5:1 to about 10:1; in still other designs, from about 10:1 to about 20:1). In some embodiments, the molar ratio of EA (linear ester) to EP (linear ester) may range from about 1:1.1 to about 1:1.4.
[0164] In some embodiments, the branched ester ethyl isobutyrate (EI) (610) may contribute to better cycle life, reduced high temperature outgassing, and / or reduced end-of-life outgassing compared to linear (unbranched) ethyl propionate (EP) (410). Furthermore, the flash point of EI, approximately 20° C., is higher than that of EP, approximately 12° C. However, in some designs, the presence of EI (or other branched esters) in the electrolyte may lead to a slight decrease in discharge voltage and a decrease in C-rate performance (e.g., due to an increase in charge transfer resistance). In some designs, this decrease in C-rate performance may be mitigated by the addition of certain charge transfer additive salt(s) (e.g., lithium difluorophosphate (LiPO2F2) (abbreviated LFO), or lithium tetrafluoroborate (LiBF4), among various combinations). Thus, the mole fraction of EI in the electrolyte may preferably range from approximately 25 mol% to approximately 80 mol% in some designs. In some designs, within this preferred mole fraction range, the presence of EI in the electrolyte may contribute to good cycle life, high discharge voltage, and / or mitigation of high temperature outgassing, and / or a suitable balance of end-of-life outgassing with the appropriate electrolyte, which in some designs may preferably include a cyclic carbonate. In some embodiments, a mixture of EP (linear ester) and EI (branched ester) may be used in a suitable electrolyte (e.g., an electrolyte using a tricarbon cyclic carbonate such as FEC), where the molar ratio of EP (linear ester) to EI (branched ester) may range from about 10:1 to about 20:1 (in some designs, from about 1:10 to about 1:5; in other designs, from about 1:5 to about 1:2; in other designs, from about 1:2 to about 1:1; in other designs, from about 1:1 to about 2:1; in other designs, from about 2:1 to about 5:1; in other designs, from about 5:1 to about 10:1; in still other designs, from about 10:1 to about 20:1; in still other designs, from about 1:1 to about 10:1). In some embodiments, the molar ratio of EP (linear ester) to EI (or another branched ester) may range from about 1.1:1 to about 1.4:1.
[0165] Ethyl isovalerate (EIV) (614) is another example of a branched ester that may be used to improve some of the performance characteristics of Li-ion batteries. Thus, in some embodiments, a mixture of EP (linear ester) and EIV (branched ester) may be used in a suitable electrolyte (e.g., an electrolyte using a tricarbon cyclic carbonate such as FEC) in which the molar ratio of EP (linear ester) to EIV (branched ester) may range from about 1:1 to about 10:1. In some embodiments, the molar ratio of EP (linear ester) to EIV (branched ester) may range from about 1.1:1 to about 1.4:1. Further, in some embodiments, a mixture of EP (linear ester), EI (branched ester), and EIV (branched ester) may be used in a suitable electrolyte (e.g., an electrolyte using a tricarbon cyclic carbonate such as FEC), where the molar ratio of EP (linear ester) to the sum of EI and EIV (branched ester) may range from about 1:10 to about 20:1 (in some designs, from about 1:10 to about 1:5; in other designs, from about 1:5 to about 1:2; in other designs, from about 1:2 to about 1:1; in other designs, from about 1:1 to about 2:1; in other designs, from about 2:1 to about 5:1; in other designs, from about 5:1 to about 10:1; in still other designs, from about 10:1 to about 20:1; in still other designs, from about 1:1 to about 10:1). In some embodiments, the molar ratio of EP (linear ester) to the sum of EI and EIV (branched ester) may range from about 1.1:1 to about 1.4:1.
[0166] In some embodiments, it may be beneficial to use the branched ester, ethyl trimethylacetate (ET) (612), as an SEI builder for anodes using blended anodes containing graphitic carbon particles and Si-C composite particles. In some designs, the presence of ET in the electrolyte may increase the cycle life of the blended anodes containing graphitic particles. In some designs, the ET-containing electrolyte may be applied to either graphite anodes or blended anodes where graphite is mixed with Si-C composite particles. In some designs, the presence of ET in the electrolyte may contribute to a reduction in HT gas emission at anodes that may be graphite anodes or blended anodes of graphite (e.g., graphitic carbon particles) and Si-C composite particles. In some designs, the presence of ET in the electrolyte may contribute to a reduction in HT gas emission at the cathode. The inventors have found that ET may contribute to the formation of a robust anode SEI for both graphitic carbon particles and Si-C composite particles. The inventors have also found that ET may contribute to the formation of a robust CEI at the cathode particles. In some designs, the use of ET in the electrolyte can be beneficial for high voltage cathode materials (e.g., LCO, NMC811). In some designs, the use of ET in the electrolyte can be beneficial for cathodes characterized by polycrystalline microstructures, thereby enabling the formation of robust CEI. In some embodiments, ET can be used in electrolytes containing ethylene carbonate (EC). In some other designs, it can be more advantageous to use ET to improve low temperature performance in electrolytes containing FEC. In some designs, it can be advantageous to use ET as a primary co-solvent with a mole fraction of ET in the electrolyte that is at least about 50 mole %. In some other designs, it can be advantageous to use ET as a secondary co-solvent with a mole fraction of ET in the electrolyte ranging from about 5 mole % to about 50 mole %.
[0167] In one or more embodiments of the present disclosure, a preferred electrolyte for a Li-ion battery may include at least one linear carbonate (LC). Figure 3 shows two examples of linear carbonates: dimethyl carbonate (DMC) (302) and ethyl methyl carbonate (EMC) (304). The molecular weights of these compounds are about 90.08 g / mol (DMC) and about 104.10 g / mol (EMC), respectively. Another example of a linear carbonate is diethyl carbonate (DEC), which has a molecular weight of about 118.13 g / mol. These linear carbonates are noted for their relatively low viscosity (approximately 0.59 cP for DMC and approximately 0.65 cP for EMC at 25°C). Thus, in some designs, the viscosity of the electrolyte may be reduced by the addition of one or more of these linear carbonates. For example, in some electrolyte formulations, EMC may increase the discharge voltage and improve low temperature performance. In some designs, the linear carbonate may be used at a relatively low mole fraction in the electrolyte, for example, in the range of from about 0 mol% to about 6 mol% (e.g., from about 0 mol% to about 1 mol%, from about 1 mol% to about 3 mol%, or from about 3 mol% to about 6 mol%). In other designs, the LC may be omitted entirely, or the electrolyte may be substantially free of linear carbonate. In some embodiments, the electrolyte may be substantially free of diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate. In other designs, the linear carbonate may be used in the electrolyte in the range of from about 1 mol% to about 17 mol% (e.g., from about 6 mol% to about 17 mol%; from about 1 mol% to about 20 mol% in other designs), or in the range of from about 17 mol% to about 30 mol%.
[0168] In some designs, it may be beneficial to avoid the use of linear carbonates in electrolytes containing FEC. For example, this may apply to electrolytes that include (1) a solvent composition that includes fluoroethylene carbonate (FEC), at least one linear ester and at least one branched ester, or (2) a solvent composition that includes fluoroethylene carbonate (FEC), at least one ester, and at least one non-FEC cyclic carbonate. Thus, in some embodiments, the electrolyte may be substantially free of diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate. In some embodiments, the electrolyte may be substantially free of linear carbonates. In some designs, the combination of FEC with linear carbonates may reduce cycle life due to the structure of the Li-ion solvation shell (e.g., FEC is displaced from the solvation shell in the presence of linear carbonates) and due to chemical decomposition of FEC by linear carbonates, or products of electrochemical decomposition of linear carbonates (e.g., ethoxide). In some embodiments, the FEC mole fraction is preferably not more than about 20 mole%. In some embodiments, the FEC mole fraction may preferably range from about 4 mol % to about 20 mol %. In some embodiments (e.g., in anodes having low Si weight %), the FEC mole fraction may be lower than about 4 mol % (e.g., from about 1 mol % to about 4 mol %).
[0169] We have investigated the use of ethylene carbonate (EC) (206), a tricarbon cyclic carbonate, in certain electrolytes to improve the performance of graphite and graphite particulate / Si-C composite particle blended anodes. We have found that EC can be effective as a primary SEI “builder.” We have found that in some designs, using EC as the primary SEI builder for electrolytes in lithium-ion batteries (including graphite anodes or blended anodes containing graphite particles and Si-C composite particles) is more advantageous when the electrolyte contains certain linear carbonates as the primary cosolvent. However, it can be advantageous to avoid the use of FEC (or reduce its mole fraction) in electrolytes containing EC. In some designs, the presence of FEC and EC in the electrolyte can be detrimental to the cycle life of anodes with “pure” graphite anodes or blended anodes of graphite and Si-C composite particles. These phenomena may be related to the structure of the Li-ion solvation shell, where FEC is displaced from the Li-ion solvation shell in the presence of EC.
[0170] In one or more embodiments of the present disclosure, an electrolyte for a lithium ion battery includes a primary lithium salt and a solvent composition. The solvent composition may include fluoroethylene carbonate (FEC) and at least one linear carbonate. The mole fraction of FEC in the electrolyte may range from about 2-4 mol% to about 20 mol%. In some designs, the total mole fraction of the at least one linear carbonate in the electrolyte is at least about 40 mol%. In some designs, the electrolyte may be substantially free of tetracarbon cyclic carbonates. In some embodiments, it may be preferred to select ethyl methyl carbonate and / or dimethyl carbonate as the at least one linear carbonate, and to avoid the use of diethyl carbonate (molecular weight of about 118). In some embodiments, it may be preferred to select dimethyl carbonate as the at least one linear carbonate. The electrolyte may be substantially free of any linear carbonate with a molecular weight greater than 117. In some embodiments, the total mole fraction of the linear carbonate(s) in the electrolyte may range from about 60 mol% to about 75 mol%. In some embodiments, the electrolyte may further include at least one non-FEC cyclic carbonate, which may be selected from ethylene carbonate and vinylene carbonate. In some embodiments, the electrolyte further includes a non-FEC cyclic carbonate, and the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte is in the range of about 1 mol% to about 30 mol%, or in the range of about 15 mol% to about 30 mol%.
[0171] In one or more embodiments of the present disclosure, the lithium ion battery may include an anode current collector, a cathode current collector, an anode disposed on and / or in the anode current collector, a cathode disposed on and / or in the cathode current collector, and any one of the aforementioned electrolytes ionically linking the anode and the cathode. For example, a separator may be interposed in the space between the anode and the cathode, and the separator may be impregnated with the electrolyte. In some embodiments, the anode may include a mixture of (A) Si-containing particles (e.g., silicon-carbon nanocomposite particles containing a total of about 75-100 wt% silicon and carbon) and (B) graphitic carbon particles containing carbon and substantially no silicon. Such anodes containing a mixture are sometimes referred to herein as blended anodes. In some embodiments, the mass of silicon ranges from about 1 wt% to about 60 wt% (about 3 wt% to about 30 wt% in other designs) of the total mass of the anode.
[0172] The inventors have found that in some embodiments where the negative electrode comprises a graphite negative electrode or a graphite and Si-C composite particle blend negative electrode, it may be advantageous to use an electrolyte containing FEC but not EC. In some designs, it may be beneficial to use an ester as the main co-solvent in combination with FEC. In some designs, an electrolyte containing an ester and FEC is beneficial for improving the cycle life of graphite negative electrodes and graphite and Si-C composite particle blend negative electrodes. In some designs, the presence of EC in such electrolytes may lead to a shortened cycle life. This phenomenon may be due to the poor SEI construction of EC compared to FEC. In some designs, the fraction of one or more esters in such electrolytes may be greater than about 50 mol%. In some other designs, a combination of linear and branched esters may be beneficial to increase the discharge voltage, improve cycle life, and reduce charge transfer resistance.
[0173] In some designs, the surfaces of the positive and negative electrodes may preferably be protected by one or more high temperature storage additives (e.g., nitrile additives, as well as other compounds) that reduce high temperature (HT) outgassing and mitigate transition metal dissolution. As used herein, the term "nitrile" refers to an organic molecule characterized by one or more CN (nitrile) groups. In some preferred examples, the nitrile may be a dinitrile. In other preferred examples, the nitrile may be a trinitrile. In other preferred examples, the nitrile may be a tetrakisnitrile. In other preferred examples, the nitrile may be a mononitrile.
[0174] Chemical structures of some compounds that may be used as high temperature storage additives are shown in Figures 11, 12, 13, 14, and 15. Some examples of nitrile compounds that may be used as high temperature storage additives are shown in Figures 11, 12, and 13. Some examples of nitrile compounds that may be used as high temperature storage additives are: adiponitrile (sometimes abbreviated as ADN) (dinitrile, structure 1102), 3-(2-cyanoethoxy)propanenitrile (dinitrile, 1104), 1,5-dicyanopentane (dinitrile, 1106), 1-(cyanomethyl)cyclopropane-1-carbonitrile (dinitrile, 1108), 4,4-dimethylheptanedinitrile (dinitrile, 1110), trans-1,4-dicyano-2-butene (dinitrile, 1112), 1,3,6-hexanetricarbonitrile (HTCN) (trinitrile, 1114), 3-{[1,3-bis(2-cyanoethoxy)propanenitrile](dinitrile, 1115), 1,3-bis(2-cyanoethoxy)propanenitrile (dinitrile, 1116), 1,3-bis(2-cyanoethoxy)propanenitrile (dinitrile, 1117), 1,3-bis(2-cyanoethoxy)propanenitrile (dinitrile, 1118), 1,3-bis(2-cyanoethoxy)propanenitrile (dinitrile, 1119), 1,3-bis(2-cyanoethoxy)propanenitrile (dinitrile, 1120), 1,3-bis(2-cyanoethoxy)propanenitrile (dinitrile, 1121), 1,3-bis(2-cyanoethoxy)propanenitrile (dinitrile, 1122), 1,3-bis(2-cyanoethoxy)propanenitrile (dinitrile, 1123), 1,3-bis(2-cyanoethoxy)propanenitrile (dinitrile, 1124), 1,3-bis(2-cyanoethoxy)propanenitr propan-2-yl]oxy}propanenitrile (trinitrile, 1116), 1-(propan-2-yl)-1H-imidazole-4,5-dicarbonitrile (dinitrile, 1202), pyridine-2,6-dicarbonitrile (dinitrile, 1204), ethylene glycol bis(propionitrile) ether (dinitrile, 1206), 3-(triethoxysilyl)propionitrile (mononitrile, 1208), succinonitrile (dinitrile, 1210), benzonitrile (mononitrile, 1212), 4-(trifluoromethyl)benzonitrile (mononitrile, 1302), 1,2,2,3-propanetetracarbonitrile (tetrakisnitrile, 1304). Some examples of other (non-nitrile) compounds that may be used as high temperature storage additives are shown in Figures 13, 14 and 15.Some examples of non-nitrile compounds that may be used as high temperature (HT) storage additives are: triisopropyl borate (TIB) (1306), 1-propene 1,3-sultone (PES) (1308), 1,3-propane sultone (1310), phenyl disulfide (1402), sulfolane (1404), N,N,N,N-tetraethylsulfamide (1406), succinic anhydride (1408), maleic anhydride. (1410), tris(trimethylsilyl) phosphite (TMSPI) (1502), tris(trimethylsilyl) phosphate (1504), dimethoxydiphenylsilane (1506), tris(trimethylsilyl) borate (TMSB) (1508), 3-(triethoxysilyl)propyl isocyanate (1510), methylene methanedisulfonate (MMDS), and 1,3,2-dioxathiolane 2,2-dioxide (DTD).
[0175] In some designs, nitriles may behave differently when interacting with the surface of the positive or negative electrode at high SOC and high temperature. For example, nitriles may coordinate to the surface of the positive electrode through the center of transition metal oxide. The coordination mechanism may be related to the large dipole moment of the nitrile group. Although effective coordination may be a prerequisite for strong binding of nitriles to transition metal oxides, the length of the nitrile chain may play an important role in blocking the access of CC to the surface of the positive electrode in some designs. On the one hand, the length of the nitrile chain may determine the effectiveness of blocking CC molecules from reaching the surface of the positive electrode. The length of the chain may have an optimal design to form an arch on the surface of the positive electrode to screen the molecules from reaching the surface. On the other hand, the steric bulk of the nitrile may be used to block CC molecules from reaching the surface of the positive electrode. In some embodiments of the present disclosure, the steric bulk of the nitrile may be improved by using (1) nitriles with fused aliphatic rings such as cyclopropane rings, (2) nitriles with carbon-carbon double bonds, or (3) branched nitriles, such as methyl or dimethyl substituted nitriles. In other embodiments of the present disclosure, star-shaped nitriles with 3 or 4 aliphatic carbon chains off-center may be used to allow the steric bulk of the nitrile, where the aliphatic carbon may also be replaced with an oxygen group such as O. In some other embodiments, nitriles with 4 or more nitrile groups may tether to the surface of the positive electrode and block other molecules from oxidation. Furthermore, in some designs, the oxidative stability of the nitrile may determine the onset of high temperature (HT) outgassing. For example, nitriles with low oxidative stability may decompose at low oxidation potentials with the formation of an electronically insulating film that is Li-ion conducting. Such surface protection may also block CC and other molecules from undesired or excessive decomposition at the positive electrode in some designs. Nitriles with ethylene glycol structural units may be effectively used in some designs to allow the formation of an electronically insulating film that is Li-ion conducting.
[0176] In some designs, nitriles may tend to decompose on the surface of the negative electrode due to their electron acceptor properties when exposed to an electron source. Therefore, in some designs, using nitriles with low reduction potentials may be beneficial to achieve long cycle life, reduce voltage hysteresis, and reduce internal resistance while ensuring surface protection of the positive electrode. In some designs, the positive electrode stability of nitriles may be adjusted by the electron donor property of the nitrile. For example, in some designs, the electron donor property of nitriles may be improved by replacing hydrogen atoms with short-chain aliphatic groups such as methyl or ethyl groups. In another example, the electron donor property may be improved by incorporating oxygen (O) groups into the structure of the nitrile.
[0177] The inventors have found that in some embodiments, it may be advantageous to use a mixture of nitriles to achieve a good balance of cycle life, high temperature cycle life, calendar life, HT storage outgassing, discharge V, C rate, and inhibit transition metal dissolution. In some embodiments, it may be advantageous to use a single dinitrile, with a mole fraction of about 0.5 mol% to about 3 mol%, to achieve a good balance of cycle life and HT outgassing. In some other embodiments, it may be advantageous to use a mixture of dinitrile and trinitrile, with a mole fraction of dinitrile of about 0.5 mol% to about 2 mol%, and a mole fraction of trinitrile of about 0.5 to about 1 mol%, to achieve a good balance of cycle life and HT outgassing. In some embodiments, it may be advantageous to use a mixture of dinitrile (e.g., ADN), trinitrile (e.g., HTCN), and a non-nitrile high temperature storage additive (e.g., PES). The total mole fraction of such a mixture containing a dinitrile (e.g., ADN), a trinitrile (e.g., HTCN), and a non-nitrile high temperature storage additive (e.g., PES) may range from about 0.1 mol % to about 3 mol %, or from about 1.0 mol % to about 3 mol %. In some embodiments, the mole fraction of one or more high temperature storage additives in the electrolyte may range from about 0.1 mol % to about 3 mol %.
[0178] The inventors have also found that it may be advantageous to use high temperature storage additives, such as triisopropyl borate (TIB) (1306), succinic anhydride (1408), maleic anhydride (1410), tris(trimethylsilyl) phosphite (TMSPI) (1502), and tris(trimethylsilyl) borate (TMSB) (1508), to reduce thickness change, scavenge HF, and reduce dissolution of transition metals. In some embodiments, it may be advantageous to use these additives in addition to the nitrile additive. In other embodiments, it may be advantageous to use about 0.1 mol % to about 3 mol % of these additives in the electrolyte formulation.
[0179] In some embodiments of the present disclosure, combinations of nitrile additive(s), charge transfer additives (e.g., Li salt additives), or other HT storage additives including branched esters may be advantageously used to reduce high temperature (HT) outgassing, for example, by preventing or reducing transition metal dissolution at high temperatures (e.g., above battery operating temperatures, e.g., about 50-80° C.) and by forming a protective cathode film. In specific examples, the branched ester may be selected from one of the branched esters, such as ethyl isobutyrate, methyl isobutyrate, ethyl trimethylacetate, ethyl isovalerate, methyl trimethylacetate, methyl isovalerate, methyl 2-methylbutyrate, ethyl 2-methylbutyrate, to name a few. In specific examples, the Li salt additive may be selected from lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium fluorosulfate (LiSO3F), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(oxalato)borate (LiBOB). In some embodiments, non-Li metal (e.g., Mg, Ca, Sr, Ba, La, lanthanides, Y, etc.) analogs of such salts may be used in addition to or instead of the Li salts (e.g., about 0.03 mol% to about 6 mol% of the total non-Li salt amount). In some embodiments, the mole fraction of the Li salt additive in the electrolyte may preferably be in the range of about 0.1 mol% to about 3.0 mol%, or in the range of about 0.1 mol% to about 6.0 mol%, or in the range of about 0.5 mol% to about 1.5 mol%. The optimum additive mole fraction (concentration) in combination with the branched ester may depend on the particular cell design and electrolyte composition.
[0180] In one or more embodiments of the present disclosure, a suitable anode and cathode surface protection combination that reduces high temperature (HT) outgassing may be designed by using a single nitrile or a mixture of nitriles and additive Li salt(s). In specific examples, the additive Li salt(s) may be selected from lithium difluorophosphate (LiPO2F2 or LFO), lithium tetrafluoroborate (LiBF4), lithium fluorosulfate (LiSO3F), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluoro(oxalato)borate (LiDFOB), to name a few. In some embodiments, non-Li metal (e.g., Mg, Ca, Sr, Ba, La, lanthanides, Y, etc.) analogs of such salts may be used in addition to or instead of the Li additive salt (e.g., about 0.01 mol % to about 3 mol % of the total non-Li salt amount). In some embodiments, the mole fraction of the Li additive salt in the electrolyte may preferably be in the range of about 0.1 mol % to about 3.0 mol %. In some embodiments, if the molar fraction of the additive salt in the electrolyte exceeds approximately 2.5-3 mol %, those fractions may need to be carefully optimized for a particular cell design, as this may tend to reduce cycle life, which is undesirable.
[0181] In one or more embodiments of the present disclosure, the preferred lithium-ion battery electrolyte may include lithium difluorophosphate (LFO). In some designs, this additive salt tends to reduce the charge transfer resistance (Rct) at room temperature, low temperature, and / or high temperature. The reduction in Rct contributes to increasing the discharge voltage and improving low temperature performance. In some cell designs, LFO can be particularly effective in reducing Rct simultaneously at the negative and positive electrodes at both room temperature and high temperature (e.g., high temperature) and improving the discharge voltage of the battery cell. In some embodiments, LFO contributes to mitigating high temperature gassing.
[0182] In one or more embodiments of the present disclosure, Li metal or Li ion battery cells may employ an electrolyte comprising (1) a branched ester, (2) a nitrile additive composition comprising an appropriate amount of a selected nitrile compound, or an appropriate mixture of selected nitrile compounds, or (3) a Li salt additive, or (4) other HT storage additives that may provide multiple benefits to Li or Li ion batteries, particularly those comprising a subclass of high capacity, moderate volume change anodes comprising about 5 to about 100 wt. % (as a fraction of all particles including active material) of (nano)composite anode powder, where such (nano)composite anode powders have a moderately high volume change during a first charge / discharge cycle, a moderate volume change during subsequent charge / discharge cycles, an average size (e.g., average diameter) in the range of about 0.2 to about 40 microns, and a mass (e.g., mass) of about 0.5 to about 50 microns. 2 / g range, and for Si-containing (nano)composite anode powders, specific reversible capacity (when normalized by the mass of the composite anode particles alone) in the range of about 800 to about 3000 mAh / g, or corresponding anode specific reversible capacity in the range of about 400 to about 2800 mAh / g (when normalized by the combined mass of all active electrode particles, conductive additives, and binder). In some designs (e.g., depending on cell chemistry, load, operating conditions, and / or other factors), suitable branched esters or related compounds (or mixtures thereof) may be added at additive levels (about 0.1 mol % to about 5-10 mol %) or as major cosolvent / principal cosolvent levels (about 30 mol % to about 80 mol %) to obtain substantial benefits. In other embodiments, such anode powders may include a mixture of Si-C nanocomposite and graphite, so-called blended anodes.
[0183] Examples of such benefits may include one or more of the following: (i) improved high temperature storage stability (e.g., higher reversible capacity retention at high state of charge (SOC) (e.g., about 70-100% SOC) after about 1 hour to about 10 years of storage at high temperatures (e.g., about 40-80° C.) or reduced gassing after storage or cycling at high temperatures); (ii) reduced gassing during storage or cycling at room or low temperatures; (iii) reduced or minimized cell expansion (or built-in stresses in the cell) at end of life (e.g., after about 20-80% initial capacity retention); (iv) various (e.g., different ) improving cycling stability when used at elevated temperature conditions; (v) reducing or minimizing impedance increase during cycling; (vi) reducing or minimizing the formation of undesirable (harmful) by-products, particularly during battery cell operation; (vii) reducing carbon monoxide production at the positive and negative electrodes; (viii) reducing carbon dioxide production at the positive and negative electrodes; (ix) reducing hydrogen production at the negative electrode, (x) reducing methane production at the negative electrode; (xi) reducing C2 hydrocarbon production at the negative electrode, and / or (xii) reducing C3 hydrocarbon production at the negative electrode.
[0184] Some of such benefits may derive from the formation of a more favorable or robust cathode / electrolyte interphase (CEI) film, which may, for example, help reduce or minimize electrolyte oxidation at the cathode associated with the formation of gaseous species, or may help reduce or minimize cathode dissolution, or other adverse / undesirable interactions between the cathode and liquid electrolyte in Li or Li-ion batteries. In some embodiments, the more robust CEI film formation may be associated with having stronger adhesion to the cathode surface, for example, when using an electrolyte containing: (1) a nitrile additive composition comprising a suitable amount of a selected nitrile compound, or a mixture of selected nitrile compounds in suitable amounts; (2) a mixture of nitrile additive compositions comprising a selected branched ester (e.g., ethyl isobutyrate, ethyl trimethylacetate, and / or other suitable esters comprising 2 or 3 aliphatic carbons bonded at the alpha or beta position to a carboxyl group); or (3) a mixture of a nitrile additive, a Li salt additive, and a branched ester. Some of such benefits may also derive from the formation of a more favorable or robust solid electrolyte interphase (SEI) film at the anode (or from helping to maintain a more stable anode SEI, for example). In some designs, improved SEI stability may be associated with dramatically reduced diffusion of suitable branched esters and related compounds through the SEI, preventing or greatly reducing or minimizing the reduction of them as well as other electrolyte components at the anode surface, especially at high temperatures. In some designs, improved SEI stability may be associated with reduced ability to form gaseous species upon reduction of the electrolyte. In some designs, improved SEI stability may be associated with reduced ability to form a more elastically or plastically deformable (in the electrolyte) SEI, or, for example, a less resistive SEI.Such improved SEI stability or properties may help to reduce or minimize, for example, electrolyte reduction at the negative electrode (with the attendant undesirable irreversible loss of cyclable Li, or with the undesirable formation of gaseous species or undesirable negative electrode swelling, etc.) that may lead to impedance growth or gassing or other undesirable processes or performance degradation in the cell, or may help to reduce or minimize negative electrode dissolution or other adverse / undesirable interactions between the negative electrode and liquid electrolyte in Li or Li-ion batteries. Some of such benefits may derive from a reduction in the elastic modulus of the electrode binder upon exposure of the electrode to the electrolyte during cell formation or cell operation (cycling). In some designs, it may be preferable to select an electrolyte composition that includes some suitable nitrile; or a suitable mixture of nitriles; or a suitable mixture of nitriles and branched esters (e.g., ethyl isobutyrate, or other suitable esters with 2 or 3 aliphatic carbons alpha or beta to the carboxyl group, and others); or a suitable mixture of nitriles, charge transfer additives (e.g., Li salt additives, such as LiFSI, LFO, LiBF4, and LiDFOB), and other additives; or a suitable mixture of nitriles, charge transfer additives, other HT storage additives (e.g., DTD, MMDS), and branched esters. Preferably, when a cell containing the electrodes is exposed to the electrolyte, the elastic modulus of at least one binder of the electrodes does not decrease by more than about 30% by volume (e.g., more preferably does not decrease by more than about 10% by volume).
[0185] In some designs, using (1) a nitrile additive composition comprising a suitable amount of a selected nitrile compound, or a mixture of suitable amounts of a selected nitrile compound, (2) a mixture of nitrile additive compositions comprising a selected branched ester (e.g., ethyl isobutyrate, ethyl trimethylacetate, and / or other suitable esters having 2 or 3 aliphatic carbons attached at the alpha or beta position to a carboxyl group), (3) an electrolyte containing the mixture of the nitrile additive, Li salt additive, and branched ester in a Li or Li-ion battery cell can exhibit a significant increase in the presence of FEC or VC in the Li-ion solvation shell to facilitate the formation of a robust SEI.
[0186] In some designs, using (1) a nitrile additive composition comprising a suitable amount of a selected nitrile compound or a mixture of suitable amounts of a selected nitrile compound, (2) a mixture of nitrile additive compositions comprising a selected branched ester (e.g., ethyl isobutyrate, ethyl trimethylacetate, and / or other suitable esters having 2 or 3 aliphatic carbons attached in the alpha or beta position to a carboxyl group), or (3) an electrolyte containing a mixture of nitrile additives, branched esters, other HT storage additives, and Li salt additives in a Li-ion battery cell can provide a significant reduction in gassing at the negative electrode surface (including, but not limited to, in the case of Li plating at the negative electrode surface). In some designs, branched esters having 2 or 3 alkyl groups alpha to the carboxyl group of the branched ester can provide particularly improved performance. In some designs, branched esters having 2 or 3 alkyl groups alpha to the carboxyl group of the branched ester can provide a reduction in the rate of hydrogen, methane, ethane, ethylene, propene, propane, butane, and / or butene formation at the negative electrode.
[0187] In some designs, using electrolytes containing (1) branched esters (e.g., ethyl isobutyrate, ethyl trimethylacetate, and / or other suitable esters with 2 or 3 aliphatic carbons attached alpha or beta to the carboxyl group) or (2) branched esters with Li salt additives (e.g., LFO, LiBF4, LiDFOB, LiFSI) in Li-ion battery cells can mitigate the parasitic (highly undesirable) degradation of typical SEI "builders" present in the electrolyte (e.g., fluoroethylene carbonate (FEC), vinylene carbonate (VC), ethylene carbonate (EC) among others) due to the slowing down of alkoxide formation. In some designs, esters with 2 or 3 alkyl groups alpha to the carboxyl group of the ester can offer particularly improved performance due to the steric bulk of the ester and the slowing down of alkoxide formation.
[0188] In some designs, using an electrolyte containing a branched ester (e.g., ethyl isobutyrate, ethyl trimethylacetate, and / or other suitable esters having two or three aliphatic carbons attached at the alpha or beta position relative to the carboxyl group) in a Li-ion battery cell can reduce or completely eliminate the undesired formation of the enol form of the corresponding ester (or reduce the formation of the tautomeric enol form) (e.g., by shifting the equilibrium toward the ester). In some designs, by reducing or avoiding the presence of enols in the electrolyte, parasitic degradation of the Li salt(s) (e.g., lithium hexafluorophosphate (LiPF6)) or other electrolyte components, e.g., by alcoholysis, can be significantly reduced or minimized. Similarly, in some designs, the formation of hydrofluoric acid (HF) or other undesired by-products of, e.g., LiPF6 alcoholysis, can be significantly reduced or minimized.
[0189] In some other embodiments of the present disclosure, it may be beneficial to use a low viscosity co-solvent selected from open-chain carbonates such as, but not limited to, dimethyl carbonate and ethyl methyl carbonate. In some designs, such co-solvents may be beneficial for improving HT outgassing and extending cycle life. In some other designs, the use of such solvents may lead to extensive outgassing during long-term gas generation at low SOC. In some other designs, it may be advantageous to use high mole fractions (concentrations) of FEC and VC that build a robust SEI to avoid outgassing during long-term cycles at low SOC.
[0190] Table 1 (FIG. 16) shows the compositional data for electrolyte formulations (ELY) #1, #2, #3, #4, #5, #6, #7, #8, #9, #10, #11, #12, #13, and #14. For each electrolyte, the relative amounts, expressed as mole %, of fluoroethylene carbonate (FEC), vinylene carbonate (VC), ethylene carbonate (EC), ethyl propionate (EP), ethyl isobutyrate (EI), ethyl isovalerate (EIV), ethyl trimethylacetate (ET), dimethyl carbonate (DMC), adiponitrile (ADN), 1,3,6-hexanetricarbonitrile (HTCN), 1-propene-1,3-sultone (PES), lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LFO), lithium difluoro(oxalato)borate (LiDFOB), and lithium tetrafluoroborate (LiBF4) are shown. No entry indicates the respective amount is zero. The linear ester entries correspond to the respective amounts of EP. The branched ester entries are the sum of the EI, EIV and ET entries, respectively. The total ester entries are the sum of the respective linear and branched ester entries. The linear ester:branched ester molar ratio entries are the ratio of each linear ester entry to each branched ester entry. The total cyclic carbonates entries are the sum of the FEC, VC and EC entries, respectively. The non-FEC cyclic carbonates entries are the sum of the VC and EC entries, respectively. The high temperature storage additive entries are the sum of the ADN, HTCN and PES entries, respectively. The charge transfer additive entries are the sum of the LFO, LiDFOB and LiBF4 entries, respectively.
[0191] In one illustrative example, a small consumer Li-ion battery cell (Li-ion battery cell used in consumer electronics) having a capacity of about 0.020 Ah may include: (i) an anode comprising 19 wt. % Si-C nanocomposite active material, and 76.5 wt. % graphite cast onto a Cu collector foil from an aqueous suspension comprising carboxymethyl cellulose and butadiene-styrene copolymer, and carbon black conductive additive, with a specific reversible capacity of about 1520 mAh / g when normalized by the weight of the active material in the anode; (ii) a cathode comprising high voltage LCO (approximate composition of LiCoO) active material cast onto an Al collector foil from an organic solvent suspension comprising a polyvinylidene fluoride (PVDF) based binder and carbon black conductive additive, with a specific reversible capacity of about 190 mAh / g when normalized by the weight of the active material in the cathode, with an anode:cathode areal capacity ratio of about 1.08:1, and a specific reversible capacity of about 3.27 mAh / cm. 2 an area reversible capacity loading of about 1.0 V, a charging voltage of about 4.4 V, (iii) a polymer ceramic separator, and (iv) an ELY #1 comprising about 15.39 mol % FEC, about 66.68 mol % ethyl propionate (EP) (linear ester), about 4.22 mol % VC, about 0.80 mol % adiponitrile (ADN), about 0.54 mol % 1,3,6-hexanetricarbonitrile (HTCN), about 1.12 mol % 1-propene 1,3-sultone (PES), and about 11.24 mol % LiPF6. Hereinafter, a particular electrolyte formulation may be referred to as an ELY followed by a number (e.g., ELY #1, ELY #2, etc.).
[0192] In one illustrative example, a small consumer Li-ion battery cell (Li-ion battery cell used in consumer electronics) having a capacity of about 0.020 Ah may include: (i) an anode comprising 19 wt. % Si-C nanocomposite active material, and 76.5 wt. % graphite powder cast onto a Cu collector foil from an aqueous suspension comprising carboxymethyl cellulose and butadiene-styrene copolymer, and carbon black conductive additive, with a specific reversible capacity of about 1520 mAh / g when normalized by the weight of the active material in the anode; (ii) a cathode comprising high voltage LCO active material cast onto an Al collector foil from an organic solvent suspension comprising a polyvinylidene fluoride (PVDF) based binder and carbon black conductive additive, with a specific reversible capacity of about 190 mAh / g when normalized by the weight of the active material in the cathode, with an anode:cathode areal capacity ratio of about 1.08:1 and a specific reversible capacity of about 3.27 mAh / cm. 2 % VC、5.28 mol% 1,3,6-hexanetricarbonitrile (HTCN) ...
[0193] In one illustrative example, a small consumer Li-ion battery cell (Li-ion battery cell used in consumer electronics) having a capacity of about 0.020 Ah may include: (i) an anode comprising 19 wt. % Si-C nanocomposite active material, and 76.5 wt. % graphite cast onto a Cu collector foil from an aqueous suspension comprising carboxymethyl cellulose and butadiene-styrene copolymer, and carbon black conductive additive, with a specific reversible capacity of about 1520 mAh / g when normalized by the weight of the active material in the anode; (ii) a cathode comprising high voltage LCO active material cast onto an Al collector foil from an organic solvent suspension comprising a polyvinylidene fluoride (PVDF) based binder and carbon black conductive additive, with a specific reversible capacity of about 190 mAh / g when normalized by the weight of the active material in the cathode, with an anode:cathode areal capacity ratio of about 1.08:1 and a specific reversible capacity of about 3.27 mAh / cm. 2 % VC、5.28 mol% 1-propene-1,3-sultone (PES) ...
[0194] In one illustrative example, a small consumer Li-ion battery cell (Li-ion battery cell used in consumer electronics) having a capacity of about 0.020 Ah may include: (i) an anode comprising 76.5 wt. % graphite cast onto a Cu collector foil from an aqueous suspension comprising 19 wt. % Si-C nanocomposite active material and carboxymethyl cellulose and butadiene-styrene copolymer, and carbon black conductive additive, with a specific reversible capacity of about 1520 mAh / g when normalized by the weight of the active material in the anode; (ii) a cathode comprising high voltage LCO active material cast onto an Al collector foil from an organic solvent suspension comprising a polyvinylidene fluoride (PVDF) based binder and carbon black conductive additive, with a specific reversible capacity of about 190 mAh / g when normalized by the weight of the active material in the cathode, with an anode:cathode areal capacity ratio of about 1.08:1 and a specific reversible capacity of about 3.27 mAh / cm. 2 % VC、5.28 mol%、5.28 mol% 1,3,6-hexanetricarbonitrile (HTCN) ...
[0195] In one illustrative example, a small consumer Li-ion battery cell (Li-ion battery cell used in consumer electronics) having a capacity of about 0.020 Ah may include: (i) an anode comprising 76.5 wt. % graphite cast onto a Cu collector foil from an aqueous suspension comprising 19 wt. % Si-C nanocomposite active material and carboxymethyl cellulose and butadiene-styrene copolymer, and carbon black conductive additive, with a specific reversible capacity of about 1520 mAh / g when normalized by the weight of the active material in the anode; (ii) a cathode comprising high voltage LCO active material cast onto an Al collector foil from an organic solvent suspension comprising a polyvinylidene fluoride (PVDF) based binder and carbon black conductive additive, with a specific reversible capacity of about 190 mAh / g when normalized by the weight of the active material in the cathode, with an anode:cathode areal capacity ratio of about 1.08:1 and a specific reversible capacity of about 3.27 mAh / cm. 2 % 1,3,6-hexanetricarbonitrile (HTCN), about 1.25 mol% 1-propene-1,3-sultone (PES), about 1.03 mol% lithium difluorophosphate (LFO), and 11.43 mol% LiPF6.
[0196] Li-ion battery test cells containing ELY #1, ELY #2, ELY #3, ELY #4 and ELY #5, respectively, were tested in cycle life tests. Test cells were assembled and the initial formation procedure was performed on the test cells. Charge / discharge test conditions included 1C charge at constant current constant potentiostatic pressure (CCCP) to 4V, ramped to 0.5C, then 0.5C charge at CCCP to 4.4V and ramped to 0.05C, followed by 0.5C discharge. The electrolytes in this series (#1, #2, #3, #4 and #5) contain FEC, VC, ADN, HTCN and PES. The test cells contain a graphite and Si-C composite particle blend anode. ELY #1 contains linear ester but no branched ester. ELY #2 and ELY #3 contain linear ester-branched ester mixture and no charge transfer additive. ELY #4 and ELY #5 contain a linear ester-branched ester mixture and contain a charge transfer additive. ELY #2 (linear ester EP, branched ester EI) and ELY #3 (linear ester EP, branched ester EIV) showed better cycle life than ELY #1, which contains one linear ester EP. ELY #4, which uses LiBF4 charge transfer additive (Li salt additive), showed similar cycle life to ELY #2, which does not use Li salt additive. ELY #5, which uses LFO Li salt additive, showed worse cycle life compared to ELY #3, which does not feature Li salt additive.
[0197] In one illustrative example, a small Li-ion battery cell having a capacity of about 0.055 Ah may include: (i) an anode comprising 50% by volume Si-C nanocomposite active material and graphite cast from an aqueous suspension containing carboxymethyl cellulose and butadiene-styrene copolymer, and carbon black conductive additive onto a Cu collector foil, with a specific reversible capacity of about 1520 mAh / g when normalized by the weight of the active material in the anode; (ii) a cathode comprising high voltage NMC811 active material cast from an organic solvent suspension containing a polyvinylidene fluoride (PVDF) based binder and carbon black conductive additive onto an Al collector foil, with a specific reversible capacity of about 200 mAh / g when normalized by the weight of the active material in the cathode, with an anode:cathode areal capacity ratio of about 1.15:1 and a specific reversible capacity of about 4.8 mAh / cm. 2 an area-reversible capacity loading of about 1.2 V, a charging voltage of about 4.2 V, (iii) a polymer ceramic separator, and (iv) an ELY #6 comprising: about 9.13 mol % FEC, about 54.42 mol % ethyl propionate (EP) (linear ester), about 2.00 mol % VC, about 24.25 mol % ethylene carbonate (EC), and about 10.20 mol % LiPF6.
[0198] In one illustrative example, a small Li-ion battery cell having a capacity of about 0.055 Ah may include: (i) an anode comprising 50% by volume Si-C nanocomposite active material and graphite cast from an aqueous suspension containing carboxymethyl cellulose and butadiene-styrene copolymer, and carbon black conductive additive onto a Cu collector foil, with a specific reversible capacity of about 1520 mAh / g when normalized by the weight of the active material in the anode; (ii) a cathode comprising high voltage NMC811 active material cast from an organic solvent suspension containing a polyvinylidene fluoride (PVDF) based binder and carbon black conductive additive onto an Al collector foil, with a specific reversible capacity of about 200 mAh / g when normalized by the weight of the active material in the cathode, with an anode:cathode areal capacity ratio of about 1.15:1 and a specific reversible capacity of about 4.8 mAh / cm. 2an area-reversible capacity loading of about 1.0 to about 4.2 V, (iii) a polymer ceramic separator, and (iv) an ELY #7 comprising: about 9.94 mol % FEC, about 50.49 mol % ethyl isobutyrate (EI) (branched ester), about 2.17 mol % VC, about 26.33 mol % ethylene carbonate (EC), and about 11.08 mol % LiPF6.
[0199] Li-ion battery test cells containing ELY #6 and ELY #7, respectively, were tested in cycle life tests. Test cells were assembled and the initial formation procedure was performed on the test cells. Charge / discharge test conditions included 1C charge to 4.2V in CCCP, ramped to 0.05C, followed by 1C discharge. The electrolytes in this series (#6 and #7) contain FEC, VC, and EC. The test cells contain a graphite and Si-C composite particle blend anode. The ELY #7 cell containing branched ester EI showed improved cycle life versus the ELY #6 cell containing linear ester EP.
[0200] Li-ion battery test cells containing ELY #6 and ELY #7, respectively, were tested for gas volume evolved as follows: The test cells were assembled and an initial formation procedure was performed on the test cells. The test cells were charged to a high state of charge and the initial cell thickness was measured. The cells were heated to a temperature of 60° C. and maintained at a temperature of 60° C. for a period of 72 hours (high temperature storage treatment). The test cells were then cooled to 25° C. and the final cell thickness was measured within 1 hour after reaching 25° C. Gas chromatography was used to analyze the volume of gas evolved in the cells. The gas volume from the cell with ELY #7 was 0.217 mL, which was 12% by volume less than the gas volume collected from the cell with ELY #6.
[0201] In one illustrative example, a small Li-ion battery cell having a capacity of about 0.055 Ah may include: (i) an anode comprising 50% by volume Si-C nanocomposite active material and graphite cast from an aqueous suspension containing carboxymethyl cellulose and butadiene-styrene copolymer, and carbon black conductive additive onto a Cu collector foil, with a specific reversible capacity of about 1520 mAh / g when normalized by the weight of the active material in the anode; (ii) a cathode comprising high voltage NMC811 active material cast from an organic solvent suspension containing a polyvinylidene fluoride (PVDF) based binder and carbon black conductive additive onto an Al collector foil, with a specific reversible capacity of about 200 mAh / g when normalized by the weight of the active material in the cathode, with an anode:cathode areal capacity ratio of about 1.15:1 and a specific reversible capacity of about 4.8 mAh / cm. 2 an area-reversible capacity loading of about 1.2 V, a charging voltage of about 4.2 V, (iii) a polymer ceramic separator, and (iv) an ELY #8 comprising: about 7.75 mol % FEC, about 61.44 mol % dimethyl carbonate (DMC), about 1.69 mol % VC, about 20.49 mol % ethylene carbonate (EC), and about 8.63 mol % LiPF6.
[0202] In one illustrative example, a small Li-ion battery cell having a capacity of about 0.055 Ah may include: (i) an anode comprising 50% by volume Si-C nanocomposite active material and graphite cast from an aqueous suspension containing carboxymethyl cellulose and butadiene-styrene copolymer, and carbon black conductive additive onto a Cu collector foil, with a specific reversible capacity of about 1520 mAh / g when normalized by the weight of the active material in the anode; (ii) a cathode comprising high voltage NMC811 active material cast from an organic solvent suspension containing a polyvinylidene fluoride (PVDF) based binder and carbon black conductive additive onto an Al collector foil, with a specific reversible capacity of about 200 mAh / g when normalized by the weight of the active material in the cathode, with an anode:cathode areal capacity ratio of about 1.15:1 and a specific reversible capacity of about 4.8 mAh / cm. 2an area-reversible capacity loading of about 1.2 V, a charging voltage of about 4.2 V, (iii) a polymer ceramic separator, and (iv) an ELY #9 comprising: about 7.66 mol % FEC, about 61.51 mol % dimethyl carbonate (DMC), about 1.69 mol % VC, about 20.49 mol % ethylene carbonate (EC), about 0.73 mol % LiBF4, and about 7.92 mol % LiPF6.
[0203] Li-ion battery test cells containing ELY #8 and ELY #9, respectively, were tested in cycle life tests. Test cells were assembled and the initial formation procedure was performed on the test cells. Charge / discharge test conditions included 1C charge to 4.2V in CCCP, ramped to 0.05C, followed by 1C discharge. The electrolytes in this series (#8, #9) contain FEC, VC, EC, and DMC. The test cells contain a graphite and Si-C composite particle blend anode. The test cells with both electrolytes (#8, #9) show satisfactory cycle life. However, the ELY #8 cell without LiBF4 shows improved cycle life versus the ELY #9 cell with LiBF4.
[0204] In one illustrative example, a small consumer Li-ion battery cell (a Li-ion battery cell used in consumer electronics products) having a capacity of about 0.140 Ah may include: (i) an anode comprising 100 wt. % graphite (i.e., 100% of the active material is graphite) cast onto a Cu collector foil from an aqueous suspension comprising carboxymethyl cellulose and butadiene-styrene copolymer, and a carbon black conductive additive; (ii) a cathode comprising a high voltage LCO active material cast onto an Al collector foil from an organic solvent suspension comprising a polyvinylidene fluoride (PVDF) based binder and a carbon black conductive additive (having a specific reversible capacity of about 190 mAh / g when normalized by the weight of the active material in the cathode); a charge voltage of about 4.25 V; (iii) a polymer ceramic separator; and (iv) an ELECTROLYTE ... #10: about 56.00 mol % ethyl trimethylacetate (ET) (branched ester), about 31.43 mol % ethylene carbonate (EC), and about 12.57 mol % LiPF6.
[0205] In one illustrative example, a small consumer Li-ion battery cell (a Li-ion battery cell used in consumer electronics products) having a capacity of about 0.140 Ah may include: (i) an anode comprising 100 wt. % graphite (i.e., 100% of the active material is graphite) cast onto a Cu collector foil from an aqueous suspension comprising carboxymethyl cellulose and butadiene-styrene copolymer, and a carbon black conductive additive; (ii) a cathode comprising a high voltage LCO active material cast onto an Al collector foil from an organic solvent suspension comprising a polyvinylidene fluoride (PVDF) based binder and a carbon black conductive additive (having a specific reversible capacity of about 190 mAh / g when normalized by the weight of the active material in the cathode); a charge voltage of about 4.25 V; (iii) a polymer ceramic separator; and (iv) an ELECTROLYTE ... #11: about 4.26 mol% fluoroethylene carbonate (FEC), about 58.55 mol% ethyl isobutyrate (EI) (branched ester), about 3.16 mol% vinylene carbonate (VC), about 22.12 mol% ethylene carbonate (EC), and about 11.79 mol% LiPF6.
[0206] In one illustrative example, a small consumer Li-ion battery cell (a Li-ion battery cell used in consumer electronics products) having a capacity of about 0.140 Ah may include: (i) an anode comprising 100 wt. % graphite (i.e., 100% of the active material is graphite) cast onto a Cu collector foil from an aqueous suspension comprising carboxymethyl cellulose and butadiene-styrene copolymer, and a carbon black conductive additive; (ii) a cathode comprising a high voltage LCO active material cast onto an Al collector foil from an organic solvent suspension comprising a polyvinylidene fluoride (PVDF) based binder and a carbon black conductive additive (having a specific reversible capacity of about 190 mAh / g when normalized by the weight of the active material in the cathode); a charge voltage of about 4.25 V; (iii) a polymer ceramic separator; and (iv) an ELECTROLYTE ... #12: about 25.56 mol% fluoroethylene carbonate (FEC), about 59.31 mol% ethyl isobutyrate (EI) (branched ester), about 3.20 mol% vinylene carbonate (VC), and about 11.92 mol% LiPF6.
[0207] Li-ion battery test cells containing ELY #10, ELY #11 and ELY #12, respectively, were tested in cycle life tests. Test cells were assembled and the initial formation procedure was performed on the test cells. Charge / discharge test conditions included 1C charge to 4.35V in CCCP, ramped to 0.05C, followed by 1C discharge. The test cells contain graphite anodes. ELY #10 contains ethylene carbonate (EC) and ET (branched esters). ELY #11 contains FEC, VC, EC and EI (branched esters). ELY #12 contains FEC, VC and EI (branched esters). ELY #12 cell (FEC, EI) showed better cycle life than ELY #11 cell (FEC, EC, EI) and ELY #10 cell (no EC, ET, FEC). The ELY #11 cells (FEC, EC, EI) showed better cycle life than the ELY #10 cells (EC, ET, (no FEC)).
[0208] In one illustrative example, a consumer Li-ion battery cell (Li-ion battery cell used in consumer electronics products) having a capacity of about 0.020 Ah may include: (i) an anode comprising 76.5 wt. % graphite cast onto a Cu collector foil from an aqueous suspension comprising 19 wt. % Si-C nanocomposite active material and carboxymethyl cellulose and butadiene-styrene copolymer, and carbon black conductive additive, with a specific reversible capacity of about 1520 mAh / g when normalized by the weight of the active material in the anode; (ii) a cathode comprising high voltage LCO active material cast onto an Al collector foil from an organic solvent suspension comprising a polyvinylidene fluoride (PVDF) based binder and carbon black conductive additive, with a specific reversible capacity of about 190 mAh / g when normalized by the weight of the active material in the cathode, with an anode:cathode areal capacity ratio of about 1.08:1 and a specific reversible capacity of about 3.27 mAh / cm. 2 an area-reversible capacity loading of about 1.0 to about 4.4 V, a charging voltage of about 4.4 V, (iii) a polymer ceramic separator, and (iv) an ELY #13 comprising: about 16.61 mol % FEC, about 34.40 mol % ethyl propionate (EP) (linear ester), about 29.75 mol % ethyl isobutyrate (EI) (branched ester), about 4.53 mol % VC, about 0.86 mol % adiponitrile (ADN), about 0.54 mol % 1,3,6-hexanetricarbonitrile (HTCN), about 1.21 mol % 1-propene-1,3-sultone (PES), about 0.98 mol % lithium difluorophosphate (LFO), and about 11.11 mol % LiPF6.
[0209] In one illustrative example, a small consumer Li-ion battery cell (Li-ion battery cell used in consumer electronics) having a capacity of about 0.020 Ah may include: (i) an anode comprising 76.5 wt. % graphite cast onto a Cu collector foil from an aqueous suspension comprising 19 wt. % Si-C nanocomposite active material and carboxymethyl cellulose and butadiene-styrene copolymer, and carbon black conductive additive, with a specific reversible capacity of about 1520 mAh / g when normalized by the weight of the active material in the anode; (ii) a cathode comprising high voltage LCO active material cast onto an Al collector foil from an organic solvent suspension comprising a polyvinylidene fluoride (PVDF) based binder and carbon black conductive additive, with a specific reversible capacity of about 190 mAh / g when normalized by the weight of the active material in the cathode, with an anode:cathode areal capacity ratio of about 1.08:1 and a specific reversible capacity of about 3.27 mAh / cm. 2 and a charge voltage of about 4.4 V; (iii) a polymer ceramic separator; and (iv) an ELY #14 comprising: about 16.62 mol % FEC, about 34.49 mol % ethyl propionate (EP) (linear ester), about 29.63 mol % ethyl isobutyrate (EI) (branched ester), about 4.53 mol % VC, about 0.86 mol % adiponitrile (ADN), about 0.58 mol % 1,3,6-hexanetricarbonitrile (HTCN), about 1.21 mol % 1-propene-1,3-sultone (PES), about 0.96 mol % Li-difluoro(oxalato)borate (LiDFOB), and about 11.12 mol % LiPF6.
[0210] Li-ion battery test cells including ELY #13 and ELY #14 were tested in discharge rate tests. Test cells were assembled and initial formation procedures were performed on the test cells. The electrolytes in this series (#13, #14) contain FEC, VC, EP (linear ester), EI (branched ester), ADN, HTCN, and PES. The test cells contain a graphite and Si-C composite particle blend anode. The charging test conditions include 1C charge to 4.35V in CCCP, ramping to 0.05C. The discharge cell capacity measured at 2C is expressed as a fraction (%) of the discharge cell capacity measured at 0.5C. The ELY #13 cell (containing LFO) showed a discharge capacity fraction of 87%. The ELY #14 cell (containing LiDFOB) showed a discharge capacity fraction of 89%. Thus, ELY #14 showed a better discharge capacity fraction than ELY #13.
[0211] 18A and 18B (shown in FIG. 18) are graphical plots of capacity retention (% of initial capacity) as a function of cycle number for Li-ion battery cells containing ELY #6 and #7, respectively. FIGs. 18C and 18D are graphical plots of estimated cycles to 80% of initial capacity as a function of cycle number for Li-ion battery cells containing ELY #6 and #7, respectively. ELY #6 and #7 are examples of electrolytes containing esters.
[0212] 19A and 19B (shown in FIG. 19) are graphical plots of capacity retention (% of initial capacity) as a function of cycle number for Li-ion battery cells containing ELY #8 and #9, respectively. FIGs. 19C and 19D are graphical plots of estimated cycles to 80% of initial capacity as a function of cycle number for Li-ion battery cells containing ELY #8 and #9, respectively. ELY #8 and #9 are examples of electrolytes containing linear carbonates.
[0213] 20A, 20B, 20C, 20D, 20E and 20F (shown in FIG. 20-1, FIG. 20-2) show cycle life test results of Li-ion battery test cells containing electrolytes ELY #10, 11 and 12. FIG. 20A, 20B and 20C are graphical plots of capacity retention (% of initial capacity) as a function of cycle number for Li-ion battery cells containing ELY #10, #11 and #12, respectively. FIG. 20D, 20E and 20F are graphical plots of estimated cycle number to 80% of initial capacity as a function of cycle number for Li-ion battery cells containing ELY #10, #11 and #12, respectively. ELY #10, #11 and #12 are examples of electrolytes containing at least one cyclic carbonate and branched ester.
[0214] The above exemplary nanocomposite particles (e.g., anode or cathode particles) may generally be of any shape (e.g., approximately spherical, or spheroidal, or ellipsoidal (including, e.g., oblate spheroidal), cylindrical, plate-like, random shape, etc.) and of any size. The maximum size of the particles may depend on the rate performance requirements, the rate of ion diffusion into the partially filled particles, and / or other parameters. For most applications, the average diffusion distance from the solid electrolyte interphase (e.g., from the surface of the composite particle) to the inner core of the composite particle may be less than about 10 microns for optimal performance.
[0215] Some embodiments of the present disclosure are also applicable to conventional intercalation type electrodes (e.g., low voltage positive electrodes), particularly those with medium and high capacity loadings (e.g., about 3-4 mAh / cm 2 ) may provide the benefit of improved speed performance or improved stability.
[0216] In the detailed description above, it can be understood that different features in the examples are grouped together. This manner of disclosure should be understood as an intention that the example items have more features than are explicitly recited in each item. Rather, various aspects of the present disclosure may include less than all features of each disclosed example item.
[0217] In the detailed description above, it can be understood that different features are grouped together in the examples. This mode of disclosure should be understood as the intention that the example items have more features than are explicitly mentioned in each item. Rather, various aspects of the disclosure may include less than all features of each disclosed example item. Thus, the following items are hereby incorporated herein, and each item should be considered as being able to stand alone as a separate example. Although each dependent item may refer to a specific combination with one of the other items in that item, the aspect(s) of that dependent item are not limited to a specific combination. It will be recognized that other example items may also include combinations of the aspect(s) of the dependent item with any other dependent item or subject matter of the independent item, or any combination of features with other dependent items and independent items. Various aspects disclosed herein explicitly include these combinations, unless it is expressly expressed or readily inferred that a particular combination is not intended (e.g., a contradictory aspect such as defining an element as both an electrical insulator and an electrical conductor). It is further contemplated that aspects of an item may be included in another independent item even if the item is not directly dependent on the independent item.
[0218] Embodiments are described in the following numbered paragraphs.
[0219] Item 1. An electrolyte for a lithium ion battery comprising a primary lithium salt and a solvent composition comprising fluoroethylene carbonate (FEC), at least one linear ester and at least one branched ester, wherein the mole fraction of FEC in the electrolyte is in the range of about 2 mole % to about 30 mole %; the combined mole fraction of the at least one linear ester and the at least one branched ester in the electrolyte is at least about 45 mole %; the molar ratio of the at least one linear ester to the at least one branched ester is in the range of about 1:10 to about 20:1; and the electrolyte is substantially free of tetracarbon cyclic carbonates.
[0220] Item 2. The electrolyte of item 1, wherein the total mole fraction of the at least one linear ester and the at least one branched ester in the electrolyte is in the range of about 60 mol % to about 75 mol %.
[0221] Item 3. The electrolyte according to item 1 or 2, wherein the molar ratio of the at least one linear ester to the at least one branched ester is in the range of about 1:1 to about 2:1.
[0222] Item 4. The electrolyte according to any one of items 1 to 3, wherein the at least one linear ester is selected from methyl acetate (MA), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), ethyl propionate (EP), ethyl butyrate (EB), propyl acetate (PA), propyl propionate (PP), propyl butyrate (PB), butyl acetate (BA), butyl propionate (BP) and butyl butyrate (BB).
[0223] Item 5. At least one branched ester is selected from the group consisting of methyl isobutyrate (MI), methyl trimethylacetate (MT), methyl isovalerate (MIV), methyl 2-methylbutyrate (MMB), ethyl isobutyrate (EI), ethyl trimethylacetate (ET), ethyl isovalerate (EIV), ethyl 2-methylbutyrate (EMB), propyl isobutyrate (PI), propyl trimethylacetate (PT), propyl isovalerate (PIV), propyl 2-methylbutyrate (PMB), butyl isobutyrate (BI), butyl trimethylacetate (BT), butyl isovalerate (BIV), butyl 2-methylbutyrate (BMB), isopropyl acetate (IPA), isopropyl propionate (IPP), isopropyl butyrate (IPB), isopropyl isobutyrate (IPI), isopropyl trimethylacetate (PT), isopropyl trimethylacetate (PMB), isopropyl trimethylacetate (BIV), isopropyl trimethylacetate (BMB), isopropyl acetate (IPA), isopropyl propionate (IPP), isopropyl butyrate (IPB), isopropyl isobutyrate (IPI), isopropyl trimethylacetate (PT ... 5. The electrolyte according to any one of items 1 to 4, wherein the electrolyte is selected from isopropyl (IPT), isopropyl isovalerate (IPIV), isopropyl 2-methylbutyrate (IPMB), tert-butyl acetate (TBA), tert-butyl propionate (TBP), tert-butyl butyrate (TBB), tert-butyl isobutyrate (TBI), tert-butyl trimethylacetate (TBT), tert-butyl isovalerate (TBIV), tert-butyl 2-methylbutyrate (TBMB), isobutyl acetate (IBA), isobutyl propionate (IBP), isobutyl butyrate (IBB), isobutyl isobutyrate (IBI), isobutyl trimethylacetate (IBT), isobutyl isovalerate (IBIV), and isobutyl 2-methylbutyrate (IBMB).
[0224] Item 6. The electrolyte according to any one of items 1 to 5, wherein the at least one linear ester is ethyl propionate (EP) and the at least one branched ester is ethyl isobutyrate (EI) and / or ethyl isovalerate (EIV).
[0225] Item 7. The electrolyte of any one of items 1 to 6, which is substantially free of diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate.
[0226] Item 8. The electrolyte of any one of items 1 to 7, wherein the primary lithium salt is LiPF6.
[0227] Item 9. The electrolyte of item 8, wherein the mole fraction of the predominant lithium salt in the electrolyte is in the range of about 6 mol% to about 20 mol%.
[0228] Item 10. The electrolyte of any of items 1 to 9, further comprising one or more charge transfer additives selected from lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium fluorosulfate (LiSO3F), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
[0229] Item 11. The electrolyte of item 10, wherein the one or more charge transfer additives include lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluoro(oxalato)borate (LiDFOB).
[0230] Item 12. The electrolyte of items 10 or 11, wherein the mole fraction of the one or more charge transfer additives in the electrolyte is in the range of about 0.1 mol % to about 6 mol %.
[0231] Item 13. The electrolyte of item 12, wherein the mole fraction of the one or more charge transfer additives is in the range of about 0.5 mol % to about 1.5 mol %.
[0232] Item 14. Adiponitrile, 3-(2-cyanoethoxy)propanenitrile, 1,5-dicyanopentane, 1-(cyanomethyl)cyclopropane-1-carbonitrile, 4,4-dimethylheptanedinitrile, trans-1,4-dicyano-2-butene, 1,3,6-hexanetricarbonitrile, 3-{[1,3-bis(2-cyanoethoxy)propan-2-yl]oxy}propanenitrile, 1-(propan-2-yl)-1H-imidazole-4,5-dicarbonitrile, pyridine-2,6-dicarbonitrile, ethylene glycol bis(propionitrile) ether, 3-(triethoxysilyl)propionitrile, succinonitrile, benzonitrile, 4-(trifluoromethyl)benzonitrile 14. The electrolyte of any of items 1 to 13, further comprising one or more high temperature storage additives selected from trimethylsilyl, 1,2,2,3-propane tetracarbonitrile, triisopropyl borate, 1-propene 1,3-sultone, 1,3-propane sultone, phenyl disulfide, sulfolane, N,N,N,N-tetraethylsulfamide, succinic anhydride, maleic anhydride, tris(trimethylsilyl) phosphite, tris(trimethylsilyl) phosphate, dimethoxydiphenylsilane, tris(trimethylsilyl) borate, 3-(triethoxysilyl)propyl isocyanate, 1,3,2-dioxathiolane 2,2-dioxide (DTD), and methylene methane disulfonate (MMDS).
[0233] Item 15. The electrolyte of item 14, wherein the mole fraction of the one or more high temperature storage additives in the electrolyte is in the range of about 0.1 mol % to about 3 mol %.
[0234] Item 16. The electrolyte of any one of items 1 to 15, further comprising at least one non-FEC cyclic carbonate selected from ethylene carbonate and vinylene carbonate.
[0235] Item 17. The electrolyte of item 16, wherein the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte is in the range of about 0.5 mol % to about 30 mol %.
[0236] Item 18. The electrolyte of item 17, wherein the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte is in the range of about 1 mol % to about 6 mol %.
[0237] Item 19. A lithium ion battery comprising: a negative electrode current collector; a positive electrode current collector; a negative electrode disposed on and / or in the negative electrode current collector; a positive electrode disposed on and / or in the positive electrode current collector; and an electrolyte according to any of items 1 to 18 ionically connecting the negative electrode and the positive electrode.
[0238] Item 20. The lithium ion battery according to item 19, wherein the negative electrode comprises a mixture of (A) silicon-containing particles comprising silicon and carbon, and (B) graphitic carbon particles comprising carbon and substantially free of silicon; the mass of silicon is in the range of about 1.5% by weight to about 60% by weight of the total mass of the negative electrode.
[0239] Item 21. An electrolyte for a lithium ion battery comprising a primary lithium salt and a solvent composition comprising fluoroethylene carbonate (FEC), at least one ester and at least one non-FEC cyclic carbonate, wherein the mole fraction of FEC in the electrolyte is in the range of about 2 mol% to about 30 mol%; the total mole fraction of the at least one ester in the electrolyte is at least about 40 mol%; the total mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte is in the range of about 0.5 mol% to about 30 mol%; and the electrolyte is substantially free of tetracarbon cyclic carbonates.
[0240] Item 22. The electrolyte according to item 21, wherein the total mole fraction of the at least one ester in the electrolyte is in the range of about 45 mol % to about 70 mol %.
[0241] Item 23. The electrolyte according to items 21 or 22, wherein the molar ratio of the at least one ester to the at least one non-FEC cyclic carbonate is in the range of about 1.5:1 to about 20:1.
[0242] Item 24. At least one ester is selected from the group consisting of methyl acetate (MA), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), ethyl propionate (EP), ethyl butyrate (EB), propyl acetate (PA), propyl propionate (PP), propyl butyrate (PB), butyl acetate (BA), butyl propionate (BP), butyl butyrate (BB), methyl isobutyrate (MI), methyl trimethylacetate (MT), methyl isovalerate (MIV), methyl 2-methylbutyrate (MMB), ethyl isobutyrate (EI), ethyl trimethylacetate (ET), ethyl isovalerate (EIV), ethyl 2-methylbutyrate (EMB), propyl isobutyrate (PI), propyl trimethylacetate (PT), propyl isovalerate (PIV), propyl 2-methylbutyrate (PMB), butyl isobutyrate (BI), butyl trimethylacetate (BT), butyl isovalerate (BIV), butyl 2-methylbutyrate (BMB), isoacetate 24. The electrolyte according to any of items 21 to 23, selected from isopropyl (IPA), isopropyl propionate (IPP), isopropyl butyrate (IPB), isopropyl isobutyrate (IPI), isopropyl trimethylacetate (IPT), isopropyl isovalerate (IPIV), isopropyl 2-methylbutyrate (IPMB), tert-butyl acetate (TBA), tert-butyl propionate (TBP), tert-butyl butyrate (TBB), tert-butyl isobutyrate (TBI), tert-butyl trimethylacetate (TBT), tert-butyl isovalerate (TBIV), tert-butyl 2-methylbutyrate (TBMB), isobutyl acetate (IBA), isobutyl propionate (IBP), isobutyl butyrate (IBB), isobutyl isobutyrate (IBI), isobutyl trimethylacetate (IBT), isobutyl isovalerate (IBIV) and isobutyl 2-methylbutyrate (IBMB).
[0243] Item 25. The electrolyte of item 24, wherein the at least one ester comprises ethyl acetate (EA), ethyl propionate (EP), ethyl isobutyrate (EI), and / or ethyl isovalerate (EIV).
[0244] Item 26. The electrolyte of items 24 or 25, wherein the at least one ester comprises a mixture of ethyl acetate (EA) and ethyl propionate (EP).
[0245] Item 27. The electrolyte of any of items 21 to 26, wherein the at least one non-FEC cyclic carbonate is selected from ethylene carbonate and vinylene carbonate.
[0246] Item 28. The electrolyte of any one of items 21 to 27, which is substantially free of diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate.
[0247] Item 29. The electrolyte of any of items 21 to 28, wherein the primary lithium salt is LiPF6.
[0248] Item 30. The electrolyte according to item 29, wherein the mole fraction of the predominant lithium salt in the electrolyte is in the range of about 6 mol% to about 20 mol%.
[0249] Item 31. The electrolyte of any of items 21 to 30, further comprising one or more charge transfer additives selected from lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium fluorosulfate (LiSO3F), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
[0250] Item 32. The electrolyte of item 31, wherein the one or more charge transfer additives include lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluoro(oxalato)borate (LiDFOB).
[0251] Item 33. The electrolyte according to items 31 or 32, wherein the mole fraction of the one or more charge transfer additives in the electrolyte is in the range of about 0.1 mol % to about 6 mol %.
[0252] Item 34. The electrolyte of item 33, wherein the mole fraction of the one or more charge transfer additives is in the range of about 0.5 mol % to about 1.5 mol %.
[0253] Item 35. Adiponitrile, 3-(2-cyanoethoxy)propanenitrile, 1,5-dicyanopentane, 1-(cyanomethyl)cyclopropane-1-carbonitrile, 4,4-dimethylheptanedinitrile, trans-1,4-dicyano-2-butene, 1,3,6-hexanetricarbonitrile, 3-{[1,3-bis(2-cyanoethoxy)propan-2-yl]oxy}propanenitrile, 1-(propan-2-yl)-1H-imidazole-4,5-dicarbonitrile, pyridine-2,6-dicarbonitrile, ethylene glycol bis(propionitrile) ether, 3-(triethoxysilyl)propionitrile, succinonitrile, benzonitrile, 4-(trifluoromethyl)benzonitrile 35. The electrolyte of any of items 21 to 34, further comprising one or more high temperature storage additives selected from butyl ether, 1,2,2,3-propane tetracarbonitrile, triisopropyl borate, 1-propene 1,3-sultone, 1,3-propane sultone, phenyl disulfide, sulfolane, N,N,N,N-tetraethylsulfamide, succinic anhydride, maleic anhydride, tris(trimethylsilyl) phosphite, tris(trimethylsilyl) phosphate, dimethoxydiphenylsilane, tris(trimethylsilyl) borate, 3-(triethoxysilyl)propyl isocyanate, 1,3,2-dioxathiolane 2,2-dioxide (DTD), and methylene methane disulfonate (MMDS).
[0254] Item 36. The electrolyte of item 35, wherein the mole fraction of the one or more high temperature storage additives in the electrolyte is in the range of about 0.1 mol % to about 3 mol %.
[0255] Item 37. A lithium ion battery comprising: a negative electrode current collector; a positive electrode current collector; a negative electrode disposed on and / or in the negative electrode current collector; a positive electrode disposed on and / or in the positive electrode current collector; and an electrolyte according to item 21 ionically connecting the negative electrode and the positive electrode.
[0256] Item 38. The lithium ion battery according to item 37, wherein the negative electrode comprises a mixture of (A) silicon-containing particles comprising silicon and carbon, and (B) graphitic carbon particles comprising carbon and substantially free of silicon; and the mass of silicon is in the range of about 1.5% by weight to about 60% by weight of the total mass of the negative electrode.
[0257] Item 39. The lithium ion battery of items 37 or 38, wherein the negative electrode comprises graphitic carbon particles that contain carbon and are substantially free of silicon.
[0258] Item 40. An electrolyte for a lithium ion battery comprising a primary lithium salt and a solvent composition comprising fluoroethylene carbonate (FEC) and at least one linear carbonate, wherein the mole fraction of FEC in the electrolyte is in the range of about 2 mol % to about 20 mol %; the total mole fraction of the at least one linear carbonate in the electrolyte is at least 40 mol %; the electrolyte is substantially free of tetracarbon cyclic carbonates; and the electrolyte is substantially free of linear carbonates having a molecular weight greater than 117.
[0259] Item 41. The electrolyte of item 40, wherein the at least one linear carbonate is selected from ethyl methyl carbonate and dimethyl carbonate; and the total mole fraction of the at least one linear carbonate in the electrolyte is in the range of about 60 mol% to about 75 mol%.
[0260] Item 42. The electrolyte of any of items 39 to 41, wherein the primary lithium salt is LiPF6.
[0261] Item 43. The electrolyte according to item 41 or 42, wherein the mole fraction of the predominant lithium salt in the electrolyte is in the range of about 6 mol% to about 20 mol%.
[0262] Item 44. The electrolyte of any of items 40 to 43, further comprising one or more charge transfer additives selected from lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium fluorosulfate (LiSO3F), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
[0263] Item 45. The electrolyte of item 44, wherein the one or more charge transfer additives include lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), and / or lithium difluoro(oxalato)borate (LiDFOB).
[0264] Item 46. The electrolyte according to items 44 or 45, wherein the mole fraction of the one or more charge transfer additives in the electrolyte is in the range of about 0.1 mol % to about 6 mol %.
[0265] Item 47. The electrolyte of item 46, wherein the mole fraction of the one or more charge transfer additives is in the range of about 0.5 mol % to about 1.5 mol %.
[0266] Item 48. Adiponitrile, 3-(2-cyanoethoxy)propanenitrile, 1,5-dicyanopentane, 1-(cyanomethyl)cyclopropane-1-carbonitrile, 4,4-dimethylheptanedinitrile, trans-1,4-dicyano-2-butene, 1,3,6-hexanetricarbonitrile, 3-{[1,3-bis(2-cyanoethoxy)propan-2-yl]oxy}propanenitrile, 1-(propan-2-yl)-1H-imidazole-4,5-dicarbonitrile, pyridine-2,6-dicarbonitrile, ethylene glycol bis(propionitrile) ether, 3-(triethoxysilyl)propionitrile, succinonitrile, benzonitrile, 4-(trifluoromethyl)benzonitrile 48. The electrolyte of any of items 40 to 47, further comprising one or more high temperature storage additives selected from butyl ether, 1,2,2,3-propane tetracarbonitrile, triisopropyl borate, 1-propene 1,3-sultone, 1,3-propane sultone, phenyl disulfide, sulfolane, N,N,N,N-tetraethylsulfamide, succinic anhydride, maleic anhydride, tris(trimethylsilyl) phosphite, tris(trimethylsilyl) phosphate, dimethoxydiphenylsilane, tris(trimethylsilyl) borate, 3-(triethoxysilyl)propyl isocyanate, 1,3,2-dioxathiolane 2,2-dioxide (DTD), and methylene methane disulfonate (MMDS).
[0267] Item 49. The electrolyte of item 48, wherein the mole fraction of the one or more high temperature storage additives in the electrolyte is in the range of about 0.1 mol % to about 3 mol %.
[0268] Item 50. The electrolyte of any of items 40 to 49, further comprising at least one non-FEC cyclic carbonate selected from ethylene carbonate and vinylene carbonate.
[0269] Item 51. The electrolyte of item 50, wherein the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte is in the range of about 1 mol % to about 30 mol %.
[0270] Item 52. The electrolyte of item 51, wherein the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte is in the range of about 15 mol% to about 30 mol%.
[0271] Item 53. A lithium ion battery comprising: a negative electrode current collector; a positive electrode current collector; a negative electrode disposed on and / or in the negative electrode current collector; a positive electrode disposed on and / or in the positive electrode current collector; and an electrolyte according to item 40 ionically connecting the negative electrode and the positive electrode.
[0272] Item 54. The lithium ion battery according to item 53, wherein the negative electrode comprises a mixture of (A) silicon-containing particles comprising silicon and carbon, and (B) graphitic carbon particles comprising carbon and substantially free of silicon; and the mass of silicon is in the range of about 1.5% by weight to about 60% by weight of the total mass of the negative electrode.
[0273] Item 55. An electrolyte for a lithium ion battery comprising a primary lithium salt and a solvent composition comprising at least one tri-carbon cyclic carbonate and ethyl trimethylacetate (ET), wherein the at least one tri-carbon cyclic carbonate comprises ethylene carbonate (EC); the mole fraction of ET in the electrolyte is at least about 50 mole %; and the electrolyte is substantially free of tetra-carbon cyclic carbonates.
[0274] Item 56. The electrolyte according to item 55, wherein the mole fraction of ET in the electrolyte is in the range of about 50 mol% to about 80 mol%.
[0275] Item 57. The electrolyte of items 55 or 56, wherein the primary lithium salt is LiPF6.
[0276] Item 58. The electrolyte according to item 57, wherein the mole fraction of the predominant lithium salt in the electrolyte is in the range of about 6 mol% to about 20 mol%.
[0277] Item 59. The electrolyte according to any of items 55 to 58, wherein the mole fraction of the at least one tricarbon cyclic carbonate in the electrolyte is in the range of about 20 mol% to about 40 mol%.
[0278] Item 60. The electrolyte of any of items 55 to 59, wherein the at least one tricarbon cyclic carbonate comprises fluoroethylene carbonate (FEC) and / or vinylene carbonate.
[0279] Item 61. The electrolyte of any of items 55 to 60, which is substantially free of linear carbonates.
[0280] Item 62. A lithium ion battery comprising: a negative electrode current collector; a positive electrode current collector; a negative electrode disposed on and / or in the negative electrode current collector; a positive electrode disposed on and / or in the positive electrode current collector; and an electrolyte according to item 55 ionically connecting the negative electrode and the positive electrode.
[0281] Item 63. The lithium ion battery of item 62, wherein the negative electrode comprises graphitic carbon particles that include carbon and are substantially free of silicon.
[0282] The specification is provided to enable any person skilled in the art to make or use the embodiments of the invention, but it is understood that the invention is not limited to the particular formulations, process steps, and materials disclosed herein, since various modifications to those embodiments will be readily apparent to those skilled in the art, and that the generic principles defined herein may be applied to other embodiments without departing from the spirit or scope of the invention.
Claims
1. The main lithium salts, a solvent composition comprising fluoroethylene carbonate (FEC), at least one linear ester, and at least one branched ester; An electrolyte for a lithium ion battery comprising: the molar fraction of the FEC in the electrolyte is in the range of about 2 mol % to about 30 mol %; the combined mole fraction of said at least one linear ester and said at least one branched ester in the electrolyte is at least about 45 mole percent; a molar ratio of said at least one linear ester to said at least one branched ester ranging from about 1:10 to about 20:1; Substantially free of tetracarbon cyclic carbonates; Electrolytes.
2. 2. The electrolyte of claim 1, wherein the combined mole fraction of the at least one linear ester and the at least one branched ester in the electrolyte is in the range of about 60 mol % to about 75 mol %.
3. 2. The electrolyte of claim 1, wherein the molar ratio of said at least one linear ester to said at least one branched ester is in the range of about 1:1 to about 2:
1.
4. 2. The electrolyte of claim 1, wherein the at least one linear ester is selected from methyl acetate (MA), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), ethyl propionate (EP), ethyl butyrate (EB), propyl acetate (PA), propyl propionate (PP), propyl butyrate (PB), butyl acetate (BA), butyl propionate (BP) and butyl butyrate (BB).
5. The at least one branched ester is selected from the group consisting of methyl isobutyrate (MI), methyl trimethylacetate (MT), methyl isovalerate (MIV), methyl 2-methylbutyrate (MMB), ethyl isobutyrate (EI), ethyl trimethylacetate (ET), ethyl isovalerate (EIV), ethyl 2-methylbutyrate (EMB), propyl isobutyrate (PI), propyl trimethylacetate (PT), propyl isovalerate (PIV), propyl 2-methylbutyrate (PMB), butyl isobutyrate (BI), butyl trimethylacetate (BT), butyl isovalerate (BIV), butyl 2-methylbutyrate (BMB), isopropyl acetate (IPA), isopropyl propionate (IPP), isopropyl butyrate (IPB), isopropyl isobutyrate (IPI), trimethylacetate (PT), butyl 2-methylbutyrate (BMB), isopropyl acetate (IPA), isopropyl propionate (IPP), isopropyl butyrate (IPB), isopropyl isobutyrate (IPI), trimethylacetate (PT), butyl 2-methylbutyrate (BMB), isopropyl acetate (IPA), isopropyl propionate (IPP), isopropyl butyrate (IPB), isopropyl isobutyrate (IPI), trimethylacetate (PT), isopropyl ...
2. The electrolyte of claim 1, wherein the isopropyl trimethylacetate (IPT), isopropyl isovalerate (IPIV), isopropyl 2-methylbutyrate (IPMB), tert-butyl acetate (TBA), tert-butyl propionate (TBP), tert-butyl butyrate (TBB), tert-butyl isobutyrate (TBI), tert-butyl trimethylacetate (TBT), tert-butyl isovalerate (TBIV), tert-butyl 2-methylbutyrate (TBMB), isobutyl acetate (IBA), isobutyl propionate (IBP), isobutyl butyrate (IBB), isobutyl isobutyrate (IBI), isobutyl trimethylacetate (IBT), isobutyl isovalerate (IBIV), and isobutyl 2-methylbutyrate (IBMB).
6. 2. The electrolyte of claim 1, wherein the at least one linear ester is ethyl propionate (EP) and the at least one branched ester is ethyl isobutyrate (EI) and / or ethyl isovalerate (EIV).
7. 10. The electrolyte of claim 1, substantially free of diethyl carbonate, dimethyl carbonate and ethyl methyl carbonate.
8. The main lithium salt is LiPF 6 2. The electrolyte of claim 1 ,
9. 9. The electrolyte of claim 8, wherein the mole fraction of the majority lithium salt in the electrolyte ranges from about 6 mol % to about 20 mol %.
10. Lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF 4 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium fluorosulfate (LiSO 3 13. The electrolyte of claim 1 further comprising one or more charge transfer additives selected from lithium difluoro(oxalato)borate (LiDFOB), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
11. The charge transfer additive(s) may be lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF 4 11. The electrolyte of claim 10 comprising lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluoro(oxalato)borate (LiDFOB).
12. 11. The electrolyte of claim 10, wherein the mole fraction of the one or more charge transfer additives in the electrolyte ranges from about 0.1 mol % to about 6 mol %.
13. 13. The electrolyte of claim 12, wherein the mole fraction of the one or more charge transport additives is in the range of about 0.5 mol % to about 1.5 mol %.
14. Adiponitrile, 3-(2-cyanoethoxy)propanenitrile, 1,5-dicyanopentane, 1-(cyanomethyl)cyclopropane-1-carbonitrile, 4,4-dimethylheptanedinitrile, trans-1,4-dicyano-2-butene, 1,3,6-hexanetricarbonitrile, 3-{[1,3-bis(2-cyanoethoxy)propan-2-yl]oxy}propanenitrile, 1-(propan-2-yl)-1H-imidazole-4,5-dicarbonitrile, pyridine-2,6-dicarbonitrile, ethylene glycol bis(propionitrile) ether, 3-(triethoxysilyl)propionitrile, succinonitrile, benzonitrile, 4-(trifluoromethyl) 10. The electrolyte of claim 1, further comprising one or more high temperature storage additives selected from benzonitrile, 1,2,2,3-propane tetracarbonitrile, triisopropyl borate, 1-propene 1,3-sultone, 1,3-propane sultone, phenyl disulfide, sulfolane, N,N,N,N-tetraethylsulfamide, succinic anhydride, maleic anhydride, tris(trimethylsilyl phosphite), tris(trimethylsilyl phosphate), dimethoxydiphenylsilane, tris(trimethylsilyl borate), 3-(triethoxysilyl)propyl isocyanate, 1,3,2-dioxathiolane 2,2-dioxide (DTD), and methylene methane disulfonate (MMDS).
15. 15. The electrolyte of claim 14, wherein the mole fraction of the one or more high temperature storage additives in the electrolyte ranges from about 0.1 mol % to about 3 mol %.
16. 10. The electrolyte of claim 1 further comprising at least one non-FEC cyclic carbonate selected from ethylene carbonate and vinylene carbonate.
17. 17. The electrolyte of claim 16, wherein the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte ranges from about 0.5 mol % to about 30 mol %.
18. 20. The electrolyte of claim 17, wherein the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte ranges from about 1 mol % to about 6 mol %.
19. A negative electrode current collector; A positive electrode current collector; a negative electrode disposed on and / or in a negative electrode current collector; a positive electrode disposed on and / or in a positive electrode current collector; an electrolyte according to claim 1 ionically linking said negative electrode and said positive electrode; Including, lithium-ion battery.
20. the negative electrode comprises a mixture of (A) silicon-containing particles containing silicon and carbon, and (B) graphite carbon particles containing carbon and substantially no silicon; The mass of silicon is in the range of about 1.5% by weight to about 60% by weight of the total mass of the negative electrode; 20. The lithium ion battery of claim 19.
21. The main lithium salts, a solvent composition comprising fluoroethylene carbonate (FEC), at least one ester, and at least one non-FEC cyclic carbonate; An electrolyte for a lithium ion battery comprising: the molar fraction of the FEC in the electrolyte is in the range of about 2 mol % to about 30 mol %, the total mole fraction of the at least one ester in the electrolyte is at least about 40 mole percent; the total mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte ranges from about 0.5 mol % to about 30 mol %; the electrolyte is substantially free of tetracarbon cyclic carbonates; Electrolytes.
22. 22. The electrolyte of claim 21, wherein the total mole fraction of the at least one ester in the electrolyte is in the range of about 45 mole % to about 70 mole %.
23. 22. The electrolyte of claim 21, wherein the molar ratio of said at least one ester to said at least one non-FEC cyclic carbonate is in the range of about 1.5:1 to about 20:
1.
24. The at least one ester is selected from the group consisting of methyl acetate (MA), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), ethyl propionate (EP), ethyl butyrate (EB), propyl acetate (PA), propyl propionate (PP), propyl butyrate (PB), butyl acetate (BA), butyl propionate (BP), butyl butyrate (BB), methyl isobutyrate (MI), methyl trimethylacetate (MT), methyl isovalerate (MIV), methyl 2-methylbutyrate (MMB), ethyl isobutyrate (EI), ethyl trimethylacetate (ET), ethyl isovalerate (EIV), ethyl 2-methylbutyrate (EMB), propyl isobutyrate (PI), propyl trimethylacetate (PT), propyl isovalerate (PIV), propyl 2-methylbutyrate (PMB), butyl isobutyrate (BI), butyl trimethylacetate (BT), butyl isovalerate (BIV), and butyl 2-methylbutyrate (BMB).
22. The electrolyte of claim 21, wherein the isopropyl acetate is selected from isopropyl acetate (IPA), isopropyl propionate (IPP), isopropyl butyrate (IPB), isopropyl isobutyrate (IPI), isopropyl trimethylacetate (IPT), isopropyl isovalerate (IPIV), isopropyl 2-methylbutyrate (IPMB), tert-butyl acetate (TBA), tert-butyl propionate (TBP), tert-butyl butyrate (TBB), tert-butyl isobutyrate (TBI), tert-butyl trimethylacetate (TBT), tert-butyl isovalerate (TBIV), tert-butyl 2-methylbutyrate (TBMB), isobutyl acetate (IBA), isobutyl propionate (IBP), isobutyl butyrate (IBB), isobutyl isobutyrate (IBI), isobutyl trimethylacetate (IBT), isobutyl isovalerate (IBIV) and isobutyl 2-methylbutyrate (IBMB).
25. 25. The electrolyte of claim 24, wherein the at least one ester comprises ethyl acetate (EA), ethyl propionate (EP), ethyl isobutyrate (EI), and / or ethyl isovalerate (EIV).
26. 25. The electrolyte of claim 24, wherein the at least one ester comprises a mixture of ethyl acetate (EA) and ethyl propionate (EP).
27. 22. The electrolyte of claim 21 wherein the at least one non-FEC cyclic carbonate is selected from ethylene carbonate and vinylene carbonate.
28. 22. The electrolyte of claim 21, substantially free of diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate.
29. The main lithium salt is LiPF 6 22. The electrolyte of claim 21 ,
30. 30. The electrolyte of claim 29, wherein the mole fraction of the majority lithium salt in the electrolyte is in the range of about 6 mol% to about 20 mol%.
31. Lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF 4 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium fluorosulfate (LiSO 3 22. The electrolyte of claim 21 further comprising one or more charge transfer additives selected from lithium difluoro(oxalato)borate (LiDFOB), lithium difluoro(oxalato)borate (LiBOB), and lithium bis(oxalato)borate (LiBOB).
32. The charge transfer additive(s) may be lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF 4 32. The electrolyte of claim 31 comprising lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluoro(oxalato)borate (LiDFOB).
33. 32. The electrolyte of claim 31, wherein the mole fraction of the one or more charge transfer additives in the electrolyte ranges from about 0.1 mol % to about 6 mol %.
34. 34. The electrolyte of claim 33, wherein the mole fraction of the one or more charge transport additives is in the range of about 0.5 mol % to about 1.5 mol %.
35. Adiponitrile, 3-(2-cyanoethoxy)propanenitrile, 1,5-dicyanopentane, 1-(cyanomethyl)cyclopropane-1-carbonitrile, 4,4-dimethylheptanedinitrile, trans-1,4-dicyano-2-butene, 1,3,6-hexanetricarbonitrile, 3-{[1,3-bis(2-cyanoethoxy)propan-2-yl]oxy}propanenitrile, 1-(propan-2-yl)-1H-imidazole-4,5-dicarbonitrile, pyridine-2,6-dicarbonitrile, ethylene glycol bis(propionitrile) ether, 3-(triethoxysilyl)propionitrile, succinonitrile, benzonitrile, 4-(trifluoromethyl)benzyl 22. The electrolyte of claim 21, further comprising one or more high temperature storage additives selected from benzonitrile, 1,2,2,3-propane tetracarbonitrile, triisopropyl borate, 1-propene 1,3-sultone, 1,3-propane sultone, phenyl disulfide, sulfolane, N,N,N,N-tetraethylsulfamide, succinic anhydride, maleic anhydride, tris(trimethylsilyl phosphite), tris(trimethylsilyl phosphate), dimethoxydiphenylsilane, tris(trimethylsilyl borate), 3-(triethoxysilyl)propyl isocyanate, 1,3,2-dioxathiolane 2,2-dioxide (DTD), and methylene methanedisulfonate (MMDS).
36. 36. The electrolyte of claim 35, wherein the mole fraction of the one or more high temperature storage additives in the electrolyte is in the range of about 0.1 mol % to about 3 mol %.
37. A negative electrode current collector; A positive electrode current collector; a negative electrode disposed on and / or in a negative electrode current collector; a positive electrode disposed on and / or in a positive electrode current collector; 22. An electrolyte according to claim 21 ionically linking the negative electrode and the positive electrode; Including, lithium-ion battery.
38. the negative electrode comprises a mixture of (A) silicon-containing particles containing silicon and carbon, and (B) graphite carbon particles containing carbon and substantially no silicon; The mass of silicon is in the range of about 1.5% by weight to about 60% by weight of the total mass of the negative electrode; 38. The lithium ion battery of claim 37.
39. 38. The lithium ion battery of claim 37, wherein the negative electrode comprises graphitic carbon particles that comprise carbon and are substantially free of silicon.
40. The main lithium salts, a solvent composition comprising fluoroethylene carbonate (FEC) and at least one linear carbonate; An electrolyte for a lithium ion battery comprising: the molar fraction of the FEC in the electrolyte is in the range of about 2 mol % to about 20 mol %; the total mole fraction of said at least one linear carbonate in the electrolyte is at least 40 mole percent; the electrolyte is substantially free of tetracarbon cyclic carbonates; the electrolyte is substantially free of linear carbonates having a molecular weight greater than 117; Electrolytes.
41. the at least one linear carbonate is selected from ethyl methyl carbonate and dimethyl carbonate; the total mole fraction of the at least one linear carbonate in the electrolyte is in the range of about 60 mol % to about 75 mol %; 41. The electrolyte of claim 40.
42. The main lithium salt is LiPF 6 40. The electrolyte of claim 39, wherein:
43. 42. The electrolyte of claim 41, wherein the mole fraction of the majority lithium salt in the electrolyte is in the range of about 6 mol% to about 20 mol%.
44. Lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF 4 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium fluorosulfate (LiSO 3 41. The electrolyte of claim 40, further comprising one or more charge transfer additives selected from lithium difluoro(oxalato)borate (LiDFOB), lithium difluoro(oxalato)borate (LiBOB), and lithium bis(oxalato)borate (LiBOB).
45. The charge transfer additive(s) may be lithium difluorophosphate (LFO), lithium tetrafluoroborate (LiBF 4 ), lithium bis(fluorosulfonyl)imide (LiFSI), and / or lithium difluoro(oxalato)borate (LiDFOB).
46. 45. The electrolyte of claim 44, wherein the mole fraction of the one or more charge transfer additives in the electrolyte ranges from about 0.1 mol % to about 6 mol %.
47. 47. The electrolyte of claim 46, wherein the mole fraction of the one or more charge transport additives is in the range of about 0.5 mol % to about 1.5 mol %.
48. Adiponitrile, 3-(2-cyanoethoxy)propanenitrile, 1,5-dicyanopentane, 1-(cyanomethyl)cyclopropane-1-carbonitrile, 4,4-dimethylheptanedinitrile, trans-1,4-dicyano-2-butene, 1,3,6-hexanetricarbonitrile, 3-{[1,3-bis(2-cyanoethoxy)propan-2-yl]oxy}propanenitrile, 1-(propan-2-yl)-1H-imidazole-4,5-dicarbonitrile, pyridine-2,6-dicarbonitrile, ethylene glycol bis(propionitrile) ether, 3-(triethoxysilyl)propionitrile, succinonitrile, benzonitrile, 4-(trifluoromethyl)benzyl 41. The electrolyte of claim 40, further comprising one or more high temperature storage additives selected from benzonitrile, 1,2,2,3-propane tetracarbonitrile, triisopropyl borate, 1-propene 1,3-sultone, 1,3-propane sultone, phenyl disulfide, sulfolane, N,N,N,N-tetraethylsulfamide, succinic anhydride, maleic anhydride, tris(trimethylsilyl phosphite), tris(trimethylsilyl phosphate), dimethoxydiphenylsilane, tris(trimethylsilyl borate), 3-(triethoxysilyl)propyl isocyanate, 1,3,2-dioxathiolane 2,2-dioxide (DTD), and methylene methane disulfonate (MMDS).
49. 49. The electrolyte of claim 48, wherein the mole fraction of the one or more high temperature storage additives in the electrolyte is in the range of about 0.1 mol % to about 3 mol %.
50. 41. The electrolyte of claim 40 further comprising at least one non-FEC cyclic carbonate selected from ethylene carbonate and vinylene carbonate.
51. 51. The electrolyte of claim 50, wherein the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte ranges from about 1 mol % to about 30 mol %.
52. 52. The electrolyte of claim 51, wherein the mole fraction of the at least one non-FEC cyclic carbonate in the electrolyte is in the range of about 15 mol% to about 30 mol%.
53. A negative electrode current collector; A positive electrode current collector; a negative electrode disposed on and / or in a negative electrode current collector; a positive electrode disposed on and / or in a positive electrode current collector; 41. An electrolyte according to claim 40 ionically linking said negative electrode and said positive electrode; Including, lithium-ion battery.
54. the negative electrode comprises a mixture of (A) silicon-containing particles containing silicon and carbon, and (B) graphite carbon particles containing carbon and substantially no silicon; The mass of silicon is in the range of about 1.5% by weight to about 60% by weight of the total mass of the negative electrode; 54. The lithium ion battery of claim 53.
55. the primary lithium salt; a solvent composition comprising at least one tricarbon cyclic carbonate and ethyl trimethylacetate (ET); An electrolyte for a lithium ion battery comprising: the at least one tricarbon cyclic carbonate comprises ethylene carbonate (EC); the mole fraction of said ET in the electrolyte is at least about 50 mole %; the electrolyte is substantially free of tetracarbon cyclic carbonates; Electrolytes.
56. 56. The electrolyte of claim 55, wherein the mole fraction of ET in the electrolyte is in the range of about 50 mol% to about 80 mol%.
57. The main lithium salt is LiPF 6 56. The electrolyte of claim 55,
58. 58. The electrolyte of claim 57, wherein the mole fraction of the majority lithium salt in the electrolyte is in the range of about 6 mol% to about 20 mol%.
59. 56. The electrolyte of claim 55, wherein the mole fraction of the at least one tricarbon cyclic carbonate in the electrolyte is in the range of about 20 mol % to about 40 mol %.
60. 56. The electrolyte of claim 55, wherein the at least one tricarbon cyclic carbonate comprises fluoroethylene carbonate (FEC) and / or vinylene carbonate.
61. 56. The electrolyte of claim 55, which is substantially free of linear carbonates.
62. A negative electrode current collector; A positive electrode current collector; a negative electrode disposed on and / or in a negative electrode current collector; a positive electrode disposed on and / or in a positive electrode current collector; 56. An electrolyte according to claim 55 ionically linking said negative electrode and said positive electrode; Including, lithium-ion battery.
63. 63. The lithium ion battery of claim 62, wherein the negative electrode comprises graphitic carbon particles comprising carbon and substantially free of silicon.